Photosensitive transfer material, resin pattern manufacturing method, conductive pattern manufacturing method, and touch sensor
Patent Information
- Application Number
- JP2023179864
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-07-06
- Filing Date
- 2023-10-18
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-08-26
AI Technical Summary
【0009】 本開示の一実施形態によれば、ピンホールの発生が抑制された樹脂パターンを形成する感光性転写材料が提供される。 本開示の他の一実施形態によれば、ピンホールの発生が抑制された樹脂パターンの製造方法が提供される。 本開示の他の一実施形態によれば、ピンホールの発生が抑制された導電パターンの製造方法が提供される。 本開示の他の一実施形態によれば、ピンホールの発生が抑制された導電パターンを含むタッチセンサーを提供が提供される。
Smart Images

Figure 0007642037000037 
Figure 0007642037000038 
Figure 0007642037000039
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a photosensitive transfer material, a method for producing a resin pattern, a method for producing a conductive pattern, and a touch sensor. [Background technology]
[0002] In a display device (e.g., an organic electroluminescence (EL) display device and a liquid crystal display device) equipped with a touch panel such as a capacitance type input device, the touch panel includes a conductive pattern. The conductive pattern is used, for example, as a sensor of a visual recognition section, peripheral wiring, or take-out wiring. In a method for manufacturing a pattern such as a conductive pattern or a resin pattern, for example, a method including a step of providing a photosensitive resin layer and a temporary support on a substrate using a photosensitive transfer material, a step of exposing the photosensitive resin layer in a pattern via the temporary support, and a step of developing the exposed photosensitive resin layer is widely adopted.
[0003] In order to avoid a decrease in resolution caused by foreign matter contained in the temporary support, JP 2019-101405 A discloses a photosensitive resin laminate roll in which the number of fine particles having a diameter of 2 μm or more is limited. Summary of the Invention [Problem to be solved by the invention]
[0004] As the conductive pattern becomes finer, in other words, the required resolution improves, the failure of the conductive pattern (especially pinholes) caused by foreign matter (e.g., coarse particles) contained in the temporary support becomes apparent. The foreign matter contained in the temporary support inhibits the exposure of the photosensitive resin layer, causing failure of the resin pattern (e.g., pinholes). For example, when a resin pattern containing pinholes is used as a protective film in etching for forming a conductive pattern, pinholes are generated in the conductive pattern. Therefore, there is a demand for reducing the pinholes generated in the resin pattern.
[0005] An object of one embodiment of the present disclosure is to provide a photosensitive transfer material that forms a resin pattern in which the occurrence of pinholes is suppressed. Another embodiment of the present disclosure has an object to provide a method for producing a resin pattern in which the occurrence of pinholes is suppressed. Another embodiment of the present disclosure has an object to provide a method for manufacturing a conductive pattern in which the occurrence of pinholes is suppressed. Another embodiment of the present disclosure has an object to provide a touch sensor including a conductive pattern in which the occurrence of pinholes is suppressed. [Means for solving the problem]
[0006] The present disclosure encompasses the following aspects. <1> A film comprising a temporary support and a photosensitive resin layer in this order, the limit resolution of the photosensitive resin layer is defined as X μm, and the reference diameter of a particle is defined as Y μm expressed by the formula (1): Y = 0.75 × X, the number of particles having a diameter of Y μm or more in the temporary support is 15 particles / cm 2 A photosensitive transfer material, which is: <2> The number of particles having a diameter of 10.5 μm or more in the temporary support is 1.0 particle / cm 2 Below is the <1> 2. The photosensitive transfer material according to claim 1 . <3> The thickness of the temporary support is 16 μm or less. <1> or <2> 2. The photosensitive transfer material according to claim 1 . <4> The thickness of the photosensitive resin layer is 5 μm or less. <1> ~ <3> 10. The photosensitive transfer material according to claim 9,
[0007] <5> A photosensitive transfer material comprising a temporary support and a photosensitive resin layer in this order, the temporary support being a polyester film consisting of two or more layers, at least one of the surface layers not containing a filler. <6> The surface layer of the temporary support on the photosensitive resin layer side does not contain a filler. <5> 2. The photosensitive transfer material according to claim 1 . <7> When the limit resolution of the photosensitive resin layer is defined as X μm and the reference diameter of the particle is defined as Y μm expressed by the formula (1): Y = 0.75 × X, the number of particles having a diameter of Y μm or more in the temporary support is 15 particles / cm 2 Below is the <5> or <6> 2. The photosensitive transfer material according to claim 1 . <8> The arithmetic average roughness Ra of the surface of the temporary support opposite to the photosensitive resin layer is 1 nm to 50 nm. <5> ~ <7> 10. The photosensitive transfer material according to claim 9, <9> The surface layer has a phase separation structure. <5> ~ <8> 10. The photosensitive transfer material according to claim 9, <10> The surface layer contains a polyester resin having an alicyclic structure. <5> ~ <9> 10. The photosensitive transfer material according to claim 9, <11> The alicyclic structure is a cyclohexane ring. <10> 2. The photosensitive transfer material according to claim 1 . <12> The surface layer contains copolymerized polyethylene terephthalate having isophthalic acid as a copolymerization component. <10> or <11> 2. The photosensitive transfer material according to claim 1 .
[0008] <13> <1> ~ <12> 1. A method for producing a resin pattern using the photosensitive transfer material described in any one of claims 1 to 9, comprising the steps of: preparing a substrate; contacting the photosensitive transfer material with the substrate, and arranging a photosensitive resin layer and a temporary support in this order on the substrate; exposing the photosensitive resin layer to a pattern; and developing the exposed photosensitive resin layer to form a resin pattern. <14> The line width of the resin pattern is 10 μm or less. <13> 2. A method for producing a resin pattern according to claim 1 . <15> <1> ~ <12> 13. A method for producing a conductive pattern using the photosensitive transfer material according to any one of claims 1 to 12, comprising the steps of: preparing a substrate including a conductive layer; bringing the photosensitive transfer material into contact with the substrate, and arranging a photosensitive resin layer and a temporary support in this order on the substrate; exposing the photosensitive resin layer to a pattern; developing the exposed photosensitive resin layer to form a resin pattern; and etching the conductive layer that is not covered by the resin pattern to form a conductive pattern. <16> <15> A touch sensor comprising a conductive pattern obtained by the conductive pattern manufacturing method described above. Effect of the Invention
[0009] According to one embodiment of the present disclosure, there is provided a photosensitive transfer material that forms a resin pattern in which the occurrence of pinholes is suppressed. According to another embodiment of the present disclosure, there is provided a method for producing a resin pattern in which the occurrence of pinholes is suppressed. According to another embodiment of the present disclosure, there is provided a method for manufacturing a conductive pattern in which the occurrence of pinholes is suppressed. According to another embodiment of the present disclosure, a touch sensor is provided that includes a conductive pattern in which the occurrence of pinholes is suppressed. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 is a schematic side view showing the layer structure of the photosensitive transfer material according to the present disclosure. [Diagram 2] FIG. 2 is a schematic side view showing another layer configuration of the photosensitive transfer material according to the present disclosure. [Diagram 3] FIG. 2 is a schematic side view showing another layer configuration of the photosensitive transfer material according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, embodiments of the present disclosure will be described in detail. The present disclosure is not limited to the following embodiments. The following embodiments may be modified as appropriate within the scope of the present disclosure.
[0012] When describing the embodiments of the present disclosure with reference to the drawings, the description of the overlapping components and symbols in the drawings may be omitted. Components indicated by the same symbols in the drawings are the same components. The dimensional ratios in the drawings do not necessarily represent the actual dimensional ratios.
[0013] In the present disclosure, a numerical range indicated using "~" indicates a range including the numerical values described before and after "~" as the lower and upper limits, respectively. In the numerical ranges described in stages in the present disclosure, the upper or lower limit described in a certain numerical range may be replaced with the upper or lower limit of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit described in a certain numerical range may be replaced with a value shown in the examples.
[0014] In the present disclosure, the term "process" includes not only independent processes, but also processes that cannot be clearly distinguished from other processes as long as the intended purpose of the process is achieved.
[0015] In the present disclosure, "mass %" and "weight %" are synonymous, and "parts by mass" and "parts by weight" are synonymous.
[0016] In the present disclosure, when a composition contains multiple substances corresponding to a certain component, the amount of the above component in the composition means the total amount of the above substances present in the composition, unless otherwise specified.
[0017] In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments.
[0018] In this disclosure, ordinal numbers (e.g., "first" and "second") are terms used to distinguish between multiple components, and do not limit the number of components or the priority of the components.
[0019] In the present disclosure, a group (atomic group) that does not specify whether it is substituted or unsubstituted includes a group having a substituent and a group having no substituent. For example, the expression "alkyl group" includes an alkyl group having a substituent (a substituted alkyl group) and an alkyl group having no substituent (an unsubstituted alkyl group).
[0020] In the present disclosure, chemical structural formulas may be represented as simplified structural formulas in which hydrogen atoms are omitted.
[0021] In this disclosure, "(meth)acrylic acid" means acrylic acid or methacrylic acid.
[0022] In this disclosure, "(meth)acrylate" means acrylate or methacrylate.
[0023] In the present disclosure, a "(meth)acryloyl group" means an acryloyl group or a methacryloyl group.
[0024] In this disclosure, unless otherwise specified, "exposure" includes not only exposure using light but also drawing using particle beams such as electron beams and ion beams. Examples of light used for exposure include the bright line spectrum of a mercury lamp, far ultraviolet light and extreme ultraviolet light (EUV (Extreme ultraviolet lithography) light) represented by an excimer laser, and active light rays (active energy rays) such as X-rays.
[0025] In this disclosure, unless otherwise specified, the weight average molecular weight (Mw) and number average molecular weight (Mn) are molecular weights obtained by detecting a compound in tetrahydrofuran (THF) with a differential refractometer using a gel permeation chromatography (GPC) analyzer equipped with columns of TSKgel GMHxL (Tosoh Corporation), TSKgel G4000HxL (Tosoh Corporation), and TSKgel G2000HxL (Tosoh Corporation), and converting the molecular weight using polystyrene as a standard substance.
[0026] In this disclosure, unless otherwise specified, the refractive index is a value measured using an ellipsometer at a wavelength of 550 nm.
[0027] In the present disclosure, the term "solid content" refers to all components of a target object excluding the solvent.
[0028] <Photosensitive transfer material> The photosensitive transfer material according to the first embodiment of the present disclosure includes a temporary support and a photosensitive resin layer in this order. When the limit resolution of the photosensitive resin layer is defined as X μm and the reference diameter of a particle is defined as Y μm represented by the formula (1): Y = 0.75 × X, the number of particles having a diameter of Y μm or more in the temporary support is 15 particles / cm. 2 The following is the result. According to the above-described first embodiment, there is provided a photosensitive transfer material that forms a resin pattern in which the occurrence of pinholes is suppressed.
[0029] The estimated reason why the above-mentioned effect is manifested is explained below. As described above, the coarse particles contained in the temporary support hinder the exposure of the photosensitive resin layer and cause pinholes in the resin pattern. For example, in the technology disclosed in JP 2019-101405 A, the number of fine particles having a diameter of 2 μm or more is limited to avoid a decrease in resolution caused by foreign matter contained in the temporary support. However, the size of the particles that cause exposure damage varies depending on the required resolution. As the required resolution becomes smaller, even fine particles that were tolerated in conventional technology hinder the exposure of the photosensitive resin layer. Therefore, the inventor of the present disclosure focused on the relationship between the size and number of particles contained in the temporary support and the resolution of the photosensitive resin layer. By verifying the relationship between the resolution of the photosensitive resin layer and the size of particles that cause exposure damage, the inventor of the present disclosure revealed that particles having a diameter of Y (Y = 0.75 × X) μm or more lead to an increase in the incidence of exposure damage with respect to the limit resolution (X) of the photosensitive resin layer. In the photosensitive transfer material according to the first embodiment of the present disclosure, the number of particles having a diameter of Y μm or more on the temporary support is set to 15 particles / cm according to the reference diameter (Y) of the particles derived from the limit resolution (X) of the photosensitive resin layer. 2 The incidence of exposure damage can be reduced by adjusting as follows. Therefore, according to the photosensitive transfer material according to the first embodiment of the present disclosure, a photosensitive transfer material that forms a resin pattern in which the occurrence of pinholes is suppressed is provided.
[0030] The photosensitive transfer material according to the second embodiment of the present disclosure comprises, in this order, a temporary support and a photosensitive resin layer, wherein the temporary support is a polyester film consisting of two or more layers, and at least one of the surface layers (i.e., at least one of the layer arranged as the outermost layer on the first surface side and the layer arranged as the outermost layer on the second surface side) does not contain a filler. The above-mentioned second embodiment also provides a photosensitive transfer material that forms a resin pattern in which the occurrence of pinholes is suppressed.
[0031] In addition, in the present disclosure, when the term "photosensitive transfer material according to the present disclosure" or "photosensitive transfer material" is used without any particular specification, it refers to both the first embodiment and the second embodiment.
[0032] <<Temporary support>> The photosensitive transfer material according to the present disclosure includes a temporary support. In the photosensitive transfer material, the temporary support supports at least a photosensitive resin layer. In the photosensitive transfer material, the temporary support is a member that can be peeled off from an adjacent layer (e.g., a photosensitive resin layer). Hereinafter, in the photosensitive transfer material, the main surface of the temporary support facing the photosensitive resin layer is referred to as the second surface, and the main surface opposite to the second surface of the temporary support is referred to as the first surface.
[0033] <Temporary Support in the Photosensitive Transfer Material According to the First Embodiment of the Present Disclosure> Hereinafter, the temporary support (hereinafter also referred to as temporary support (1)) in the photosensitive transfer material according to the first embodiment of the present disclosure will be described. In the photosensitive transfer material according to the first embodiment of the present disclosure, when the limit resolution of the photosensitive resin layer is defined as X μm and the reference diameter of the particle is defined as Y μm expressed by the formula (1): Y = 0.75 × X, the number of particles having a diameter of Y μm or more on the temporary support (hereinafter, sometimes referred to as the "number of specific particles (A)") is 15 particles / cm. 2 The number of specific particles (A) on the temporary support (1) is 15 / cm or less. 2 By keeping the number of specific particles (A) at 14 / cm or less, the incidence of exposure damage is reduced and the occurrence of pinholes is suppressed. 2 Preferably less than 12 pieces / cm 2 More preferably, 9 particles / cm or less. 2 It is particularly preferable that the number of specific particles (A) is 7 / cm or less. 2 Preferably, 6 or less per cm 2 More preferably, 5 or less per cm 2 It is particularly preferable that the number of specific particles (A) is not limited. The number of specific particles (A) is, for example, 0 particles / cm.2 The number of specific particles (A) may be determined within the above range. 2 Or 0 pieces / cm 2 It may be more than 10 ...
[0034] The limit resolution (X) of the photosensitive resin layer will be described below. In the present disclosure, the limit resolution of the photosensitive resin layer is defined as X μm. The term "μm" used with respect to X μm is a unit of length, i.e., micrometer. The limit resolution (X) of the photosensitive resin layer is preferably 15 μm or less, more preferably 10 μm or less, and particularly preferably 7 μm or less. The lower limit of the limit resolution (X) of the photosensitive resin layer is not limited. The lower limit of the limit resolution (X) of the photosensitive resin layer may be, for example, 0.5 μm, 1 μm, or 2 μm. The limit resolution (X) of the photosensitive resin layer is adjusted, for example, according to the composition of the photosensitive resin layer, the thickness of the photosensitive resin layer, and the distance between the mask and the substrate during exposure. The limit resolution (X) of the photosensitive resin layer is determined by the following method. (1) A photosensitive transfer material is brought into contact with a polyethylene terephthalate (PET) film having a thickness of 100 μm, and a photosensitive resin layer and a temporary support are placed on the PET film in this order. That is, a laminate containing at least a PET film, a photosensitive resin layer, and a temporary support in this order is obtained by laminating the PET film and the photosensitive transfer material. In the laminate, the configuration of the layer placed on the PET film varies depending on the layer configuration of the photosensitive transfer material. (2) The obtained laminate is pressurized and degassed for 30 minutes using an autoclave under conditions of 0.6 MPa and 60° C. (3) Using an ultra-high pressure mercury lamp, the photosensitive resin layer is exposed through a line and space pattern mask (the duty ratio is 1:1, and the line width changes stepwise from 1 μm to 20 μm at 1 μm intervals) without peeling off the temporary support. (4) After peeling off the temporary support, development is performed. Development is performed by shower development for 30 seconds using a 1.0 mass % sodium carbonate aqueous solution at 25° C. The photosensitive resin layer is developed to form a resin pattern. The exposure dose (unit: mJ / cm2) is increased until a resin pattern having a minimum line width corresponding to the mask pattern (hereinafter referred to as the "reference pattern" in this paragraph) is obtained. 2 The above-mentioned series of steps (1) to (4) are carried out while adjusting the above-mentioned step size (X) and the step size (X) for each step. If necessary, a mask having a line width of less than 1 μm may be used. The minimum line width of the reference pattern is adopted as the limit resolution (X) of the photosensitive resin layer.
[0035] The particle reference diameter (Y) will be described below. In this disclosure, the particle reference diameter is defined as Y μm, which is expressed by the formula (1): Y = 0.75 × X. The term "X" used in relation to the formula (1) is the limit resolution (X) of the photosensitive resin layer. The unit of X is micrometers. The term "μm" used in relation to Y μm is a unit of length, i.e., micrometers.
[0036] In the present disclosure, the number of specific particles (A) is measured by the following method. The number of specific particles (A) is measured by measuring the number of specific particles (A) in 10 arbitrary regions (size of each region: 10 mm × 10 mm, total area: 1000 mm) on the surface of the temporary support. 2 ) is visually observed using an optical microscope. The number of particles with a diameter of Y μm or more contained in each region is counted. The "diameter" is the maximum value of the line connecting two points on the outline of the particle in a plan view. Based on the total number of particles measured in 10 regions, the particle diameter is calculated for 1 cm of the measurement region. 2 Number of particles per cm 2 The value obtained is used as the number of specific particles (A).
[0037] From the viewpoint of reducing pinholes, the number of particles having a diameter of 10.5 μm or more in the temporary support (1) (hereinafter sometimes referred to as the “number of specific particles (B)”) is 1.0 particle / cm 2 It is preferable that the number of particles is less than 0.5 / cm. 2 More preferably, it is 0.2 particles / cm or less. 2 It is particularly preferable that the number of specific particles (B) is not limited. The lower limit of the number of specific particles (B) is, for example, 0 particles / cm. 2 The number of specific particles (B) may be determined within the above range. 2 Or 0 pieces / cm 2 The number of specific particles (B) may be greater than 1000. The number of specific particles (B) is measured by a method similar to the method for measuring the number of specific particles (A). The number of specific particles (B) is adjusted by a method similar to the method for adjusting the number of specific particles (A).
[0038] The particles in the temporary support (1) (including specific particles (A) and specific particles (B) (hereinafter the same in this paragraph) may be a particulate compound added when the temporary support (1) is produced. The particles in the temporary support (1) may be particles produced by precipitation or crystallization during polycondensation, stretching or cooling process of an additive added when the temporary support is produced.
[0039] Examples of particulate compounds include inorganic particles and organic particles. Examples of inorganic particles include particles containing inorganic oxides. Examples of inorganic oxides include silicon oxide (silica), titanium oxide (titania), zirconium oxide (zirconia), magnesium oxide (magnesia), and aluminum oxide (alumina). Examples of organic particles include particles containing polymers. Examples of polymers include acrylic resins, polyesters, polyurethanes, polycarbonates, polyolefins, and polystyrenes.
[0040] Examples of additives that can be added during the preparation of the temporary support (1) include a reaction catalyst for polycondensation, a coloring inhibitor, and a film-forming agent.
[0041] Examples of reaction catalysts for polycondensation include alkali metal compounds, alkaline earth metal compounds, zinc compounds, lead compounds, manganese compounds, cobalt compounds, aluminum compounds, antimony compounds, titanium compounds, and phosphorus compounds. Usually, antimony compounds, germanium compounds, or titanium compounds are preferably used as polymerization catalysts at any stage before the completion of the polyester production process.
[0042] Examples of the coloring inhibitor include phosphate compounds. Examples of the phosphate compounds include pentavalent phosphates that do not have an aromatic ring as a substituent. Examples of the pentavalent phosphates that do not have an aromatic ring as a substituent include phosphates that have a lower alkyl group with 2 or less carbon atoms as a substituent [(RO)3-P=O, R=an alkyl group with 1 or 2 carbon atoms]. Examples of the compound represented by "(RO)3-P=O" include trimethyl phosphate and triethyl phosphate.
[0043] Examples of the film-forming agent include alkali metal and alkaline earth metal compounds. In particular, magnesium compounds are preferably used in the manufacture of a temporary support or in the manufacture of a polyester used as a raw material for a temporary support. By including a magnesium compound in a polyester, the electrostatic applicability of the polyester is improved. In this case, coloring is likely to occur, but by using the compound in combination with a coloring inhibitor, coloring is suppressed and excellent color tone and heat resistance are obtained. Examples of the magnesium compound include magnesium salts. Examples of the magnesium salts include magnesium oxide, magnesium hydroxide, magnesium alkoxide, magnesium acetate, and magnesium carbonate. Among these, magnesium acetate is most preferably used from the viewpoint of solubility in ethylene glycol.
[0044] The shape of the particles is not limited. Examples of the shape of the particles in a plan view include a circle, an ellipse, a polygon, and an irregular shape.
[0045] The particles may be transparent particles, translucent particles or colored, such as black.
[0046] The temporary support (1) preferably has optical transparency. In the present disclosure, "having optical transparency" means that the transmittance at the wavelength used for pattern exposure is 50% or more. From the viewpoint of improving the exposure sensitivity of the photosensitive resin layer, the transmittance of the temporary support (1) at the wavelength used for pattern exposure (more preferably a wavelength of 365 nm) is preferably 60% or more, more preferably 70% or more. The transmittance is the ratio of the intensity of light (outgoing light) that has passed through an object to the intensity of light (incident light) that is incident perpendicularly to the main surface of the object. The transmittance is measured using a known spectrometer (for example, "MCPD Series", Otsuka Electronics Co., Ltd.).
[0047] The thickness of the temporary support (1) is not limited. From the viewpoints of the strength as a support, the flexibility required for lamination with a substrate, and the light transmittance required for exposure, the thickness of the temporary support (1) may be determined according to the material. From the viewpoints of ease of handling and versatility, the thickness of the temporary support (1) is preferably 100 μm or less, more preferably 50 μm or less, even more preferably 20 μm or less, and particularly preferably 16 μm or less. From the viewpoints of ease of handling and versatility, the thickness of the temporary support (1) is preferably 5 μm or more, more preferably 10 μm or more. Furthermore, as the thickness of the temporary support (1) becomes thinner, the volume of the temporary support decreases, and the absolute amount of particles contained in the temporary support per unit area decreases. The thickness of the temporary support is measured by the following method. A cross section of the temporary support along the thickness direction (perpendicular to the main surface of the temporary support) is observed using a scanning electron microscope (SEM) or a transmission electron microscope (TEM). The thickness of the temporary support is measured at 10 points based on the observed image, and the measured values are arithmetically averaged. The obtained value is used as the thickness of the temporary support.
[0048] The layer structure of the temporary support (1) is not limited. The temporary support (1) may be a temporary support having a single-layer structure or a temporary support having a multilayer structure. The layer structure of the temporary support (1) will be described below. However, the layer structure of the temporary support (1) is not limited to the layer structure shown below.
[0049] Examples of the temporary support (1) having a single layer structure include glass substrates, resin films, and paper. From the viewpoints of strength, flexibility, and light transmittance, resin films are preferred. Examples of the resin film include polyethylene terephthalate (PET) films, cellulose triacetate films, polystyrene films, and polycarbonate films. Among the above, PET films are preferred, and biaxially stretched PET films are more preferred. Examples of the method for producing the resin film include extrusion molding.
[0050] The multilayered temporary support (1) may, for example, include a temporary support including a base material and a particle-containing layer. The multilayered temporary support (1) may include a layer (for example, an adhesive layer) other than the particle-containing layer.
[0051] From the viewpoint of transportability, the temporary support (1) preferably includes, in the stacking direction from the temporary support toward the photosensitive resin layer, a particle-containing layer (hereinafter sometimes referred to as a "first particle-containing layer") arranged as the outermost layer of the temporary support, and a base material, in this order. In other words, the temporary support (1) preferably includes a base material and a particle-containing layer (first particle-containing layer) arranged as the outermost layer on the first surface side of the temporary support, in this order. The surface of the first particle-containing layer includes the first surface of the temporary support (1).
[0052] From the viewpoint of ensuring transportability during the manufacture of the temporary support, the temporary support (1) may include, in the lamination direction from the temporary support toward the photosensitive resin layer, a base material and a particle-containing layer (hereinafter, sometimes referred to as a "second particle-containing layer") arranged as the outermost layer of the temporary support, in this order. In other words, the temporary support (1) may include a base material and a particle-containing layer (second particle-containing layer) arranged as the outermost layer on the second surface side of the temporary support, in this order. The surface of the second particle-containing layer includes the second surface of the temporary support (1).
[0053] The temporary support (1) may include a plurality of particle-containing layers. For example, the temporary support (1) may include a first particle-containing layer, a base material, and a second particle-containing layer in this order in the stacking direction from the temporary support toward the photosensitive resin layer.
[0054] Examples of the substrate include a glass substrate, a resin film, and paper. The substrate is preferably a resin film, more preferably a polyethylene terephthalate (PET) film, and particularly preferably a biaxially stretched PET film. Examples of the resin film include the resin films described above. Examples of the method for producing the resin film include an extrusion molding method.
[0055] Examples of the particles in the particle-containing layer include inorganic particles and organic particles. Examples of the inorganic particles include particles containing an inorganic oxide. Examples of the inorganic oxide include silicon oxide (silica), titanium oxide (titania), zirconium oxide (zirconia), magnesium oxide (magnesia), and aluminum oxide (alumina). Examples of the organic particles include particles containing a polymer. Examples of the polymer include acrylic resin, polyester, polyurethane, polycarbonate, polyolefin, and polystyrene. From the viewpoint of the wear resistance of the particles, the particles are preferably inorganic particles, more preferably particles containing an inorganic oxide, further preferably particles containing at least one selected from the group consisting of silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, and aluminum oxide, and particularly preferably particles containing silicon oxide.
[0056] From the viewpoint of reducing pinholes, the average particle diameter of the particles in the particle-containing layer is preferably 2 μm or less, more preferably 1 μm or less. From the viewpoint of transparency (haze), the average particle diameter of the particles in the particle-containing layer is preferably 300 nm or less, more preferably 100 nm or less, and particularly preferably 80 nm or less. From the viewpoint of transportability, the average particle diameter of the particles in the particle-containing layer is preferably 5 nm or more, more preferably 20 nm or more, and particularly preferably 40 nm or more. In the present disclosure, the average particle diameter of the particles in the particle-containing layer is measured by the following method. The particle diameters of 10 particles are measured using a transmission electron microscope (TEM). Here, the "particle diameter" is the maximum value of the straight line connecting two points on the contour line of the particle. The arithmetic average of the measured values is adopted as the average particle diameter of the particles.
[0057] The shape of the particles in the particle-containing layer is not limited. Examples of the shape of the particles in a plan view include circular, elliptical, polygonal, and irregular.
[0058] The particle-containing layer may contain a binder. Examples of the binder include polymers. Examples of the polymers include acrylic resins, polyurethanes, polyolefins, styrene-butadiene polymers, polyesters, polyvinyl chloride, and polyvinylidene chloride.
[0059] The thickness of the particle-containing layer is not limited. From the viewpoint of the ease of forming protrusions by the added particles, the thickness of the particle-containing layer (excluding particles exposed on the surface of the particle-containing layer; the same applies hereinafter in this paragraph) is preferably 3 μm or less, more preferably 2 μm or less. Furthermore, from the viewpoint of uniformly distributing the particles, the thickness of the particle-containing layer is preferably 5 nm or more, more preferably 20 nm or more. The thickness of the particle-containing layer is measured by a method similar to the method for measuring the thickness of the temporary support.
[0060] The method for producing the particle-containing layer is not limited. The particle-containing layer is formed, for example, by applying a composition for forming a particle-containing layer on a substrate and drying the applied composition for forming a particle-containing layer as necessary. The composition for forming a particle-containing layer is a raw material for forming a particle-containing layer. In the above method, the composition for forming a particle-containing layer may be applied on an unstretched film, a uniaxially stretched film, or a biaxially stretched film. The unstretched film or the uniaxially stretched film to which the composition for forming a particle-containing layer is applied may be further stretched. The particle-containing layer may be formed together with the substrate by, for example, a co-extrusion method.
[0061] The film used as the temporary support (1) is preferably free from deformations (eg wrinkles), scratches and defects.
[0062] From the viewpoint of pattern formability during pattern exposure through the temporary support and the transparency of the temporary support, it is preferable that the number of fine particles, foreign matter, defects and precipitates contained in the temporary support (1) is small. The number of fine particles, foreign matter and defects having a diameter of 2 μm or more is 50 / 10 mm. 2 It is preferable that the number of pieces is less than 10 pieces / 10 mm. 2 More preferably, 3 pieces / 10 mm or less. 2 More preferably, 0 pieces / 10 mm or less. 2 It is particularly preferred that:
[0063] Preferred embodiments of the temporary support (1) are described, for example, in paragraphs 0017 to 0018 of JP 2014-85643 A, paragraphs 0019 to 0026 of JP 2016-27363 A, paragraphs 0041 to 0057 of WO 2012 / 081680 A, paragraphs 0029 to 0040 of WO 2018 / 179370 A, and paragraphs 0012 to 0032 of JP 2019-101405 A. The contents of these publications are incorporated herein by reference.
[0064] Examples of the temporary support (1) include a biaxially oriented polyethylene terephthalate film having a thickness of 16 μm, a biaxially oriented polyethylene terephthalate film having a thickness of 12 μm, and a biaxially oriented polyethylene terephthalate film having a thickness of 9 μm.
[0065] <Temporary Support in the Photosensitive Transfer Material According to the Second Embodiment of the Present Disclosure> Hereinafter, the temporary support in the photosensitive transfer material according to the second embodiment of the present disclosure (hereinafter, also referred to as temporary support (2)) will be described. In the photosensitive transfer material according to the second embodiment of the present disclosure, the temporary support is a polyester film consisting of two or more layers, and at least one of the surface layers does not contain a filler. Here, the term "filler" in the present disclosure refers to an inorganic material that is added to fill gaps between polyester resin particles in the surface layer and has a particle size of 2.0 μm or more. Examples of the inorganic material that is the filler include the inorganic materials (preferably inorganic oxides) described above. The presence or absence and number of fillers are confirmed by the method described below, but in the particle measurement method described above, the fillers may be measured as part of the particles. "The surface layer does not contain filler" means that when the surface layer is observed with a scanning electron microscope (SEM) and a transmission electron microscope (TEM) and 10 fields of view are confirmed at a magnification of 5,000 times, the average number of fillers present is 0.5 pieces / mm 2 This means that the average number of fillers present is 0.5 / mm or less when confirmed by the above method. 2 If it is below this, it is considered that the "surface layer does not contain a filler."
[0066] The above observation method will now be described in more detail. The polyester resin is removed from the polyester film, which is the surface layer of the temporary support, by a plasma low-temperature ashing process, leaving the inorganic filler exposed. The processing conditions are selected so that the polyester resin is ashed but the filler is not damaged as much as possible. The processed sample is observed at a magnification of 5000 times using a scanning electron microscope (SEM, for example, Hitachi, Ltd. S-4000 type), and the particle image is imported into an image analyzer (Nireco Corporation LUZEX_AP) to confirm the presence or absence of filler and the number of particles. If the filler is significantly damaged by the plasma low-temperature ashing treatment method, the cross section of the temporary support is observed at 5,000x magnification using a transmission electron microscope (TEM, for example, Hitachi, Ltd. H-600 model) to confirm the presence or absence of filler and the number of fillers. When observed with SEM and TEM, the average number of fillers present was 0.5 pieces / mm when 10 fields of view were confirmed at a magnification of 5,000 times. 2 If it is below this value, it is determined that the surface layer of the object to be observed does not contain particles.
[0067] If the temporary support (2) is a polyester film consisting of two layers, one of the two layers is the surface layer on the first surface side (i.e., the layer arranged as the outermost layer on the first surface side), and the other layer is the surface layer on the second surface side (i.e., the layer arranged as the outermost layer on the second surface side). If the temporary support (2) is a polyester film consisting of three or more layers, it is composed of the surface layer on the first surface side (i.e., the layer arranged as the outermost layer on the first surface side), the surface layer on the second surface side (i.e., the layer arranged as the outermost layer on the second surface side), and one or more intermediate layers sandwiched between these two surface layers. The temporary support (2) has two surface layers, at least one of which does not contain a filler.
[0068] From the viewpoint of reducing pinholes, it is preferable that the surface layer on the photosensitive resin layer side of the temporary support (2) (that is, the surface layer on the second surface side) does not contain a filler.
[0069] From the viewpoint of reducing pinholes, the limit resolution of the photosensitive resin layer is defined as X μm, and the reference diameter of a particle is defined as Y μm expressed by the formula (1): Y = 0.75 × X. In this case, the number of particles having a diameter of Y μm or more on the temporary support (2) is 15 particles / cm. 2 Preferably less than 12 pieces / cm 2 More preferably, 9 particles / cm or less. 2 More preferably, the number is 7 / cm or less. 2 The lower limit of the number of particles having a diameter of Y μm or more in the temporary support (2) is not limited, and is particularly preferably 0 particles / cm. 2 Or 0 pieces / cm 2 It may be super.
[0070] From the viewpoint of transportability, the surface of the temporary support (2) opposite to the photosensitive resin layer (ie, the first surface) preferably has an arithmetic mean roughness Ra of 1 nm to 50 nm, more preferably 1 nm to 40 nm. The arithmetic mean roughness Ra of the surface of the temporary support (2) opposite to the photosensitive resin layer (i.e., the first surface) is measured by a method in accordance with JIS B 0601: 1994. Specifically, it can be measured by the same method as the arithmetic mean roughness Ra of the surface of the protective film described below.
[0071] The polyester film consisting of two or more layers constituting the temporary support (2) may be any film whose resin is mainly composed of polyester resin. Note that "the resin which constitutes the film is mainly composed of polyester resin" means that at least 70 mol % of the resin which constitutes the film is polyester resin.
[0072] The polyester resin constituting the polyester film is obtained by polymerization of monomers having dicarboxylic acid, diol, and their ester-forming derivatives as constituent components. Specific examples of the polyester resin constituting the film include polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polybutylene naphthalate, polyhexamethylene terephthalate, polyhexamethylene naphthalate, and copolymers thereof, with polyethylene terephthalate being particularly preferred.
[0073] As the dicarboxylic acid component (including dicarboxylic acid and its ester-forming derivative) which is a monomer for obtaining the polyester resin, it is preferable to use an aromatic dicarboxylic acid. Examples of aromatic dicarboxylic acids include terephthalic acid, 2,6-naphthalenedicarboxylic acid, and isophthalic acid, with terephthalic acid being particularly preferred. The dicarboxylic acid component may be used alone or in combination of two or more kinds. For example, two or more kinds of aromatic dicarboxylic acids may be used in combination, or an aromatic dicarboxylic acid and an aliphatic dicarboxylic acid may be used in combination.
[0074] Examples of the diol component (including diol and its ester-forming derivative) that is a monomer for obtaining polyester include ethylene glycol, 1,2-propanediol, 1,3-propanediol, neopentyl glycol, etc., with ethylene glycol being particularly preferred. The diol component may be used alone or in combination of two or more kinds.
[0075] The polyester resin constituting the polyester film can be produced by a conventionally known method. For example, a method of directly esterifying a dicarboxylic acid component with a diol component, and then heating the product of this reaction under reduced pressure to remove excess diol component while polycondensing, a method of using a dialkyl ester of a dicarboxylic acid as the dicarboxylic acid component, and then esterifying the diol component with this, and then polycondensing in the same manner as above, and the like can be mentioned. In this case, conventionally known alkali metals, alkaline earth metals, manganese, cobalt, zinc, antimony, germanium, titanium compounds, etc. can also be used as a reaction catalyst as necessary.
[0076] The intrinsic viscosity of the polyester resin constituting the polyester film is preferably from 0.5 dl / g to 0.8 dl / g, and more preferably from 0.55 dl / g to 0.70 dl / g.
[0077] The surface layer of the temporary support (2) that does not contain particles preferably has a phase-separated structure. That is, the surface layer preferably does not contain particles and has a phase-separated structure (specifically, it may be a sea-island structure). Although the surface layer does not contain particles, the surface layer has a phase-separated structure (for example, a sea-island structure), and thus surface irregularities resulting from the phase-separated structure are formed. Specifically, when a film having a surface layer with a phase-separated structure is biaxially stretched, for example, regions that are easily stretched and regions that are difficult to stretch are generated due to the phase-separated structure, and this stretching unevenness can form minute surface irregularities. In order to form a phase-separated structure in the surface layer as described above, the surface layer preferably contains a polyester resin having an alicyclic structure. That is, the surface layer contains a main polyester resin (e.g., a polyester resin having an aromatic ring structure) and a polyester resin having an alicyclic structure with a different compatibility from that of the main polyester resin, thereby forming a phase-separated structure (e.g., a sea-island structure).
[0078] The alicyclic structure in the polyester resin having the alicyclic structure is preferably a cyclopropane ring, a cyclobutane ring, a cyclopentane ring, or a cyclohexane ring, and is particularly preferably a cyclohexane ring. The polyester resin having the alicyclic structure can be obtained, for example, by carrying out a polycondensation reaction using dimethyl terephthalate as a dicarboxylic acid component and 1,3-cyclopropanediol, 1,3-cyclobutanediol, 1,3-cyclopentanediol, 1,4-cyclohexanedimethanol as a diol component in the presence of 200 ppm of butyltin tris(2-ethylhexanoate).
[0079] The content of the polyester resin having an alicyclic structure is preferably 3% by mass to 10% by mass based on the total mass of the surface layer, from the viewpoints of formability of surface irregularities and occurrence of coating defects of the composition for forming a photosensitive resin layer.
[0080] The temporary support (2) preferably contains, in the surface layer, a polyester resin having an alicyclic structure and a copolymerized polyethylene terephthalate having isophthalic acid as a copolymerization component. Here, the copolymerized polyethylene terephthalate having isophthalic acid as a copolymerization component refers to a polyester resin in which the diol component contained in the largest amount is ethylene glycol and the dicarboxylic acid component contained in the largest amount is terephthalic acid, and the polyester resin contains isophthalic acid as a dicarboxylic acid component. The copolymerization rate of isophthalic acid is preferably in the range of 0.1 mol% to 49 mol%, and more preferably 0.5 mol% to 40 mol%, based on the total dicarboxylic acid components. It is preferable to contain the copolymerized polyethylene terephthalate having an isophthalic acid component as a copolymerization component in the surface layer in terms of film formability, and is preferable in terms of facilitating the formation of surface irregularities due to the difference in stretchability with the polyester resin having an alicyclic structure.
[0081] The content of copolymerized polyethylene terephthalate in which isophthalic acid is a copolymerization component is not particularly limited, but is preferably 10% by mass to 20% by mass with respect to the total mass constituting the surface layer.
[0082] From the viewpoint of reducing pinholes, the thickness of the surface layer is preferably 0.5 μm to 2.5 μm, and more preferably 0.6 μm to 2.0 μm.
[0083] From the viewpoint of reducing pinholes, the thickness of the temporary support (2) is preferably 50 μm or less, more preferably 40 μm or less. The lower limit of the thickness of the temporary support is, for example, 5 μm or more.
[0084] (Layer composition) In the temporary support (2), the layer structure of the polyester film consisting of two layers can be A layer (surface layer) / B layer (surface layer), and the layer structure of the polyester film consisting of three layers can be A layer / B layer (intermediate layer) / A layer, or A layer / B layer (intermediate layer) / C layer (surface layer). The polyester film consisting of four or more layers can be one in which the intermediate layer has a laminated structure. In addition, when the above-mentioned A layer is a surface layer that does not contain particles, the B layer (surface layer), the B layer (intermediate layer), and the C layer (surface layer) may each be a polyester film, and may contain particles within a range that does not impair the purpose of the present disclosure, but may also be a layer (polyester film) that does not contain particles like the A layer. When the above-mentioned B layer (surface layer), the B layer (intermediate layer), or the C layer (surface layer) is a layer that contains particles, the particles contained therein may be organic particles or inorganic particles. Examples of organic particles include particles of polyimide resins, olefin or modified olefin resins, crosslinked polystyrene resins, silicone resins, and the like. Examples of inorganic particles include particles of silicon oxide, calcium carbonate, agglomerated alumina, aluminum silicate, mica, clay, talc, barium sulfate, and the like.
[0085] The above-mentioned particles are preferably those whose particle surface is modified with a surfactant or the like to improve the affinity with polyester resin. Also, particles whose particle shape is close to spherical and whose refractive index difference with polyester resin is small are preferred, for example, colloidal silica and organic particles are mentioned, and silicone resin particles and crosslinked polystyrene resin particles are particularly preferred. Among them, crosslinked polystyrene resin particles made of styrene-divinylbenzene copolymer prepared by emulsion polymerization are preferred because they have a particle shape close to a perfect sphere, have a uniform particle size distribution, and can form uniform protrusions.
[0086] A preferred embodiment of the temporary support (2) is a polyester film consisting of three or more layers, both surface layers of which do not contain particles and contain a polyester resin having an alicyclic structure, a thickness of 0.5 μm to 2.5 μm, and an arithmetic mean roughness Ra of the first surface of which is 1 nm to 50 nm.
[0087] The method for producing the temporary support (2) will be described below. The polyester film consisting of two or more layers, which is the temporary support (2), may be produced by melt film formation using a co-extrusion method. When obtaining a layer containing particles (polyester film), for example, the particles are dispersed in ethylene glycol, which is a diol component, to form a slurry, and then, for example, after performing high-precision filtration of coarse particles, the ethylene glycol slurry is added at any stage before the completion of polyester polymerization. Here, when adding particles, for example, the aqueous sol or alcohol sol obtained during the synthesis of the particles may be added as it is without drying. Alternatively, a method may be used in which the aqueous slurry of particles is mixed with polyester pellets, and then the mixture is fed to a vent-type twin-screw kneading extruder to incorporate the particles into the polyester film.
[0088] Pellets containing particles and pellets not containing particles prepared for each layer are used, and if necessary, the pellets containing particles and the pellets not containing particles are mixed and then fed to a known melt lamination extruder. As the extruder, a single-screw or twin-screw extruder can be used. In addition, in order to omit the drying process of the pellets, a vent-type extruder equipped with a vacuum line can also be used. In addition, for the formation of layer B, which has the largest extrusion amount, a so-called tandem extruder can be used, in which the function of melting the pellets and the function of keeping the molten pellets at a constant temperature are shared between the extruders.
[0089] The melt extruded from the extruder is filtered through a filter. For example, a high-precision filter capable of collecting 95% or more of foreign matter having a diameter of 5 μm or more can be used. Then, the material is extruded into a sheet from a slit die and cooled and solidified on a casting roll to produce an unstretched film. That is, the material is laminated using a plurality of extruders and a plurality of manifolds or merging blocks (e.g., a merging block having a rectangular merging portion), a sheet is extruded from a die, and the unstretched film is produced by cooling with a casting roll. In this case, it is preferable to install a static mixer and a gear pump in the flow path of the melt.
[0090] The temporary support (2) is preferably a biaxially stretched film. The stretching method may be simultaneous biaxial stretching or sequential biaxial stretching. In the case of sequential stretching, the stretching temperature in the first longitudinal stretching is desirably 90° C. to 130° C., more desirably 100° C. to 125° C., from the viewpoints of preventing breakage of the film and heat damage. Moreover, from the viewpoints of preventing stretching unevenness and scratches, it is preferable to perform the stretching in two or more stages.
[0091] From the viewpoint of suppressing stretching unevenness and suppressing breakage of the film, the stretching ratio is desirably 3 to 4.5 times (preferably 3.5 to 4.3 times) in the longitudinal direction and 3.2 to 5 times (preferably 4.0 to 4.6 times) in the transverse direction. From the viewpoint of obtaining the desired characteristics such as heat shrinkage after stretching, it is desirably heat-fixed at 200°C to 230°C (preferably 210°C to 230°C) for 0.5 to 20 seconds (preferably 1 to 15 seconds). Furthermore, after heat solidification, it is preferable to perform a relaxation treatment of 0.1% to 7.0% in the longitudinal and / or transverse directions.
[0092] Hereinafter, unless otherwise specified, when the term "temporary support" is used, it refers to both the above-mentioned temporary support (1) and temporary support (2).
[0093] <<Photosensitive resin layer>> The photosensitive transfer material according to the present disclosure includes a photosensitive resin layer. The photosensitive resin layer is preferably a negative photosensitive resin layer in which the solubility of the exposed portion in a developer is reduced by exposure, and the non-exposed portion is removed by development. However, the photosensitive resin layer is not limited to a negative photosensitive resin layer. The photosensitive resin layer may be a positive photosensitive resin layer in which the solubility of the exposed portion in a developer is improved by exposure, and the exposed portion is removed by development.
[0094] The photosensitive resin layer preferably contains a polymer A, a polymerizable compound B, and a photopolymerization initiator. The photosensitive resin layer preferably contains 10% by mass to 90% by mass of the polymer A, 5% by mass to 70% by mass of the polymerizable compound B, and 0.01% by mass to 20% by mass of the photopolymerization initiator, based on the total solid content mass of the photosensitive resin layer. The components of the photosensitive resin layer will be described below.
[0095] (Polymer A) Examples of the polymer A include acrylic resin, styrene-acrylic copolymer, polyurethane resin, polyvinyl alcohol, polyvinyl formal, polyamide, polyester, polyamide resin, epoxy resin, polyacetal, polyhydroxystyrene, polyimide resin, polybenzoxazole, polysiloxane, polyethyleneimine, polyallylamine, and polyalkylene glycol. The polymer A is preferably an alkali-soluble polymer compound. The alkali-soluble polymer compound includes polymer compounds that are easily soluble in alkaline substances. In the present disclosure, "alkali-soluble" means a property in which the solubility in an aqueous solution (100 g) containing 1% by mass of sodium carbonate at 22°C is 0.1 g or more.
[0096] From the viewpoint of more excellent resolution by suppressing swelling of the photosensitive resin layer by the developer, the acid value of the polymer A is preferably 220 mgKOH / g or less, more preferably less than 200 mgKOH / g, and particularly preferably less than 190 mgKOH / g. The lower limit of the acid value of the polymer A is not limited. From the viewpoint of more excellent developability, the acid value of the polymer A is preferably 60 mgKOH / g or more, more preferably 120 mgKOH / g or more, even more preferably 150 mgKOH / g or more, and particularly preferably 170 mgKOH / g or more. The acid value of the polymer A may be adjusted by the type of structural unit constituting the polymer A and the content of the structural unit containing an acid group.
[0097] In this disclosure, the term "acid value" refers to the mass (mg) of potassium hydroxide required to neutralize 1 g of a sample. The unit of acid value is mgKOH / g. The acid value can be calculated, for example, from the average content of acid groups in a compound.
[0098] The weight average molecular weight of the polymer A is preferably 5,000 to 500,000. The weight average molecular weight of 500,000 or less is preferable from the viewpoint of improving resolution and developability. The weight average molecular weight of the polymer A is more preferably 100,000 or less, further preferably 80,000 or less, and particularly preferably 70,000 or less. On the other hand, the weight average molecular weight of 5,000 or more is preferable from the viewpoint of controlling the properties of the development aggregate and the properties of the unexposed film (for example, edge fuse property and cut chip property). The weight average molecular weight of the polymer A is more preferably 10,000 or more, further preferably 20,000 or more, and particularly preferably 30,000 or more. The edge fuse property refers to the degree of the tendency of the photosensitive resin layer to protrude from the end surface of the roll in the photosensitive transfer material wound into a roll. The cut chip property refers to the degree of the tendency of the chip to fly off when the unexposed film is cut with a cutter. For example, if the generated chips are transferred to a mask used for exposure, it will cause defective products. The dispersity of polymer A is preferably 1.0 to 6.0, more preferably 1.0 to 5.0, further preferably 1.0 to 4.0, and particularly preferably 1.0 to 3.0. In the present disclosure, the dispersity is the ratio of the weight average molecular weight to the number average molecular weight (weight average molecular weight / number average molecular weight). In the present disclosure, the weight average molecular weight and the number average molecular weight are values measured using gel permeation chromatography.
[0099] The glass transition temperature (Tg) of the polymer A is preferably 30°C or more and 135°C or less. When the Tg of the polymer A is 135°C or less, it is possible to suppress line width thickening or deterioration of resolution when the focal position is shifted during exposure. The Tg of the polymer A is more preferably 130°C or less, further preferably 120°C or less, and particularly preferably 110°C or less. When the Tg of the polymer A is 30°C or more, it is possible to improve edge fuse resistance. The Tg of the polymer A is more preferably 40°C or more, further preferably 50°C or more, particularly preferably 60°C or more, and most preferably 70°C or more.
[0100] From the viewpoint of suppressing line width thickening or deterioration of resolution when the focal position is shifted during exposure, the polymer A preferably contains a structural unit having an aromatic hydrocarbon group. The polymer A may contain one or more structural units having an aromatic hydrocarbon group. Examples of the aromatic hydrocarbon group include a substituted or unsubstituted phenyl group and a substituted or unsubstituted aralkyl group. The content of the structural unit having an aromatic hydrocarbon group in the polymer A is preferably 20% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, particularly preferably 45% by mass or more, and most preferably 50% by mass or more, based on the total mass of the polymer A. The upper limit of the content of the structural unit having an aromatic hydrocarbon group in the polymer A is not limited. The content of the structural unit having an aromatic hydrocarbon group in the polymer A is preferably 95% by mass or less, more preferably 85% by mass or less. When the photosensitive resin layer contains a plurality of types of the polymer A, the content of the structural unit having an aromatic hydrocarbon group is determined as a weight average value.
[0101] The structural unit having an aromatic hydrocarbon group is introduced using a monomer having an aromatic hydrocarbon group. Examples of the monomer having an aromatic hydrocarbon group include a monomer having an aralkyl group, styrene, and polymerizable styrene derivatives (e.g., methylstyrene, vinyltoluene, tert-butoxystyrene, acetoxystyrene, 4-vinylbenzoic acid, styrene dimer, and styrene trimer). Among the above, a monomer having an aralkyl group or styrene is preferred. When the structural unit having an aromatic hydrocarbon group in the polymer A is a structural unit derived from styrene, the content of the structural unit derived from styrene is preferably 20% by mass to 80% by mass, more preferably 25% by mass to 70% by mass, and particularly preferably 30% by mass to 60% by mass, based on the total mass of the polymer A.
[0102] Examples of the aralkyl group include a substituted or unsubstituted phenylalkyl group (excluding a benzyl group) and a substituted or unsubstituted benzyl group, with a substituted or unsubstituted benzyl group being preferred.
[0103] An example of a monomer having a phenylalkyl group is phenylethyl (meth)acrylate.
[0104] Examples of the monomer having a benzyl group include (meth)acrylates having a benzyl group (e.g., benzyl (meth)acrylate and chlorobenzyl (meth)acrylate) and vinyl monomers having a benzyl group (e.g., vinylbenzyl chloride and vinylbenzyl alcohol). Among the above, benzyl (meth)acrylate is preferred. When the structural unit having an aromatic hydrocarbon group in the polymer A is a structural unit derived from benzyl (meth)acrylate, the content of the structural unit derived from benzyl (meth)acrylate is preferably 50% by mass to 95% by mass, more preferably 60% by mass to 90% by mass, further preferably 70% by mass to 90% by mass, and particularly preferably 75% by mass to 90% by mass, based on the total mass of the polymer A.
[0105] The polymer A containing a structural unit having an aromatic hydrocarbon group preferably contains a structural unit having an aromatic hydrocarbon group, and at least one type selected from the group consisting of a structural unit derived from a first monomer and a structural unit derived from a second monomer.
[0106] Polymer A which does not contain a structural unit having an aromatic hydrocarbon group preferably contains a structural unit derived from a first monomer, and more preferably contains a structural unit derived from a first monomer and a structural unit derived from a second monomer.
[0107] The first monomer is a monomer having a carboxyl group in the molecule. Examples of the first monomer include (meth)acrylic acid, fumaric acid, cinnamic acid, crotonic acid, itaconic acid, 4-vinylbenzoic acid, maleic anhydride, and maleic acid half ester. Among the above, (meth)acrylic acid is preferable. Polymer A may contain a structural unit derived from one or more first monomers. The content of the first monomer in Polymer A is preferably 5% by mass to 50% by mass, more preferably 10% by mass to 45% by mass, and particularly preferably 15% by mass to 35% by mass, based on the total mass of Polymer A.
[0108] The second monomer is a monomer that is non-acidic and has at least one polymerizable unsaturated group in the molecule. Examples of the second monomer include (meth)acrylates (e.g., methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, cyclohexyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate), esters of vinyl alcohol (e.g., vinyl acetate), and (meth)acrylonitrile. Among the above, methyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and n-butyl (meth)acrylate are preferred, and methyl (meth)acrylate is particularly preferred. The content of the second monomer in polymer A is preferably 5% by mass to 60% by mass, more preferably 15% by mass to 50% by mass, and particularly preferably 20% by mass to 45% by mass, based on the total mass of polymer A.
[0109] From the viewpoint of suppressing line width thickening or deterioration of resolution when the focal position is shifted during exposure, it is preferable that the polymer A contains at least one selected from the group consisting of a structural unit derived from a monomer having an aralkyl group and a structural unit derived from styrene.Preferable specific examples of the polymer A as described above include a copolymer of methacrylic acid, benzyl methacrylate, and styrene, and a copolymer of methacrylic acid, methyl methacrylate, benzyl methacrylate, and styrene.
[0110] In one embodiment, polymer A is preferably a polymer containing 25% to 40% by mass of structural units having an aromatic hydrocarbon group, 20% to 35% by mass of structural units derived from a first monomer, and 30% to 45% by mass of structural units derived from a second monomer. In another embodiment, polymer A is preferably a polymer containing 70% to 90% by mass of structural units derived from a monomer having an aromatic hydrocarbon group, and 10% to 25% by mass of structural units derived from the first monomer.
[0111] The polymer A may have a branched structure or an alicyclic structure in the side chain. For example, a monomer containing a group having a branched structure in the side chain or a monomer containing a group having an alicyclic structure in the side chain can be used to introduce a branched structure or an alicyclic structure into the side chain of the polymer (A). The alicyclic structure in the side chain of the polymer A may be monocyclic or polycyclic. Furthermore, the polymer A may have a linear structure in the side chain.
[0112] Examples of monomers containing a group having a branched structure in the side chain include isopropyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, isoamyl (meth)acrylate, tert-amyl (meth)acrylate, sec-amyl (meth)acrylate, 2-octyl (meth)acrylate, 3-octyl (meth)acrylate, and tert-octyl (meth)acrylate. Among the above, isopropyl (meth)acrylate, isobutyl (meth)acrylate, and tert-butyl methacrylate are preferred, and isopropyl methacrylate or tert-butyl methacrylate are more preferred.
[0113] Specific examples of the monomer containing a group having an alicyclic structure in the side chain include a monomer having a monocyclic aliphatic hydrocarbon group and a monomer having a polycyclic aliphatic hydrocarbon group. Specific examples of the monomer containing a group having an alicyclic structure in the side chain include a (meth)acrylate having an alicyclic hydrocarbon group having 5 to 20 carbon atoms. Examples of monomers containing a group having an alicyclic structure in the side chain include (bicyclo[2.2.1]heptyl-2)(meth)acrylate, 1-adamantyl (meth)acrylate, 2-adamantyl (meth)acrylate, 3-methyl-1-adamantyl (meth)acrylate, 3,5-dimethyl-1-adamantyl (meth)acrylate, 3-ethyladamantyl (meth)acrylate, 3-methyl-5-ethyl-1-adamantyl (meth)acrylate, 3,5,8-triethyl-1-adamantyl (meth)acrylate, 3,5-dimethyl-8-ethyl-1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, 2-ethyl-2-adamantyl (meth)acrylate, Examples of the acrylates include 3-hydroxy-1-adamantyl (meth)acrylate, octahydro-4,7-menthanoinden-5-yl (meth)acrylate, octahydro-4,7-menthanoinden-1-ylmethyl (meth)acrylate, 1-menthyl (meth)acrylate, tricyclodecane (meth)acrylate, 3-hydroxy-2,6,6-trimethyl-bicyclo[3.1.1]heptyl (meth)acrylate, 3,7,7-trimethyl-4-hydroxy-bicyclo[4.1.0]heptyl (meth)acrylate, (nor)bornyl (meth)acrylate, isobornyl (meth)acrylate, fenchyl (meth)acrylate, 2,2,5-trimethylcyclohexyl (meth)acrylate, and cyclohexyl (meth)acrylate.Among the above, cyclohexyl (meth)acrylate, (nor)bornyl (meth)acrylate, isobornyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-adamantyl (meth)acrylate, fenchyl (meth)acrylate, 1-menthyl (meth)acrylate and tricyclodecane (meth)acrylate are preferred, and cyclohexyl (meth)acrylate, (nor)bornyl (meth)acrylate, isobornyl (meth)acrylate, 2-adamantyl (meth)acrylate and tricyclodecane (meth)acrylate are more preferred.
[0114] The photosensitive resin layer may contain one or more types of polymer A. When two or more types of polymer A are used, it is preferable to use two types of polymer A containing a structural unit having an aromatic hydrocarbon group, or to use a mixture of a polymer A containing a structural unit having an aromatic hydrocarbon group and a polymer A not containing a structural unit having an aromatic hydrocarbon group. In the latter case, the proportion of the polymer A containing a structural unit having an aromatic hydrocarbon group is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more, based on the total mass of the polymer A.
[0115] The content of polymer A in the photosensitive resin layer is preferably 10% by mass to 90% by mass, more preferably 30% by mass to 70% by mass, and particularly preferably 40% by mass to 60% by mass, based on the total mass of the photosensitive resin layer. It is preferable to set the content of polymer A to 90% by mass or less from the viewpoint of controlling the development time. It is preferable to set the content of polymer A to 10% by mass or more from the viewpoint of improving edge fuse resistance.
[0116] The synthesis of polymer A is preferably carried out by adding an appropriate amount of a radical polymerization initiator (e.g., benzoyl peroxide and azoisobutyronitrile) to a solution obtained by diluting the monomers with a solvent (e.g., acetone, methyl ethyl ketone and isopropanol), and heating and stirring the solution. In some cases, the synthesis is carried out while dropping a part of the mixture into the reaction solution. In some cases, the solvent is further added after the reaction is completed to adjust the concentration to the desired level. As a synthesis method, bulk polymerization, suspension polymerization or emulsion polymerization may be used in addition to solution polymerization.
[0117] (Polymerizable compound B) The polymerizable compound B is a compound having a polymerizable group. In the present disclosure, the term "polymerizable compound" refers to a compound that is polymerized by the action of a polymerization initiator and is different from the polymer A described above.
[0118] The polymerizable group is not limited as long as it is a group involved in a polymerization reaction, and examples thereof include ethylenically unsaturated groups (e.g., vinyl groups, acryloyl groups, methacryloyl groups, styryl groups, and maleimide groups) and cationic polymerizable groups (e.g., epoxy groups and oxetane groups). The polymerizable group is preferably an ethylenically unsaturated group, and more preferably an acryloyl group or a methacryloyl group.
[0119] In terms of superior photosensitivity of the photosensitive resin layer, the polymerizable compound B is preferably a compound having at least one ethylenically unsaturated group (i.e., an ethylenically unsaturated compound), and more preferably a compound having two or more ethylenically unsaturated groups in one molecule (i.e., a polyfunctional ethylenically unsaturated compound). In terms of superior resolution and peelability, the number of ethylenically unsaturated groups contained in one molecule of the ethylenically unsaturated compound is preferably 6 or less, more preferably 3 or less, and particularly preferably 2 or less. The ethylenically unsaturated compound is preferably a (meth)acrylate compound having a (meth)acryloyl group.
[0120] In terms of a better balance between the photosensitivity, resolution, and peelability of the photosensitive resin layer, the photosensitive resin layer preferably contains a compound having two or three ethylenically unsaturated groups in one molecule (i.e., a bifunctional or trifunctional ethylenically unsaturated compound), and more preferably contains a compound having two ethylenically unsaturated groups in one molecule (i.e., a bifunctional ethylenically unsaturated compound). In terms of excellent peelability, the content of the bifunctional ethylenically unsaturated compound in the photosensitive resin layer is preferably 60% by mass or more, more preferably more than 70% by mass, and particularly preferably 90% by mass or more, based on the total mass of the polymerizable compound B. The upper limit of the content of the bifunctional ethylenically unsaturated compound is not limited. The content of the bifunctional ethylenically unsaturated compound in the photosensitive resin layer may be 100% by mass based on the total mass of the polymerizable compound B. That is, all of the polymerizable compound B contained in the photosensitive resin layer may be a bifunctional ethylenically unsaturated compound.
[0121] The photosensitive resin layer preferably contains a polymerizable compound B1 having an aromatic ring and two ethylenically unsaturated groups. The polymerizable compound B1 is a compound included in the above-mentioned polymerizable compounds B having two ethylenically unsaturated groups in one molecule (i.e., bifunctional ethylenically unsaturated compounds).
[0122] Examples of the aromatic ring include aromatic hydrocarbon rings (e.g., benzene ring, naphthalene ring, and anthracene ring), aromatic heterocycles (e.g., thiophene ring, furan ring, pyrrole ring, imidazole ring, triazole ring, and pyridine ring), and condensed rings thereof. The aromatic ring is preferably an aromatic hydrocarbon ring, and more preferably a benzene ring. The aromatic ring may have a substituent. The polymerizable compound B1 may have two or more aromatic rings.
[0123] The polymerizable compound B1 preferably has a bisphenol structure, since the resolution is improved by suppressing the swelling of the photosensitive resin layer by the developer. Examples of the bisphenol structure include a bisphenol A structure derived from bisphenol A (2,2-bis(4-hydroxyphenyl)propane), a bisphenol F structure derived from bisphenol F (2,2-bis(4-hydroxyphenyl)methane), and a bisphenol B structure derived from bisphenol B (2,2-bis(4-hydroxyphenyl)butane). The bisphenol structure is preferably a bisphenol A structure. Examples of the polymerizable compound B1 having a bisphenol structure include a compound having a bisphenol structure and two ethylenically unsaturated groups (preferably (meth)acryloyl groups) bonded to both ends of the bisphenol structure. Each ethylenically unsaturated group may be bonded directly to the end of the bisphenol structure, or may be bonded via one or more alkyleneoxy groups. The alkyleneoxy group is preferably an ethyleneoxy group or a propyleneoxy group, and more preferably an ethyleneoxy group. The number of alkyleneoxy groups added to the bisphenol structure is not limited. The number of alkyleneoxy groups added to the bisphenol structure is preferably 4 to 16 per molecule, more preferably 6 to 14. The polymerizable compound B1 having a bisphenol structure is described in paragraphs 0072 to 0080 of JP 2016-224162 A. The contents of the above publication are incorporated herein by reference.
[0124] The polymerizable compound B1 is preferably a bifunctional ethylenically unsaturated compound having a bisphenol A structure, and more preferably 2,2-bis(4-((meth)acryloxypolyalkoxy)phenyl)propane. Examples of 2,2-bis(4-((meth)acryloxypolyalkoxy)phenyl)propane include 2,2-bis(4-(methacryloxydiethoxy)phenyl)propane (FA-324M, Hitachi Chemical Co., Ltd.), 2,2-bis(4-(methacryloxyethoxypropoxy)phenyl)propane, 2,2-bis(4-(methacryloxypentaethoxy)phenyl)propane (BPE-500, Shin-Nakamura Chemical Co., Ltd.), 2,2-bis(4-(methacryloxydodecaethoxy)phenyl)propane (BPE-500, Shin-Nakamura Chemical Co., Ltd.), and 2,2-bis(4-(methacryloxydodecaethoxy)phenyl)propane (BPE-500, Shin-Nakamura Chemical Co., Ltd.). Examples of such bisphenol A diacrylates include 2,2-bis(4-(methacryloxypentadecaethoxy)phenyl)propane (FA-3200MY, Hitachi Chemical Co., Ltd.), 2,2-bis(4-(methacryloxypentadecaethoxy)phenyl)propane (BPE-1300, Shin-Nakamura Chemical Co., Ltd.), 2,2-bis(4-(methacryloxydiethoxy)phenyl)propane (BPE-200, Shin-Nakamura Chemical Co., Ltd.), and ethoxylated (10) bisphenol A diacrylate (NK Ester A-BPE-10, Shin-Nakamura Chemical Co., Ltd.).
[0125] The polymerizable compound B1 also includes, for example, a compound represented by the following formula (I).
[0126] [ka]
[0127] In formula (I), R1 and R2 each independently represent a hydrogen atom or a methyl group, A represents C2H4, B represents C3H6, n1 and n3 each independently represent an integer of 1 to 39, n1+n3 is an integer of 2 to 40, n2 and n4 each independently represent an integer of 0 to 29, n2+n4 is an integer of 0 to 30, and the arrangement of the repeating units of -(AO)- and -(BO)- may be random or block. In the case of block, -(AO)- may be on the bisphenyl group side, and -(BO)- may be on the bisphenyl group side. n1+n2+n3+n4 is preferably an integer of 2 to 20, more preferably an integer of 2 to 16, and particularly preferably an integer of 4 to 12. n2+n4 is preferably an integer of 0 to 10, more preferably an integer of 0 to 4, even more preferably an integer of 0 to 2, and particularly preferably 0.
[0128] The photosensitive resin layer may contain one or more polymerizable compounds B1.
[0129] The content of the polymerizable compound B1 in the photosensitive resin layer is preferably 10% by mass or more, more preferably 20% by mass or more, based on the total mass of the photosensitive resin layer, from the viewpoint of better resolution. The upper limit is not particularly limited, but is preferably 70% by mass or less, more preferably 60% by mass or less, from the viewpoint of transferability and edge fuse resistance.
[0130] From the viewpoint of better resolution, the ratio of the content of the polymerizable compound B1 to the content of the polymerizable compound B in the photosensitive resin layer is preferably 40% or more by mass, more preferably 50% or more by mass, even more preferably 55% or more by mass, and particularly preferably 60% or more by mass. The upper limit of the ratio of the content of the polymerizable compound B1 to the content of the polymerizable compound B in the photosensitive resin layer is not limited. From the viewpoint of peelability, the ratio of the content of the polymerizable compound B1 to the content of the polymerizable compound B in the photosensitive resin layer is preferably 99% or less by mass, more preferably 95% or less by mass, even more preferably 90% or less by mass, and particularly preferably 85% or less by mass.
[0131] The photosensitive resin layer may contain a polymerizable compound B other than the above-mentioned polymerizable compound B1. Examples of the polymerizable compound B other than the polymerizable compound B1 include a monofunctional ethylenically unsaturated compound (i.e., a compound having one ethylenically unsaturated group in one molecule), a bifunctional ethylenically unsaturated compound having no aromatic ring (i.e., a compound having no aromatic ring and having two ethylenically unsaturated groups in one molecule), and a trifunctional or higher ethylenically unsaturated compound (i.e., a compound having three or more ethylenically unsaturated groups in one molecule).
[0132] Examples of monofunctional ethylenically unsaturated compounds include ethyl (meth)acrylate, ethylhexyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, and phenoxyethyl (meth)acrylate.
[0133] Examples of the difunctional ethylenically unsaturated compound having no aromatic ring include alkylene glycol di(meth)acrylate, polyalkylene glycol di(meth)acrylate, urethane di(meth)acrylate, and trimethylolpropane diacrylate.
[0134] Examples of alkylene glycol di(meth)acrylates include tricyclodecane dimethanol diacrylate (A-DCP, Shin-Nakamura Chemical Co., Ltd.), tricyclodecane dimethanol dimethacrylate (DCP, Shin-Nakamura Chemical Co., Ltd.), 1,9-nonanediol diacrylate (A-NOD-N, Shin-Nakamura Chemical Co., Ltd.), 1,6-hexanediol diacrylate (A-HD-N, Shin-Nakamura Chemical Co., Ltd.), ethylene glycol dimethacrylate, 1,10-decanediol diacrylate, and neopentyl glycol di(meth)acrylate.
[0135] Examples of polyalkylene glycol di(meth)acrylates include polyethylene glycol di(meth)acrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, and polypropylene glycol di(meth)acrylate.
[0136] Examples of urethane di(meth)acrylate include propylene oxide modified urethane di(meth)acrylate, and ethylene oxide and propylene oxide modified urethane di(meth)acrylate. Examples of commercially available urethane di(meth)acrylate include 8UX-015A (Taisei Fine Chemical Co., Ltd.), UA-32P (Shin-Nakamura Chemical Co., Ltd.) and UA-1100H (Shin-Nakamura Chemical Co., Ltd.).
[0137] Examples of trifunctional or higher ethylenically unsaturated compounds include dipentaerythritol (tri / tetra / penta / hexa)(meth)acrylate, pentaerythritol (tri / tetra)(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, trimethylolethane tri(meth)acrylate, isocyanuric acid tri(meth)acrylate, glycerin tri(meth)acrylate, and alkylene oxide modified products thereof. Here, "(tri / tetra / penta / hexa)(meth)acrylate" is a concept that includes tri(meth)acrylate, tetra(meth)acrylate, penta(meth)acrylate, and hexa(meth)acrylate, and "(tri / tetra)(meth)acrylate" is a concept that includes tri(meth)acrylate and tetra(meth)acrylate.
[0138] Examples of alkylene oxide modified trifunctional or higher ethylenically unsaturated compounds include caprolactone modified (meth)acrylate compounds (e.g., KAYARAD DPCA-20 (Nippon Kayaku Co., Ltd.) and A-9300-1CL (Shin-Nakamura Chemical Co., Ltd.)), alkylene oxide modified (meth)acrylate compounds (KAYARAD RP-1040 (Nippon Kayaku Co., Ltd.), ATM-35E (Shin-Nakamura Chemical Co., Ltd.), A-9300 (Shin-Nakamura Chemical Co., Ltd.) and EBECRYL 135 (Daicel-Allnex Corporation)), ethoxylated glycerin triacrylate (e.g., A-GLY-9E (Shin-Nakamura Chemical Co., Ltd.)), ARONIX TO-2349 (Toagosei Co., Ltd.), ARONIX M-520 (Toagosei Co., Ltd.) and ARONIX M-510 (Toagosei Co., Ltd.).
[0139] From the viewpoint of resistance to processing solutions such as development, the photosensitive resin layer preferably contains a polymerizable compound B1 and a trifunctional or higher ethylenically unsaturated compound, and more preferably contains a polymerizable compound B1 and two or more trifunctional or higher ethylenically unsaturated compounds. The mass ratio of the polymerizable compound B1 to the trifunctional or higher ethylenically unsaturated compounds (total mass of the polymerizable compound B1:total mass of the trifunctional or higher ethylenically unsaturated compounds) is preferably 1:1 to 5:1, more preferably 1.2:1 to 4:1, and particularly preferably 1.5:1 to 3:1.
[0140] As the polymerizable compound B other than the polymerizable compound B1, a polymerizable compound having an acid group described in paragraphs 0025 to 0030 of JP-A No. 2004-239942 may be used.
[0141] The photosensitive resin layer may contain one or more polymerizable compounds B.
[0142] The content of polymerizable compound B in the photosensitive resin layer is preferably 10% by mass to 70% by mass, more preferably 20% by mass to 60% by mass, and particularly preferably 20% by mass to 50% by mass, relative to the total mass of the photosensitive resin layer.
[0143] The molecular weight of the polymerizable compound B is preferably from 200 to 3,000, more preferably from 280 to 2,200, and particularly preferably from 300 to 2,200. The molecular weight of the polymerizable compound B having a molecular weight distribution is represented by the weight average molecular weight (Mw).
[0144] The ratio Mm / Mb of the content Mm of the ethylenically unsaturated compound in the photosensitive resin layer to the content Mb of the polymer A is preferably 1.0 or less, more preferably 0.9 or less, and particularly preferably 0.5 to 0.9, from the viewpoints of resolution and linearity. The ethylenically unsaturated compound in the photosensitive resin layer preferably contains a (meth)acrylic compound, and more preferably contains a (meth)acrylate compound, from the viewpoints of curability and resolution. The ethylenically unsaturated compound in the photosensitive resin layer preferably contains a (meth)acrylic compound, and the content ratio of the acrylic compound to the total mass of the (meth)acrylic compound contained in the photosensitive resin layer is more preferably 60 mass% or less.
[0145] (Photopolymerization initiator) A photopolymerization initiator is a compound that initiates polymerization of a polymerizable compound upon exposure to actinic radiation (eg, ultraviolet light, visible light, and X-rays).
[0146] The type of photopolymerization initiator is not limited. The photopolymerization initiator according to the present disclosure includes known photopolymerization initiators. Examples of the photopolymerization initiator include a photoradical polymerization initiator and a photocationic polymerization initiator, and a photoradical polymerization initiator is preferred.
[0147] Examples of the photoradical polymerization initiator include a photopolymerization initiator having an oxime ester structure, a photopolymerization initiator having an α-aminoalkylphenone structure, a photopolymerization initiator having an α-hydroxyalkylphenone structure, a photopolymerization initiator having an acylphosphine oxide structure, and a photopolymerization initiator having an N-phenylglycine structure.
[0148] From the viewpoints of photosensitivity, visibility of exposed areas, visibility of non-exposed areas, and resolution, the photosensitive resin layer preferably contains at least one selected from the group consisting of 2,4,5-triarylimidazole dimers and derivatives thereof as a photoradical polymerization initiator. The two 2,4,5-triarylimidazole structures in the 2,4,5-triarylimidazole dimers and derivatives thereof may be the same or different. Examples of derivatives of 2,4,5-triarylimidazole dimers include 2-(o-chlorophenyl)-4,5-diphenylimidazole dimer, 2-(o-chlorophenyl)-4,5-di(methoxyphenyl)imidazole dimer, 2-(o-fluorophenyl)-4,5-diphenylimidazole dimer, 2-(o-methoxyphenyl)-4,5-diphenylimidazole dimer, and 2-(p-methoxyphenyl)-4,5-diphenylimidazole dimer.
[0149] As the photoradical polymerization initiator, for example, the polymerization initiators described in paragraphs 0031 to 0042 of JP-A No. 2011-95716 and paragraphs 0064 to 0081 of JP-A No. 2015-14783 may be used.
[0150] Examples of photoradical polymerization initiators include ethyl dimethylaminobenzoate (DBE, CAS No. 10287-53-3), benzoin methyl ether, and anisyl (p,p'-dimethoxybenzyl).
[0151] Commercially available photoradical polymerization initiators include, for example, TAZ-110 (trade name: Midori Chemical Co., Ltd.), benzophenone, TAZ-111 (trade name: Midori Chemical Co., Ltd.), 1-[4-(phenylthio)phenyl]-1,2-octanedione-2-(O-benzoyloxime) (trade name: IRGACURE OXE01, BASF), 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone-1-(O-acetyloxime) (trade name: IRGACURE OXE02, BASF), IRGACURE OXE03 (BASF), IRGACURE OXE04 (BASF), 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone (trade name: Omnirad 379EG, IGM Resins), BV), 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one (trade name: Omnirad 907, IGM Resins BV), 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2-methylpropan-1-one (trade name: Omnirad 127, IGM Resins BV), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone-1 (trade name: Omnirad 369, IGM Resins BV), 2-hydroxy-2-methyl-1-phenylpropan-1-one (trade name: Omnirad 1173, IGM Resins BV), 1-hydroxycyclohexyl phenyl ketone (trade name: Omnirad 184, IGM Resins BV), 2,2-dimethoxy-1,2-diphenylethan-1-one (trade name: Omnirad 651, IGM Resins BV), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (trade name: Omnirad TPO H, IGM Resins BV), bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (trade name: Omnirad 819, IGM Resins BVOxime ester photoinitiator (trade name: Lunar 6, DKSH Japan Co., Ltd.), 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetraphenylbisimidazole (also known as 2-(2-chlorophenyl)-4,5-diphenylimidazole dimer, trade name: B-CIM, Hampford Co., Ltd.), 2-(o-chlorophenyl)-4,5-diphenylimidazole dimer (trade name: BCTB, Tokyo Chemical Industry Co., Ltd.), 1-[4-(phenylthio)phenyl]-3-cyclopentylpropane-1,2-dione-2-(O-benzoyloxime) (trade name: TR-PBG-305 , Changzhou Strong Electronic New Materials Co., Ltd.), 1,2-propanedione, 3-cyclohexyl-1-[9-ethyl-6-(2-furanylcarbonyl)-9H-carbazol-3-yl]-, 2-(O-acetyloxime) (trade name: TR-PBG-326, Changzhou Strong Electronic New Materials Co., Ltd.) and 3-cyclohexyl-1-(6-(2-(benzoyloxyimino)hexanoyl)-9-ethyl-9H-carbazol-3-yl)-propane-1,2-dione-2-(O-benzoyloxime) (trade name: TR-PBG-391, Changzhou Strong Electronic New Materials Co., Ltd.).
[0152] A photocationic polymerization initiator (photoacid generator) is a compound that generates an acid when exposed to actinic rays. As the photocationic polymerization initiator, a compound that responds to actinic rays having a wavelength of 300 nm or more (preferably a wavelength of 300 nm to 450 nm) and generates an acid is preferable. In addition, a photocationic polymerization initiator that does not directly respond to actinic rays having a wavelength of 300 nm or more can be preferably used in combination with a sensitizer, so long as it is a compound that responds to actinic rays having a wavelength of 300 nm or more and generates an acid when used in combination with a sensitizer.
[0153] The photocationic polymerization initiator is preferably a photocationic polymerization initiator that generates an acid having a pKa of 4 or less, more preferably a photocationic polymerization initiator that generates an acid having a pKa of 3 or less, and particularly preferably a photocationic polymerization initiator that generates an acid having a pKa of 2 or less. There is no lower limit for the pKa. The pKa of the acid generated by the photocationic polymerization initiator is preferably -10.0 or more.
[0154] Examples of the photocationic polymerization initiator include ionic photocationic polymerization initiators and nonionic photocationic polymerization initiators. Examples of the ionic photocationic polymerization initiator include onium salt compounds (e.g., diaryliodonium salts and triarylsulfonium salts) and quaternary ammonium salts. Examples of the ionic photocationic polymerization initiator include the ionic photocationic polymerization initiators described in paragraphs 0114 to 0133 of JP-A-2014-85643. Examples of the nonionic photocationic polymerization initiator include trichloromethyl-s-triazines, diazomethane compounds, imide sulfonate compounds, and oxime sulfonate compounds. Examples of the trichloromethyl-s-triazines, diazomethane compounds, and imide sulfonate compounds include the compounds described in paragraphs 0083 to 0088 of JP-A-2011-221494. In addition, as the oxime sulfonate compound, the compounds described in paragraphs 0084 to 0088 of WO 2018 / 179640 may be used.
[0155] The photosensitive resin layer preferably contains a photoradical polymerization initiator, and more preferably contains at least one selected from the group consisting of 2,4,5-triarylimidazole dimers and derivatives thereof.
[0156] The photosensitive resin layer may contain one or more types of photopolymerization initiators.
[0157] The content of the photopolymerization initiator in the photosensitive resin layer is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and particularly preferably 1.0% by mass or more, based on the total mass of the photosensitive resin layer. There is no upper limit to the content of the photopolymerization initiator. The content of the photopolymerization initiator in the photosensitive resin layer is preferably 10% by mass or less, more preferably 5% by mass or less, based on the total mass of the photosensitive resin layer.
[0158] (dye) From the viewpoints of visibility of exposed areas, visibility of unexposed areas, and pattern visibility and resolution after development, the photosensitive resin layer preferably contains a dye (hereinafter sometimes referred to as "dye N") whose maximum absorption wavelength in the wavelength range of 400 nm to 780 nm during color development is 450 nm or more and whose maximum absorption wavelength changes with an acid, a base, or a radical. When the photosensitive resin layer contains dye N, adhesion to a layer adjacent to the photosensitive resin layer (for example, a temporary support) is improved, and resolution is improved.
[0159] In the present disclosure, the term "the maximum absorption wavelength changes due to an acid, a base, or a radical" used in relation to a dye includes (1) an embodiment in which a dye in a colored state is decolorized by an acid, a base, or a radical, (2) an embodiment in which a dye in a decolorized state is colored by an acid, a base, or a radical, and (3) an embodiment in which a dye in a colored state is changed to a colored state of another hue. For example, dye N may be a compound that changes from a decolorized state upon exposure to develop a color, or a compound that changes from a colored state upon exposure to decolorize. Dye N may be a dye whose colored or decolorized state changes due to the action of an acid, a base, or a radical generated in the photosensitive resin layer upon exposure. Dye N may be a dye whose colored or decolorized state changes due to a change in the state (e.g., pH) in the photosensitive resin layer caused by an acid, a base, or a radical. Dye N may also be a dye whose colored or decolorized state changes due to a change in the state (e.g., pH) in the photosensitive resin layer caused by an acid, a base, or a radical, without exposure.
[0160] From the viewpoint of visibility of exposed and unexposed areas, dye N is preferably a dye that develops color in response to an acid, a base, or a radical.
[0161] From the viewpoints of visibility of the exposed portion, visibility of the non-exposed portion, and resolution, the dye N is preferably a dye whose maximum absorption wavelength changes with an acid or a radical, and more preferably a dye whose maximum absorption wavelength changes with a radical. From the viewpoints of visibility of the exposed portion, visibility of the non-exposed portion, and resolution, the photosensitive resin layer preferably contains, as the dye N, a dye whose maximum absorption wavelength changes with a radical, and a photoradical polymerization initiator.
[0162] From the viewpoints of visibility of exposed areas, visibility of unexposed areas, and pattern visibility and resolution after development, dye N is preferably a dye whose maximum absorption wavelength changes in response to radicals, and more preferably a dye that develops color in response to radicals.
[0163] The color-developing mechanism of dye N in the present disclosure may, for example, be a mode in which a radical-reactive dye, an acid-reactive dye, or a base-reactive dye (e.g., a leuco dye) develops color due to a radical, an acid, or a base generated from a photoradical polymerization initiator, a photocationic polymerization initiator (photoacid generator), or a photobase generator contained in a photosensitive resin layer.
[0164] From the viewpoint of visibility of the exposed portion and the non-exposed portion, the maximum absorption wavelength of the dye N in the wavelength range of 400 nm to 780 nm during color development is preferably 550 nm or more, more preferably 550 to 700 nm, and even more preferably 550 to 650 nm. The number of maximum absorption wavelengths in the wavelength range of 400 to 780 nm during color development may be one or two or more. When the number of maximum absorption wavelengths in the wavelength range of 400 to 780 nm during color development is two or more, it is sufficient that the maximum absorption wavelength having the highest absorbance among the two or more maximum absorption wavelengths is 450 nm or more.
[0165] The maximum absorption wavelength of dye N is measured by the following method. In an air atmosphere, a spectrophotometer (e.g., UV3100, Shimadzu Corporation) is used to measure the transmission spectrum of a solution containing dye N (liquid temperature: 25°C) in the wavelength range of 400 nm to 780 nm, and the wavelength at which the light intensity is minimal is detected. The wavelength at which the light intensity is minimal is adopted as the maximum absorption wavelength.
[0166] Examples of the dye that develops or loses color upon exposure to light include leuco dyes.
[0167] Examples of dyes that are decolorized by exposure to light include leuco dyes, diarylmethane dyes, oxazine dyes, xanthene dyes, iminonaphthoquinone dyes, azomethine dyes, and anthraquinone dyes.
[0168] From the viewpoint of visibility of exposed areas and visibility of unexposed areas, dye N is preferably a leuco dye.
[0169] Examples of the leuco dye include leuco dyes having a triarylmethane skeleton (triarylmethane dyes), leuco dyes having a spiropyran skeleton (spiropyran dyes), leuco dyes having a fluoran skeleton (fluoran dyes), leuco dyes having a diarylmethane skeleton (diarylmethane dyes), leuco dyes having a rhodamine lactam skeleton (rhodamine lactam dyes), leuco dyes having an indolylphthalide skeleton (indolylphthalide dyes) and leuco dyes having a leucoauramine skeleton (leucoauramine dyes). Among the above, triarylmethane dyes or fluoran dyes are preferred, and leuco dyes having a triphenylmethane skeleton (triphenylmethane dyes) or fluoran dyes are more preferred.
[0170] From the viewpoint of visibility of the exposed and non-exposed areas, the leuco dye preferably has a lactone ring, a sultine ring, or a sultone ring. The lactone ring, sultine ring, or sultone ring in the leuco dye reacts with a radical generated from a photoradical polymerization initiator or an acid generated from a photocationic polymerization initiator, thereby changing the leuco dye into a ring-closed state and causing it to lose color, or changing the leuco dye into a ring-open state and causing it to develop color. The leuco dye is preferably a compound having a lactone ring, a sultine ring, or a sultone ring, which is opened by a radical or an acid to develop color, and more preferably a compound having a lactone ring, which is opened by a radical or an acid to develop color.
[0171] Specific examples of leuco dyes include p,p',p"-hexamethyltriaminotriphenylmethane (leuco crystal violet), Pergascript Blue SRB (Ciba-Geigy), crystal violet lactone, malachite green lactone, benzoyl leucomethylene blue, 2-(N-phenyl-N-methylamino)-6-(Np-tolyl-N-ethyl)aminofluoran, 2-anilino-3-methyl-6-(N-ethyl-p-toluidino)fluoran, 3,6-dimethoxyfluoran, 3-(N,N-diethylamino)-5-methyl-7-(N,N-dibenzylamino)fluoran, 3-(N-cyclohexyl-N-methylamino)-6-(N-cyclohexyl-N-methyl ... -methyl-7-anilinofluoran, 3-(N,N-diethylamino)-6-methyl-7-anilinofluoran, 3-(N,N-diethylamino)-6-methyl-7-xylidinofluoran, 3-(N,N-diethylamino)-6-methyl-7-chlorofluoran, 3-(N,N-diethylamino)-6-methoxy-7-aminofluoran, 3-(N,N-diethylamino)-7-(4-chloroanilino)fluoran, 3-(N,N-diethylamino)-7-chlorofluoran, 3-(N,N-diethylamino)-7-chlorofluoran, 3-(N,N-diethylamino)-7-benzylaminofluoran, 3-(N,N-diethylamino)-7,8-benzofluoran, 3-(N,N-dibutylamino)-6-methyl-7-anilinofluoran, 3-(N,N-dibutylamino)-6-methyl-7-xylidinofluoran, 3-piperidino-6-methyl-7-anilinofluoran, 3-pyrrolidino-6-methyl-7-anilinofluoran, 3,3-bis(1-ethyl-2-methylindol-3-yl)phthalide, 3,3-bis(1-n-butyl-2 -methylindol-3-yl)phthalide, 3,3-bis(p-dimethylaminophenyl)-6-dimethylaminophthalide, 3-(4-diethylamino-2-ethoxyphenyl)-3-(1-ethyl-2-methylindol-3-yl)-4-zaphthalide, 3-(4-diethylaminophenyl)-3-(1-ethyl-2-methylindol-3-yl)phthalide and 3',6'-bis(diphenylamino)spiroisobenzofuran-1(3H),9'-[9H]xanthen-3-one.
[0172] Examples of the pigment N include dyes. Examples of the dyes include brilliant green, ethyl violet, methyl green, crystal violet, basic fuchsin, methyl violet 2B, quinaldine red, rose bengal, metanil yellow, thymolsulfophthalein, xylenol blue, methyl orange, paramethyl red, Congo red, benzopurpurin 4B, α-naphthyl red, Nile blue 2B, Nile blue A, methyl violet, malachite green, parafuchsin, Victoria Pure Blue-naphthalenesulfonate, Victoria Pure Blue BOH (Hodogaya Chemical Industry Co., Ltd.), oil blue #603 (Orient Chemical Industry Co., Ltd.), oil pink #312 (Orient Chemical Industry Co., Ltd.), oil red 5B (Orient Chemical Industry Co., Ltd.), oil scarlet #308 (Orient Chemical Industry Co., Ltd.), and the like. Examples of the pigments that may be used include Orient Chemical Industry Co., Ltd.), Oil Red OG (Orient Chemical Industry Co., Ltd.), Oil Red RR (Orient Chemical Industry Co., Ltd.), Oil Green #502 (Orient Chemical Industry Co., Ltd.), Spiron Red BEH Special (Hodogaya Chemical Co., Ltd.), m-Cresol Purple, Cresol Red, Rhodamine B, Rhodamine 6G, Sulforhodamine B, Auramine, 4-p-diethylaminophenyliminonaphthoquinone, 2-carboxyanilino-4-p-diethylaminophenyliminonaphthoquinone, 2-carboxystearylamino-4-pN,N-bis(hydroxyethyl)amino-phenyliminonaphthoquinone, 1-phenyl-3-methyl-4-p-diethylaminophenylimino-5-pyrazolone, and 1-β-naphthyl-4-p-diethylaminophenylimino-5-pyrazolone.
[0173] Dye N is preferably leuco crystal violet, crystal violet lactone, brilliant green or Victoria Pure Blue-naphthalenesulfonate.
[0174] The photosensitive resin layer may contain one or more kinds of dyes N.
[0175] From the viewpoints of visibility of exposed areas, visibility of unexposed areas, pattern visibility after development, and resolution, the content of dye N is preferably 0.1% by mass or more, more preferably 0.1% by mass to 10% by mass, even more preferably 0.1% by mass to 5% by mass, and particularly preferably 0.1% by mass to 1% by mass, based on the total mass of the photosensitive resin layer. The content of dye N means the content of dye N when all of the dye N contained in the photosensitive resin layer is in a color-developing state. Hereinafter, a method for quantifying the dye will be described using a dye that develops color by radicals as an example. A solution in which a dye (0.001 g) is dissolved in methyl ethyl ketone (100 mL) and a solution in which 0.01 g is dissolved in methyl ethyl ketone (100 mL) are prepared. A photoradical polymerization initiator (Irgacure OXE01, BASF) is added to each solution, and then 365 nm light is irradiated to generate radicals and cause all of the dyes to develop color. Using a spectrophotometer (UV3100, manufactured by Shimadzu Corporation) in an air atmosphere, the absorbance of each solution at a liquid temperature of 25°C is measured, and a calibration curve is created. Next, the absorbance of the solution in which all the dyes have been colored is measured by the same method as described above, except that the photosensitive resin layer (3 g) is dissolved in methyl ethyl ketone instead of the dye. Based on the calibration curve, the amount of dye contained in the photosensitive resin layer is calculated from the absorbance of the solution containing the photosensitive resin layer.
[0176] (Surfactant) From the viewpoint of thickness uniformity, the photosensitive resin layer preferably contains a surfactant. Examples of the surfactant include an anionic surfactant, a cationic surfactant, a nonionic surfactant, and an amphoteric surfactant. The surfactant is preferably a nonionic surfactant. The surfactant is preferably a fluorine-based surfactant or a silicone-based surfactant.
[0177] Commercially available fluorine-based surfactants include, for example, Megafac (e.g., F-171, F-172, F-173, F-176, F-177, F-141, F-142, F-143, F-144, F-437, F-444, F-475, F-477, F-479, F-482, F-551-A, F-552, F-554, F-555-A, F-556, F-557, F-558, F-559, F-5 60, F-561, F-565, F-563, F-568, F-575, F-780, EXP, MFS-330, MFS-578, MFS-578-2, MFS-579, MFS-586, MFS- 587, MFS-628, MFS-631, MFS-603, R-41, R-41-LM, R-01, R-40, R-40-LM, RS-43, TF-1956, RS-90, R-94, RS-72 -K and DS-21, DIC Corporation), Fluorad (e.g., FC430, FC431 and FC171, Sumitomo 3M Limited), Surflon (e.g., S-382, SC-101, SC-103, SC-104, SC-105, SC-1068, SC-381, SC-383, S-393 and KH-40, AGC Corporation), PolyFox (e.g., PF636, PF656, PF632 PF6520 and PF7002, OMNOVA), Futergent (e.g., 710FL, 710FM, 610FM, 601AD, 601ADH2, 602A, 215M, 245F, 251, 212M, 250, 209F, 222F, 208G, 710LA, 710FS, 730LM, 650AC, 681 and 683, NEOS Corporation), and U-120E (Unichem Corporation).
[0178] As the fluorosurfactant, an acrylic compound may be used that has a molecular structure containing a functional group containing a fluorine atom, and when heat is applied, the functional group containing the fluorine atom is broken and the fluorine atom is volatilized. Examples of such fluorosurfactants include the Megafac DS series by DIC Corporation (The Chemical Daily (February 22, 2016), Nikkei Business Daily (February 23, 2016), for example, Megafac DS-21).
[0179] As the fluorine-based surfactant, a polymer of a fluorine atom-containing vinyl ether compound having a fluorinated alkyl group or a fluorinated alkylene ether group and a hydrophilic vinyl ether compound may be used.
[0180] As the fluorosurfactant, a block polymer may be used.
[0181] As the fluorine-based surfactant, a fluorine-containing polymer compound containing a structural unit derived from a (meth)acrylate compound containing a fluorine atom and a structural unit derived from a (meth)acrylate compound containing two or more (preferably five or more) alkyleneoxy groups (preferably ethyleneoxy groups or propyleneoxy groups) may be used.
[0182] As the fluorosurfactant, a fluorine-containing polymer having a group containing an ethylenically unsaturated bond in a side chain may be used. Commercially available products of the above-mentioned fluorosurfactant include, for example, Megafac (e.g., RS-101, RS-102, RS-718K and RS-72-K, DIC Corporation).
[0183] From the viewpoint of improving environmental compatibility, it is preferable that the fluorosurfactant be a surfactant derived from an alternative material to compounds having a linear perfluoroalkyl group having 7 or more carbon atoms, such as perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS).
[0184] Examples of nonionic surfactants include glycerol, trimethylolpropane, trimethylolethane, and their ethoxylates (e.g., glycerol ethoxylate) and propoxylates (e.g., glycerol propoxylate). Examples of nonionic surfactants include polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene nonylphenyl ether, polyethylene glycol dilaurate, polyethylene glycol distearate, sorbitan fatty acid esters, Pluronic (e.g., L10, L31, L61, L62, 10R5, 17R2, and 25R2, HYDROPALAT WE 3323, BASF), Tetronic (e.g., 304, 701, 704, 901, 904 and 150R1, BASF), Solsperse 20000 (Lubrizol Japan Co., Ltd.), NCW-101 (FUJIFILM Wako Pure Chemical Industries Co., Ltd.), NCW-1001 (FUJIFILM Wako Pure Chemical Industries Co., Ltd.), NCW-1002 (FUJIFILM Wako Pure Chemical Industries Co., Ltd.), Paionin (e.g., D-1105, D-6112, D-6112-W and D-6315, Takemoto Yushi Co., Ltd.), Olfine E1010 (Nissin Chemical Industry Co., Ltd.) and Surfynol (e.g., 104, 400 and 440, Nissin Chemical Industry Co., Ltd.).
[0185] Examples of silicone surfactants include linear polymers formed from siloxane bonds and modified siloxane polymers in which organic groups have been introduced into the side chains or ends.
[0186] Examples of surfactants include DOWSIL8032 ADDITIVE, Toray Silicone DC3PA, Toray Silicone SH7PA, Toray Silicone DC11PA, Toray Silicone SH21PA, Toray Silicone SH28PA, Toray Silicone SH29PA, Toray Silicone SH30PA, and Toray Silicone SH8400 (Dow Corning Toray Co., Ltd.).
[0187] Examples of the surfactant include EXP.S-309-2, EXP.S-315, EXP.S-503-2, and EXP.S-505-2 (all manufactured by DIC Corporation).
[0188] Examples of surfactants include X-22-4952, X-22-4272, X-22-6266, KF-351A, K354L, KF-355A, KF-945, KF-640, KF-642, KF-643, X-22-6191, X-22-4515, KF-6004, KP-341, KF-6001, and KF-6002 (Shin-Etsu Chemical Co., Ltd.).
[0189] Surfactants include, for example, F-4440, TSF-4300, TSF-4445, TSF-4460, and TSF-4452 (Momentive Performance Materials, Inc.).
[0190] Examples of surfactants include BYK307, BYK323, and BYK330 (BYK-Chemie).
[0191] Examples of surfactants include BYK300, BYK306, BYK310, BYK320, BYK325, BYK313, BYK315N, BYK331, BYK333, BYK345, BYK347, BYK348, BYK349, BYK370, BYK377, BYK378, and BYK323 (all manufactured by BYK-Chemie).
[0192] The photosensitive resin layer may contain one or more types of surfactants.
[0193] The content of the surfactant is preferably from 0.001% by mass to 10% by mass, and more preferably from 0.01% by mass to 3% by mass, based on the total mass of the photosensitive resin layer.
[0194] (Additives) In addition to the above components, the photosensitive resin layer may contain known additives as necessary. Examples of additives include thermal crosslinking compounds, radical polymerization inhibitors, benzotriazoles, carboxybenzotriazoles, sensitizers, plasticizers, heterocyclic compounds, and solvents. The photosensitive resin layer may contain one or more additives.
[0195] The photosensitive resin layer preferably contains a thermally crosslinkable compound from the viewpoints of the strength of the obtained cured film and the adhesion of the obtained uncured film. In this specification, the thermally crosslinkable compound having an ethylenically unsaturated group described later is not treated as an ethylenically unsaturated compound but as a thermally crosslinkable compound. Examples of the thermally crosslinkable compound include methylol compounds and blocked isocyanate compounds. Among these, blocked isocyanate compounds are preferred from the viewpoints of the strength of the resulting cured film and the adhesion of the resulting uncured film. Since the blocked isocyanate compound reacts with a hydroxy group and a carboxy group, for example, when the polymer A and / or the ethylenically unsaturated compound has at least one of a hydroxy group and a carboxy group, the hydrophilicity of the formed film tends to decrease, and the functionality tends to be enhanced when the film obtained by curing the photosensitive resin layer is used as a protective film. The blocked isocyanate compound refers to a compound having a structure in which the isocyanate group of an isocyanate is protected (so-called masked) with a blocking agent.
[0196] The dissociation temperature of the blocked isocyanate compound is not particularly limited, but is preferably from 100°C to 160°C, and more preferably from 130°C to 150°C. The dissociation temperature of a blocked isocyanate means "the temperature of an endothermic peak accompanying the deprotection reaction of a blocked isocyanate when measured by DSC (Differential Scanning Calorimetry) analysis using a differential scanning calorimeter." As the differential scanning calorimeter, for example, a differential scanning calorimeter (model: DSC6200) manufactured by Seiko Instruments Inc. can be suitably used. However, the differential scanning calorimeter is not limited to this.
[0197] Examples of blocking agents having a dissociation temperature of 100°C to 160°C include active methylene compounds [malonic acid diesters (dimethyl malonate, diethyl malonate, di-n-butyl malonate, di-2-ethylhexyl malonate, etc.)] and oxime compounds (compounds having a structure represented by -C(=N-OH)- in the molecule, such as formaldoxime, acetaldoxime, acetoxime, methylethylketoxime, and cyclohexanoneoxime). Among these, the blocking agent having a dissociation temperature of 100° C. to 160° C. preferably contains an oxime compound, for example, from the viewpoint of storage stability.
[0198] The blocked isocyanate compound preferably has an isocyanurate structure from the viewpoints of, for example, improving the brittleness of the film and improving the adhesive strength to the transfer target. A blocked isocyanate compound having an isocyanurate structure can be obtained, for example, by protecting hexamethylene diisocyanate by converting it into an isocyanurate. Among blocked isocyanate compounds having an isocyanurate structure, a compound having an oxime structure in which an oxime compound is used as a blocking agent is preferred from the viewpoints that it is easier to set the dissociation temperature in a preferred range and to reduce development residues than a compound not having an oxime structure.
[0199] The blocked isocyanate compound may have a polymerizable group. The polymerizable group is not particularly limited, and any known polymerizable group can be used, with a radically polymerizable group being preferred. Examples of the polymerizable group include ethylenically unsaturated groups such as a (meth)acryloxy group, a (meth)acrylamide group, and a styryl group, as well as groups having an epoxy group such as a glycidyl group. Among these, as the polymerizable group, an ethylenically unsaturated group is preferable, a (meth)acryloxy group is more preferable, and an acryloxy group is even more preferable.
[0200] As the blocked isocyanate compound, commercially available products can be used. Examples of commercially available blocked isocyanate compounds include Karenz (registered trademark) AOI-BM, Karenz (registered trademark) MOI-BM, Karenz (registered trademark) MOI-BP, and the like (all manufactured by Showa Denko K.K.), and the blocked Duranate series (e.g., Duranate (registered trademark) TPA-B80E, Duranate (registered trademark) WT32-B75P, and the like, manufactured by Asahi Kasei Chemicals Corporation). In addition, as the blocked isocyanate compound, a compound having the following structure can also be used.
[0201] [ka]
[0202] The thermally crosslinkable compounds may be used alone or in combination of two or more. When the photosensitive resin layer contains a thermally crosslinkable compound, the content of the thermally crosslinkable compound is preferably 1 mass % to 50 mass %, and more preferably 5 mass % to 30 mass %, based on the total mass of the photosensitive resin layer.
[0203] The radical polymerization inhibitor may be, for example, a thermal polymerization inhibitor described in paragraph 0018 of Japanese Patent No. 4502784. The radical polymerization inhibitor is preferably phenothiazine, phenoxazine, or 4-methoxyphenol. The radical polymerization inhibitor may also be, for example, naphthylamine, cuprous chloride, nitrosophenylhydroxyamine aluminum salt, and diphenylnitrosamine. In order not to impair the sensitivity of the photosensitive resin layer, it is preferable to use nitrosophenylhydroxyamine aluminum salt as the radical polymerization inhibitor.
[0204] Examples of benzotriazoles include 1,2,3-benzotriazole, 1-chloro-1,2,3-benzotriazole, bis(N-2-ethylhexyl)aminomethylene-1,2,3-benzotriazole, bis(N-2-ethylhexyl)aminomethylene-1,2,3-tolyltriazole, and bis(N-2-hydroxyethyl)aminomethylene-1,2,3-benzotriazole.
[0205] Examples of carboxybenzotriazoles include 4-carboxy-1,2,3-benzotriazole, 5-carboxy-1,2,3-benzotriazole, N-(N,N-di-2-ethylhexyl)aminomethylenecarboxybenzotriazole, N-(N,N-di-2-hydroxyethyl)aminomethylenecarboxybenzotriazole, and N-(N,N-di-2-ethylhexyl)aminoethylenecarboxybenzotriazole. Examples of commercially available carboxybenzotriazoles include CBT-1 (Johoku Chemical Industry Co., Ltd.).
[0206] The total content of the radical polymerization inhibitor, benzotriazoles and carboxybenzotriazoles is preferably 0.01% by mass to 3% by mass, more preferably 0.05% by mass to 1% by mass, based on the total mass of the photosensitive resin layer. It is preferable to set the total content of the above additives to 0.01% by mass or more from the viewpoint of imparting storage stability to the photosensitive resin layer. On the other hand, it is preferable to set the total content of the above additives to 3% by mass or less from the viewpoint of maintaining sensitivity and suppressing discoloration of the dye.
[0207] The type of the sensitizer is not limited. Examples of the sensitizer include a dialkylaminobenzophenone compound, a pyrazoline compound, an anthracene compound, a coumarin compound, a xanthone compound, a thioxanthone compound, an acridone compound, an oxazole compound, a benzoxazole compound, a thiazole compound, a benzothiazole compound, a triazole compound (e.g., 1,2,4-triazole), a stilbene compound, a triazine compound, a thiophene compound, a naphthalimide compound, a triarylamine compound, and an aminoacridine compound.
[0208] From the viewpoint of improving the sensitivity to the light source and improving the curing speed by balancing the polymerization rate and chain transfer, when the photosensitive resin layer contains a sensitizer, the content of the sensitizer is preferably 0.01% by mass to 5% by mass, and more preferably 0.05% by mass to 1% by mass, relative to the total mass of the photosensitive resin layer.
[0209] Examples of the plasticizer and heterocyclic compound include the compounds described in paragraphs 0097 to 0103 and paragraphs 0111 to 0118 of WO 2018 / 179640.
[0210] Examples of the solvent include the solvents described in the section "Method of forming a photosensitive resin layer" below. For example, when a photosensitive resin layer is formed using a composition for forming a photosensitive resin layer containing a solvent, the solvent may remain in the photosensitive resin layer.
[0211] The photosensitive resin layer may further contain at least one selected from the group consisting of metal oxide particles, antioxidants, dispersants, acid multipliers, development accelerators, conductive fibers, thermal radical polymerization initiators, thermal acid generators, ultraviolet absorbers, thickeners, crosslinking agents, organic suspending agents, and inorganic suspending agents.
[0212] Additives contained in the photosensitive resin layer are described in paragraphs 0165 to 0184 of JP2014-85643A, the contents of which are incorporated herein by reference.
[0213] (impurities) The photosensitive resin layer may contain impurities. Examples of impurities include sodium, potassium, magnesium, calcium, iron, manganese, copper, aluminum, titanium, chromium, cobalt, nickel, zinc, tin, halogens, and ions thereof. Since halide ions, sodium ions, and potassium ions are easily mixed in as impurities, it is preferable that the contents of halide ions, sodium ions, and potassium ions are within the following ranges.
[0214] The content of impurities in the photosensitive resin layer is preferably 80 ppm or less, more preferably 10 ppm or less, and particularly preferably 2 ppm or less, based on the total mass of the photosensitive resin layer. The content of impurities in the photosensitive resin layer may be 1 ppb or more, or 0.1 ppm or more, based on the total mass of the photosensitive resin layer. Methods for making the content of impurities within the above range include selecting raw materials with a low content of impurities, preventing impurities from being mixed in when forming the photosensitive resin layer, and removing them by washing. Impurities are quantified by known methods such as ICP (Inductively Coupled Plasma) emission spectroscopy, atomic absorption spectroscopy, and ion chromatography.
[0215] The content of compounds such as benzene, formaldehyde, trichloroethylene, 1,3-butadiene, carbon tetrachloride, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide and hexane in the photosensitive resin layer is preferably low. The content of the above compounds in the photosensitive resin layer is preferably 100 ppm or less, more preferably 20 ppm or less, and particularly preferably 4 ppm or less, based on the total mass of the photosensitive resin layer. The content of the above compounds in the photosensitive resin layer may be 10 ppb or more or 100 ppb or more, based on the total mass of the photosensitive resin layer. The content of the above compounds is adjusted by the same method as the method for adjusting the content of the above impurities. The above compounds are quantified by a known measurement method.
[0216] From the viewpoint of improving reliability and lamination properties, the water content in the photosensitive resin layer is preferably 0.01 mass % to 1.0 mass %, and more preferably 0.05 mass % to 0.5 mass %, based on the total mass of the photosensitive resin layer.
[0217] (Residual monomer) The photosensitive resin layer may contain residual monomers, for example, residual monomers corresponding to each structural unit of the polymer A described above. From the viewpoints of patterning property and reliability, the content of the residual monomer is preferably 5,000 ppm by mass or less, more preferably 2,000 ppm by mass or less, and even more preferably 500 ppm by mass or less, based on the total mass of the polymer A. There is no particular lower limit for the content of the residual monomer, but it is preferably 1 ppm by mass or more, and more preferably 10 ppm by mass or more, based on the total mass of the polymer A. From the viewpoints of patterning property and reliability, the content of the residual monomer corresponding to each structural unit of the polymer A is preferably 3,000 mass ppm or less, more preferably 600 mass ppm or less, and even more preferably 100 mass ppm or less, based on the total mass of the photosensitive resin layer. The lower limit of the content of the residual monomer corresponding to each structural unit of the polymer A is not particularly limited, but is preferably 0.1 mass ppm or more, more preferably 1 mass ppm or more, based on the total mass of the photosensitive resin layer.
[0218] The amount of residual monomers in the synthesis of polymer A by the polymer reaction is also preferably within the above range. For example, when polymer A is synthesized by reacting glycidyl acrylate with a carboxylic acid side chain, the content of glycidyl acrylate is preferably within the above range. The amount of the residual monomer can be measured by a known method such as liquid chromatography or gas chromatography.
[0219] (Thickness) The thickness of the photosensitive resin layer is not limited. The thickness of the photosensitive resin layer is determined, for example, in the range of 0.1 μm to 100 μm. From the viewpoint of developability and resolution, the thickness of the photosensitive resin layer is preferably 50 μm or less, more preferably 30 μm or less, and particularly preferably 20 μm or less. Furthermore, the thickness of the photosensitive resin layer is preferably 10 μm or less, and more preferably 5 μm or less. From the viewpoint of resistance to processing solutions such as a developing solution, the thickness of the photosensitive resin layer is preferably 0.1 μm or more, more preferably 0.2 μm or more, and particularly preferably 0.5 μm or more. Furthermore, the thickness of the photosensitive resin layer is preferably 0.5 μm to 10 μm, and more preferably 0.5 μm to 5 μm. Moreover, the thickness of the photosensitive resin layer is preferably 0.5 μm to 5 μm, and particularly preferably 0.5 μm to 4 μm. The thickness of the photosensitive resin layer is measured by a method similar to the method for measuring the thickness of the temporary support.
[0220] (transmittance) From the viewpoint of superior adhesion, the transmittance of the photosensitive resin layer at a wavelength of 365 nm is preferably 10% or more, more preferably 30% or more, and particularly preferably 50% or more. There is no upper limit to the transmittance of the photosensitive resin layer at a wavelength of 365 nm. The transmittance of the photosensitive resin layer at a wavelength of 365 nm is preferably 99.9% or less.
[0221] (Method of forming photosensitive resin layer) The method for forming the photosensitive resin layer is not limited as long as it is a method capable of forming a layer containing the above-mentioned components. The photosensitive resin layer is formed, for example, by preparing a composition for forming a photosensitive resin layer, applying the composition for forming a photosensitive resin layer on a temporary support, and drying the applied composition for forming a photosensitive resin layer.
[0222] The photosensitive resin layer forming composition may, for example, be a composition containing a polymer A, a polymerizable compound B, and a photopolymerization initiator. In order to adjust the viscosity of the photosensitive resin layer forming composition and facilitate the formation of the photosensitive resin layer, the photosensitive resin layer forming composition preferably contains a solvent.
[0223] The solvent is not limited as long as it can dissolve or disperse the components of the photosensitive resin layer. Examples of the solvent include alkylene glycol ether solvents, alkylene glycol ether acetate solvents, alcohol solvents (e.g., methanol and ethanol), ketone solvents (e.g., acetone and methyl ethyl ketone), aromatic hydrocarbon solvents (e.g., toluene), aprotic polar solvents (e.g., N,N-dimethylformamide), cyclic ether solvents (e.g., tetrahydrofuran), ester solvents, amide solvents, and lactone solvents.
[0224] Examples of alkylene glycol ether solvents include ethylene glycol monoalkyl ethers, ethylene glycol dialkyl ethers, propylene glycol monoalkyl ethers, propylene glycol dialkyl ethers, diethylene glycol dialkyl ethers, dipropylene glycol monoalkyl ethers, and dipropylene glycol dialkyl ethers.
[0225] Examples of alkylene glycol ether acetate solvents include ethylene glycol monoalkyl ether acetate, propylene glycol monoalkyl ether acetate, diethylene glycol monoalkyl ether acetate, and dipropylene glycol monoalkyl ether acetate.
[0226] Examples of the solvent include the solvents described in paragraphs 0092 to 0094 of WO 2018 / 179640 and the solvents described in paragraph 0014 of JP 2018-177889 A. The contents of these publications are incorporated herein by reference.
[0227] The photosensitive resin layer forming composition may contain one or more solvents. The photosensitive resin layer forming composition preferably contains at least one selected from the group consisting of alkylene glycol ether solvents and alkylene glycol ether acetate solvents, more preferably contains at least one selected from the group consisting of alkylene glycol ether solvents and alkylene glycol ether acetate solvents, and at least one selected from the group consisting of ketone solvents and cyclic ether solvents, and particularly preferably contains at least one selected from the group consisting of alkylene glycol ether solvents and alkylene glycol ether acetate solvents, a ketone solvent, and a cyclic ether solvent.
[0228] The content of the solvent in the composition for forming a photosensitive resin layer is preferably 50 parts by mass to 1,900 parts by mass, and more preferably 100 parts by mass to 900 parts by mass, relative to 100 parts by mass of the total solid content in the composition for forming a photosensitive resin layer.
[0229] The method for preparing the composition for forming a photosensitive resin layer is not limited. For example, the composition for forming a photosensitive resin layer is prepared by dissolving each component in a solvent in advance and mixing the obtained solution in a predetermined ratio. Before forming the photosensitive resin layer, it is preferable to filter the composition for forming a photosensitive resin layer using a filter with a pore size of 0.2 μm to 30 μm.
[0230] Examples of the method for applying the photosensitive resin layer-forming composition include slit coating, spin coating, curtain coating, and inkjet coating.
[0231] <<Thermoplastic resin layer>> The photosensitive transfer material according to the present disclosure may include a thermoplastic resin layer. When the photosensitive transfer material includes a thermoplastic resin layer, the conformability of the photosensitive transfer material to the substrate is improved during lamination of the photosensitive transfer material and the substrate, and the inclusion of air bubbles between the photosensitive transfer material and the substrate is suppressed. In addition, when the photosensitive transfer material includes a thermoplastic resin layer, the adhesion between the layers is improved. The photosensitive transfer material according to the present disclosure preferably includes a thermoplastic resin layer between the temporary support and the photosensitive resin layer. The thermoplastic resin layer is described, for example, in paragraphs 0189 to 0193 of JP 2014-85643 A. The contents of the above publications are incorporated herein by reference.
[0232] (alkali soluble resin) The thermoplastic resin layer preferably contains an alkali-soluble resin as a thermoplastic resin, such as an acrylic resin, a polystyrene resin, a styrene-acrylic copolymer, a polyurethane resin, a polyvinyl alcohol, a polyvinyl formal, a polyamide resin, a polyester resin, a polyamide resin, an epoxy resin, a polyacetal resin, a polyhydroxystyrene resin, a polyimide resin, a polybenzoxazole resin, a polysiloxane resin, a polyethyleneimine, a polyallylamine, and a polyalkylene glycol.
[0233] From the viewpoint of developability and adhesion to adjacent layers, the alkali-soluble resin is preferably an acrylic resin. Here, the acrylic resin means a resin containing at least one selected from the group consisting of a structural unit derived from (meth)acrylic acid, a structural unit derived from a (meth)acrylic acid ester, and a structural unit derived from a (meth)acrylic acid amide. From the viewpoint of developability and adhesion to adjacent layers, the alkali-soluble resin is particularly preferably an acrylic resin having a structural unit derived from (meth)acrylic acid.
[0234] The total content of the (meth)acrylic acid-derived structural units, the (meth)acrylic acid ester-derived structural units, and the (meth)acrylic acid amide-derived structural units is preferably 50% by mass or more based on the total mass of the acrylic resin. The total content of the (meth)acrylic acid-derived structural units and the (meth)acrylic acid ester-derived structural units is preferably 30% by mass to 100% by mass, and more preferably 50% by mass to 100% by mass, based on the total mass of the acrylic resin.
[0235] The alkali-soluble resin preferably contains an acid group. Examples of the acid group include a carboxy group, a sulfo group, a phosphoric acid group, and a phosphonic acid group. The acid group is preferably a carboxy group.
[0236] From the viewpoint of developability, the alkali-soluble resin is preferably an alkali-soluble resin having an acid value of 60 mgKOH / g or more, more preferably a carboxyl group-containing acrylic resin having an acid value of 60 mgKOH / g or more, and the acid value of the alkali-soluble resin is preferably 200 mgKOH / g or less, more preferably 150 mgKOH / g or less.
[0237] Examples of carboxyl group-containing acrylic resins having an acid value of 60 mgKOH / g or more include carboxyl group-containing acrylic resins having an acid value of 60 mgKOH / g or more among the polymers described in paragraph 0025 of JP2011-95716A, carboxyl group-containing acrylic resins having an acid value of 60 mgKOH / g or more among the polymers described in paragraphs 0033 to 0052 of JP2010-237589A, and carboxyl group-containing acrylic resins having an acid value of 60 mgKOH / g or more among the binder polymers described in paragraphs 0053 to 0068 of JP2016-224162A.
[0238] The content of structural units having a carboxy group in the carboxy group-containing acrylic resin is preferably 5% by mass to 50% by mass, more preferably 10% by mass to 40% by mass, and particularly preferably 12% by mass to 30% by mass, relative to the total mass of the acrylic resin.
[0239] The alkali-soluble resin may contain a reactive group, such as an ethylenically unsaturated group, a polycondensation group (e.g., a hydroxy group and a carboxy group), and a polyaddition reactive group (e.g., an epoxy group and a (blocked) isocyanate group).
[0240] The weight average molecular weight (Mw) of the alkali-soluble resin is preferably 1,000 or more, more preferably 10,000 to 100,000, and particularly preferably 20,000 to 50,000.
[0241] The thermoplastic resin layer may contain one or more types of alkali-soluble resins.
[0242] From the viewpoint of developability and adhesion to adjacent layers, the content of the alkali-soluble resin is preferably 10% by mass to 99% by mass, more preferably 20% by mass to 90% by mass, even more preferably 40% by mass to 80% by mass, and particularly preferably 50% by mass to 70% by mass, relative to the total mass of the thermoplastic resin layer.
[0243] (dye) The thermoplastic resin layer preferably contains a dye (hereinafter sometimes referred to as "dye B") that has a maximum absorption wavelength of 450 nm or more in the wavelength range of 400 to 780 nm during color development and whose maximum absorption wavelength changes with an acid, a base, or a radical. Preferred aspects of dye B are the same as those of dye N, except for the following points.
[0244] From the viewpoints of visibility of exposed areas and visibility and resolution of unexposed areas, dye B is preferably a dye whose maximum absorption wavelength changes in response to an acid or a radical, and more preferably a dye whose maximum absorption wavelength changes in response to an acid.
[0245] The thermoplastic resin layer may contain one or more dyes B.
[0246] From the viewpoint of visibility of the exposed portion and the non-exposed portion, the content of the dye B is preferably 0.2% by mass or more, more preferably 0.2% by mass to 6% by mass, even more preferably 0.2% by mass to 5% by mass, and particularly preferably 0.25% by mass to 3.0% by mass, based on the total mass of the thermoplastic resin layer. Here, the content of the dye B means the content of the dye when all of the dye B contained in the thermoplastic resin layer is in a colored state. Hereinafter, a method for quantifying the dye will be described using a dye that develops color by radicals as an example. A solution in which the dye B (0.001 g) is dissolved in methyl ethyl ketone (100 mL) and a solution in which the dye B (0.01 g) is dissolved in methyl ethyl ketone (100 mL) are prepared. A photoradical polymerization initiator (Irgacure OXE01, BASF) is added to each solution, and then 365 nm light is irradiated to generate radicals and cause all of the dyes to develop color. Using a spectrophotometer (UV3100, Shimadzu Corporation) in an air atmosphere, the absorbance of each solution at a liquid temperature of 25°C is measured, and a calibration curve is created. Next, the absorbance of the solution in which all the dyes have been colored is measured by the same method as above, except that the thermoplastic resin layer (0.1 g) is dissolved in methyl ethyl ketone instead of the dye. Based on the calibration curve, the amount of dye contained in the thermoplastic resin layer is calculated from the absorbance of the solution containing the thermoplastic resin layer.
[0247] From the viewpoints of visibility of exposed areas and visibility and resolution of unexposed areas, the thermoplastic resin layer preferably contains a dye whose maximum absorption wavelength changes in response to an acid as dye B, and a compound that generates an acid when exposed to light. The compound that generates an acid when exposed to light will be described later.
[0248] (Compounds that generate acids, bases, or radicals when exposed to light) The thermoplastic resin layer may contain a compound (hereinafter, sometimes referred to as "compound C") that generates an acid, a base, or a radical when exposed to light. Compound C is preferably a compound that generates an acid, a base, or a radical when exposed to actinic rays (e.g., ultraviolet light and visible light). Examples of compound C include photoacid generators, photobase generators, and photoradical polymerization initiators (photoradical generators). Among the above, photoacid generators are preferred.
[0249] From the viewpoint of resolution, the thermoplastic resin layer preferably contains a photoacid generator. Examples of the photoacid generator include the photocationic polymerization initiator described in the above "photosensitive resin layer". A preferred embodiment of the photoacid generator is the same as the preferred embodiment of the photocationic polymerization initiator described in the above "photosensitive resin layer" except for the matters shown below. From the viewpoint of sensitivity and resolution, the photoacid generator preferably contains at least one selected from the group consisting of an onium salt compound and an oxime sulfonate compound. From the viewpoint of sensitivity, resolution and adhesion, the photoacid generator preferably contains an oxime sulfonate compound. Specific examples of preferred photoacid generators are shown below.
[0250] [ka]
[0251] The thermoplastic resin layer may contain a photobase generator. Examples of the photobase generator include 2-nitrobenzyl cyclohexyl carbamate, triphenylmethanol, O-carbamoyl hydroxylamide, O-carbamoyl oxime, [[(2,6-dinitrobenzyl)oxy]carbonyl]cyclohexylamine, bis[[(2-nitrobenzyl)oxy]carbonyl]hexane 1,6-diamine, 4-(methylthiobenzoyl)-1-methyl-1-morpholinoethane, (4-morpholinobenzoyl)-1-benzyl-1-diamine, and the like. Methylaminopropane, N-(2-nitrobenzyloxycarbonyl)pyrrolidine, hexaamminecobalt(III) tris(triphenylmethylborate), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone, 2,6-dimethyl-3,5-diacetyl-4-(2-nitrophenyl)-1,4-dihydropyridine and 2,6-dimethyl-3,5-diacetyl-4-(2,4-dinitrophenyl)-1,4-dihydropyridine.
[0252] The thermoplastic resin layer may contain a photoradical polymerization initiator. Examples of the photoradical polymerization initiator include the photoradical polymerization initiators described above in the "Photosensitive resin layer" section. A preferred embodiment of the photoradical polymerization initiator is the same as the preferred embodiment of the photoradical polymerization initiator described above in the "Photosensitive resin layer" section.
[0253] The thermoplastic resin layer may contain one or more compounds C.
[0254] From the viewpoints of visibility of exposed areas and visibility and resolution of non-exposed areas, the content of compound C in the thermoplastic resin layer is preferably 0.1 mass% to 10 mass%, and more preferably 0.5 mass% to 5 mass%, relative to the total mass of the thermoplastic resin layer.
[0255] (Plasticizer) From the viewpoints of resolution, adhesion to adjacent layers, and developability, the thermoplastic resin layer preferably contains a plasticizer.
[0256] The molecular weight of the plasticizer (weight average molecular weight (Mw) when the plasticizer has a molecular weight distribution) is preferably smaller than the molecular weight of the alkali-soluble resin. The molecular weight of the plasticizer is preferably 200 to 2,000.
[0257] The plasticizer may be, for example, a compound that is compatible with an alkali-soluble resin and exhibits plasticity. From the viewpoint of imparting plasticity, the plasticizer is preferably a compound that contains an alkyleneoxy group in the molecule, and more preferably a polyalkylene glycol compound. The alkyleneoxy group contained in the plasticizer more preferably has a polyethyleneoxy structure or a polypropyleneoxy structure.
[0258] From the viewpoint of resolution and storage stability, the plasticizer preferably contains a (meth)acrylate compound. From the viewpoint of compatibility, resolution, and adhesion with adjacent layers, it is more preferable that the alkali-soluble resin is an acrylic resin and the plasticizer contains a (meth)acrylate compound. Examples of the (meth)acrylate compound used as the plasticizer include the (meth)acrylate compounds described in the above section on "polymerizable compound B". When the thermoplastic resin layer is in contact with the photosensitive resin layer in the photosensitive transfer material, it is preferable that the thermoplastic resin layer and the photosensitive resin layer contain the same (meth)acrylate compound. By containing the same (meth)acrylate compound in the thermoplastic resin layer and the photosensitive resin layer, the diffusion of components between the layers is suppressed, and storage stability is improved.
[0259] From the viewpoint of adhesion to adjacent layers, it is preferable that the (meth)acrylate compound used as a plasticizer does not polymerize even in the exposed area after exposure.
[0260] From the viewpoints of resolution, adhesion to adjacent layers, and developability, the (meth)acrylate compound used as a plasticizer is preferably a (meth)acrylate compound having two or more (meth)acryloyl groups in one molecule.
[0261] The (meth)acrylate compound used as the plasticizer is also preferably a (meth)acrylate compound having an acid group or a urethane (meth)acrylate compound.
[0262] The thermoplastic resin layer may contain one or more plasticizers.
[0263] From the viewpoints of resolution, adhesion to adjacent layers, and developability, the content of the plasticizer in the thermoplastic resin layer is preferably 1% by mass to 70% by mass, more preferably 10% by mass to 60% by mass, and particularly preferably 20% by mass to 50% by mass, relative to the total mass of the thermoplastic resin layer.
[0264] (Surfactant) From the viewpoint of thickness uniformity, the thermoplastic resin layer preferably contains a surfactant. Examples of the surfactant include the surfactants described in the above "Photosensitive resin layer". The preferred aspects of the surfactant are the same as those described in the above "Photosensitive resin layer".
[0265] The thermoplastic resin layer may contain one or more surfactants.
[0266] The content of the surfactant in the thermoplastic resin layer is preferably 0.001% by mass to 10% by mass, and more preferably 0.01% by mass to 3% by mass, based on the total mass of the thermoplastic resin layer.
[0267] (sensitizer) The thermoplastic resin layer may contain a sensitizer, for example, the sensitizers described above in the section "Photosensitive resin layer."
[0268] The thermoplastic resin layer may contain one or more sensitizers.
[0269] From the viewpoints of improving sensitivity to the light source and visibility of exposed and non-exposed areas, the content of the sensitizer is preferably 0.01% by mass to 5% by mass, and more preferably 0.05% by mass to 1% by mass, relative to the total mass of the thermoplastic resin layer.
[0270] (Additives) The thermoplastic resin layer may contain known additives, in addition to the above-mentioned components, as necessary.
[0271] (Thickness) The thickness of the thermoplastic resin layer is not limited. From the viewpoint of adhesion with adjacent layers, the thickness of the thermoplastic resin layer is preferably 1 μm or more, more preferably 2 μm or more. From the viewpoint of developability and resolution, the thickness of the thermoplastic resin layer is preferably 20 μm or less, more preferably 10 μm or less, and particularly preferably 5 μm or less. The thickness of the thermoplastic resin layer is measured by a method similar to the method for measuring the thickness of the temporary support.
[0272] (Method of forming thermoplastic resin layer) The method for forming the thermoplastic resin layer is not limited as long as it is a method capable of forming a layer containing the above-mentioned components. The thermoplastic resin layer is formed, for example, by preparing a composition for forming a thermoplastic resin layer, applying the composition for forming a thermoplastic resin layer onto an object (for example, a photosensitive resin layer), and drying the applied composition for forming a thermoplastic resin layer.
[0273] In order to adjust the viscosity of the composition for forming a thermoplastic resin layer and to facilitate the formation of the thermoplastic resin layer, the composition for forming a thermoplastic resin layer preferably contains a solvent. The solvent is not limited as long as it is a solvent capable of dissolving or dispersing the components of the thermoplastic resin layer. Examples of the solvent include the solvents described in the above section "Photosensitive resin layer". The preferred embodiment of the solvent is the same as the preferred embodiment of the solvent described in the above section "Photosensitive resin layer".
[0274] The composition for forming a thermoplastic resin layer may contain one or more solvents.
[0275] The content of the solvent in the composition for forming a thermoplastic resin layer is preferably 50 parts by mass to 1,900 parts by mass, and more preferably 100 parts by mass to 900 parts by mass, per 100 parts by mass of the total solid content in the composition for forming a thermoplastic resin layer.
[0276] The thermoplastic resin layer forming composition is prepared, for example, by a method similar to the preparation method of the photosensitive resin layer forming composition. The thermoplastic resin layer forming composition is applied, for example, by a method similar to the application method of the photosensitive resin layer forming composition.
[0277] <<Middle layer>> The photosensitive transfer material according to the present disclosure preferably includes an intermediate layer between the photosensitive resin layer and the thermoplastic resin layer. By including the intermediate layer in the photosensitive transfer material, it is possible to suppress interlayer mixing of components during the formation of the photosensitive transfer material or the storage of the photosensitive transfer material. From the viewpoint of developability and suppression of interlayer mixing of components during the formation of the photosensitive transfer material or the storage of the photosensitive transfer material, the intermediate layer is preferably a water-soluble layer. In the present disclosure, "water-soluble" means a property in which the solubility in water (100 g) of pH 7.0 at a liquid temperature of 22°C is 0.1 g or more.
[0278] An example of the intermediate layer is an oxygen barrier layer having an oxygen barrier function, which is described as a "separation layer" in JP-A-5-72724. The oxygen barrier layer is preferable in that it improves the sensitivity during exposure, reduces the time load of the exposure machine, and improves productivity. The oxygen barrier layer is preferably an oxygen barrier layer that exhibits low oxygen permeability and disperses or dissolves in water or an alkaline aqueous solution (1% by mass sodium carbonate aqueous solution, liquid temperature: 22°C).
[0279] The intermediate layer preferably contains a resin. Examples of the resin include polyvinyl alcohol resins, polyvinylpyrrolidone resins, cellulose resins, acrylamide resins, polyethylene oxide resins, gelatin, vinyl ether resins, and polyamide resins. The resin may be a homopolymer or a copolymer. The resin is preferably a water-soluble resin.
[0280] From the viewpoints of oxygen barrier properties and suppressing intermixing of components that occurs between layers during formation of the photosensitive transfer material or storage of the photosensitive transfer material, the intermediate layer preferably contains polyvinyl alcohol, and more preferably contains polyvinyl alcohol and polyvinylpyrrolidone.
[0281] From the viewpoint of suppressing mixing of components between layers, it is preferable that the resin contained in the intermediate layer is a resin different from the polymer A contained in the photosensitive resin layer and a resin different from the thermoplastic resin (e.g., an alkali-soluble resin) contained in the thermoplastic resin layer.
[0282] The intermediate layer may contain one or more types of resins.
[0283] From the viewpoints of oxygen barrier properties and suppressing intermixing of components that occurs between layers during formation of the photosensitive transfer material or storage of the photosensitive transfer material, the resin content in the intermediate layer is preferably 50% by mass to 100% by mass, more preferably 70% by mass to 100% by mass, even more preferably 80% by mass to 100% by mass, and particularly preferably 90% by mass to 100% by mass, relative to the total mass of the intermediate layer.
[0284] The intermediate layer may contain an additive such as a surfactant, if necessary. Examples of the surfactant include the surfactants described in the above "Photosensitive resin layer". The preferred aspects of the surfactant are the same as those described in the above "Photosensitive resin layer".
[0285] The thickness of the intermediate layer is not limited. The thickness of the intermediate layer is preferably 0.1 μm to 5 μm, and more preferably 0.5 μm to 3 μm. When the thickness of the intermediate layer is within the above range, the oxygen barrier property is not reduced, and the mixing of components between layers during the formation of the photosensitive transfer material or the storage of the photosensitive transfer material can be suppressed, and the increase in the time required to remove the intermediate layer in the development process can be suppressed. The thickness of the intermediate layer is measured by a method similar to the method for measuring the thickness of the temporary support.
[0286] The method for forming the intermediate layer is not limited. For example, the intermediate layer is formed by preparing a composition for forming an intermediate layer containing a resin and any additives, applying the composition for forming an intermediate layer to the surface of a thermoplastic resin layer or a photosensitive resin layer, and drying the applied composition for forming an intermediate layer.
[0287] In order to adjust the viscosity of the composition for forming an intermediate layer and to facilitate the formation of the intermediate layer, the composition for forming an intermediate layer preferably contains a solvent. The solvent is not limited as long as it is a solvent capable of dissolving or dispersing a resin. The solvent is preferably at least one selected from the group consisting of water and water-miscible organic solvents, and more preferably water or a mixed solvent of water and a water-miscible organic solvent. Examples of the water-miscible organic solvent include alcohols having 1 to 3 carbon atoms, acetone, ethylene glycol, and glycerin. The water-miscible organic solvent is preferably alcohols having 1 to 3 carbon atoms, and more preferably methanol or ethanol.
[0288] <<Protective film>> The photosensitive transfer material according to the present disclosure preferably includes a protective film. The photosensitive transfer material according to the present disclosure preferably includes a temporary support, a photosensitive resin layer, and a protective film in this order. The protective film is preferably the outermost layer of the photosensitive transfer material.
[0289] Examples of the protective film include resin films and paper. From the viewpoint of strength and flexibility, resin films are preferred. Examples of the resin film include polyethylene films, polypropylene films, polyethylene terephthalate films, cellulose triacetate films, polystyrene films, and polycarbonate films. Among the above, polyethylene films, polypropylene films, and polyethylene terephthalate films are preferred.
[0290] The thickness of the protective film is not limited. The thickness of the protective film is preferably 5 μm to 100 μm, and more preferably 10 μm to 50 μm. The thickness of the protective film is measured by a method similar to the method for measuring the thickness of the temporary support.
[0291] From the viewpoint of superior resolution, the arithmetic mean roughness Ra of the surface of the protective film on the photosensitive resin layer side (hereinafter sometimes simply referred to as the "surface of the protective film") is preferably 0.3 μm or less, more preferably 0.1 μm or less, and particularly preferably 0.05 μm or less. It is believed that when the arithmetic mean roughness Ra of the surface of the protective film is within the above range, the uniformity of the thickness of the photosensitive resin layer and the resin pattern formed is improved. The lower limit of the arithmetic mean roughness Ra of the protective film is preferably 0.001 μm or more.
[0292] The arithmetic mean roughness Ra of the surface of the protective film is measured by the following method. A three-dimensional optical profiler (New View7300, Zygo) is used to obtain a surface profile of the protective film under the following conditions. MetroPro ver8.3.2 Microscope Application is used as the measurement and analysis software. Next, the above analysis software is used to display the Surface Map screen, and histogram data is obtained in the Surface Map screen. The arithmetic mean roughness Ra is calculated from the obtained histogram data. In measuring the arithmetic mean roughness Ra of the surface of the protective film included in the photosensitive transfer material, the arithmetic mean roughness Ra of the surface of the protective film that appears when the protective film is peeled off from the photosensitive transfer material may be measured.
[0293] <<Relationship between temporary support, photosensitive resin layer and protective film>> In the photosensitive transfer material according to the present disclosure, it is preferred that the breaking elongation of a cured film obtained by curing the photosensitive resin layer at 120°C is 15% or more, the arithmetic mean roughness Ra of the surface of the temporary support facing the photosensitive resin layer is 50 nm or less, and the arithmetic mean roughness Ra of the surface of the protective film facing the photosensitive resin layer is 150 nm or less.
[0294] Moreover, the photosensitive transfer material according to the present disclosure preferably satisfies the following formula (R1). X×Y<1,500: Formula (R1) In the above formula (R1), X represents the breaking elongation value (%) of the cured film obtained by curing the photosensitive resin layer at 120°C, and Y represents the arithmetic mean roughness Ra value (nm) of the surface of the temporary support on the photosensitive resin layer side. It is more preferable that X×Y is 750 or less.
[0295] It is preferable that the breaking elongation at 120°C is at least twice as large as the breaking elongation at 23°C of the cured film obtained by curing the photosensitive resin layer. The breaking elongation was measured by exposing a 20μm thick photosensitive resin layer to 120mJ / cm2 of high pressure mercury lamp. 2 After curing by exposure to 400 mJ / cm 2 with a high-pressure mercury lamp 2 The cured film is then subjected to additional exposure at 145° C. for 30 minutes, and then subjected to a tensile test.
[0296] Moreover, the photosensitive transfer material according to the present disclosure preferably satisfies the following formula (R2). Y≦Z: Formula (R2) Here, in the above formula (R2), Y represents the value of the arithmetic mean roughness Ra (nm) of the surface of the temporary support facing the photosensitive resin layer, and Z represents the value of the arithmetic mean roughness Ra (nm) of the surface of the protective film facing the photosensitive resin layer.
[0297] <<Other layers>> The photosensitive transfer material according to the present disclosure may include layers other than the above-mentioned layers (hereinafter referred to as "other layers" in this paragraph). Examples of the other layers include a contrast enhancement layer (also referred to as a refractive index adjustment layer). The contrast enhancement layer is described in paragraph 0134 of International Publication No. 2018 / 179640. The other layers are described in paragraphs 0194 to 0196 of JP 2014-85643 A. The contents of these publications are incorporated herein by reference.
[0298] <<How to manufacture photosensitive transfer material>> The method for producing the photosensitive transfer material according to the present disclosure is not limited. The photosensitive transfer material is produced, for example, by utilizing the above-mentioned method for forming each layer. Hereinafter, the method for producing the photosensitive transfer material will be described with reference to FIG. 1 and FIG. 2. FIG. 1 is a schematic diagram showing the configuration of the photosensitive transfer material according to the present disclosure. FIG. 2 is a schematic diagram showing the configuration of the photosensitive transfer material according to another embodiment of the present disclosure. FIG. 3 is a schematic diagram showing the configuration of the photosensitive transfer material according to another embodiment of the present disclosure.
[0299] The photosensitive transfer material 100 shown in FIG. 1 includes a temporary support 10, a photosensitive resin layer 20, and a protective film 30 in this order. The photosensitive transfer material 100 is manufactured, for example, by the following method. A temporary support 10 having a first surface 10a and a second surface 10b on the opposite side of the first surface 10a is prepared. A photosensitive resin layer forming composition is applied onto the second surface 10b of the temporary support 10, and the applied photosensitive resin layer forming composition is dried to form a photosensitive resin layer 20. A protective film 30 is placed on the photosensitive resin layer 20. The photosensitive transfer material 100 manufactured by the above method may be wound up to produce and store a roll-shaped photosensitive transfer material 100. The roll-shaped photosensitive transfer material 100 is used, for example, for bonding to a substrate by a roll-to-roll method.
[0300] The photosensitive transfer material 110 shown in FIG. 2 includes a temporary support 11, a photosensitive resin layer 20, and a protective film 30 in this order. The temporary support 11 includes a particle-containing layer 11-1 and a substrate 11-2 in this order in the lamination direction from the temporary support 11 to the photosensitive resin layer 20. In the temporary support 11, the particle-containing layer 11-1 is disposed as the outermost layer on the first surface 11a side of the temporary support 11. In the temporary support 11, the substrate 11-2 is disposed as the outermost layer on the second surface 11b side of the temporary support 11. The photosensitive transfer material 110 is manufactured by the same method as the manufacturing method of the photosensitive transfer material 100 described above, except that the temporary support 11 is prepared instead of the temporary support 10, for example.
[0301] 3 includes, in this order, a temporary support 10, a thermoplastic resin layer 40, an intermediate layer 50, a photosensitive resin layer 20, and a protective film 30. The photosensitive transfer material 120 can be produced, for example, by forming the thermoplastic resin layer 40, the intermediate layer 50, the photosensitive resin layer 20, and the protective film 30 in this order on the second surface 10b of the temporary support in accordance with the above-mentioned method.
[0302] The method for producing the photosensitive transfer material according to the present disclosure is not limited to the above-mentioned method. For example, the photosensitive transfer material may be produced by forming each layer on a protective film instead of a temporary support.
[0303] <<Applications of photosensitive transfer materials>> The photosensitive transfer material according to the present disclosure is preferably used in various applications requiring precise microfabrication by photolithography. For example, after patterning the photosensitive resin layer, etching may be performed using the photosensitive resin layer or its cured product as a coating, or electroforming mainly using electroplating may be performed. The cured product obtained by patterning may be used as a permanent film. The cured product obtained by patterning may be used as, for example, an interlayer insulating film, a wiring protective film, or a wiring protective film having an index matching layer. The photosensitive transfer material according to the present disclosure is preferably used in, for example, a method for forming wiring in a semiconductor package, a printed circuit board, or a sensor board. The photosensitive transfer material according to the present disclosure is preferably used in, for example, a method for forming a conductive film such as a touch panel, an electromagnetic wave shielding material, and a film heater. The photosensitive transfer material according to the present disclosure is preferably used in, for example, a method for forming a structure in the fields of liquid crystal sealant, micromachines, and microelectronics.
[0304] The photosensitive transfer material according to the present disclosure may be used, for example, as a photosensitive transfer material for a wiring protective film. Examples of the layer structure of the photosensitive transfer material preferably used as the photosensitive transfer material for a wiring protective film include the following (1) and (2). (1) Temporary support / photosensitive resin layer / refractive index adjusting layer / protective film (2) Temporary support / photosensitive resin layer / protective film
[0305] The components of the photosensitive transfer material preferably used as the photosensitive transfer material for the wiring protective film will be described below. However, the components of the photosensitive transfer material preferably used as the photosensitive transfer material for the wiring protective film are not limited to the components shown below.
[0306] (Temporary Support) Examples of the temporary support include the temporary supports described above in the section "Temporary Support." Preferred aspects of the temporary support are the same as those described above in the section "Temporary Support."
[0307] (Protective film) Examples of the protective film include the protective films described above in the section "Protective Film." Preferred aspects of the protective film are the same as those described above in the section "Protective Film."
[0308] (Photosensitive resin layer) -Alkali-soluble resin- The photosensitive resin layer preferably contains an alkali-soluble resin. Examples of the alkali-soluble resin include (meth)acrylic resin, styrene resin, epoxy resin, amide resin, amide epoxy resin, alkyd resin, phenol resin, ester resin, urethane resin, epoxy acrylate resin obtained by reacting an epoxy resin with (meth)acrylic acid, and acid-modified epoxy acrylate resin obtained by reacting an epoxy acrylate resin with an acid anhydride.
[0309] One preferred embodiment of the alkali-soluble resin is a (meth)acrylic resin, which has excellent alkali developability and film formability. In this specification, the (meth)acrylic resin means a resin having a structural unit derived from a (meth)acrylic compound. The content of the structural unit derived from a (meth)acrylic compound is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more, based on the total structural units of the (meth)acrylic resin. The (meth)acrylic resin may be composed only of structural units derived from (meth)acrylic compounds, or may contain structural units derived from polymerizable monomers other than (meth)acrylic compounds. That is, the upper limit of the content of structural units derived from (meth)acrylic compounds is 100% by mass or less based on the total structural units of the (meth)acrylic resin.
[0310] Examples of the (meth)acrylic compound include (meth)acrylic acid, (meth)acrylic acid esters, (meth)acrylamide, and (meth)acrylonitrile. Examples of the (meth)acrylic acid ester include (meth)acrylic acid alkyl ester, (meth)acrylic acid tetrahydrofurfuryl ester, (meth)acrylic acid dimethylaminoethyl ester, (meth)acrylic acid diethylaminoethyl ester, (meth)acrylic acid glycidyl ester, (meth)acrylic acid benzyl ester, 2,2,2-trifluoroethyl (meth)acrylate, and 2,2,3,3-tetrafluoropropyl (meth)acrylate, and (meth)acrylic acid alkyl ester is preferred. Examples of (meth)acrylamides include acrylamides such as diacetoneacrylamide.
[0311] Examples of the (meth)acrylic acid alkyl ester include (meth)acrylic acid alkyl esters having an alkyl group having 1 to 12 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, and dodecyl (meth)acrylate. As the (meth)acrylic acid ester, a (meth)acrylic acid alkyl ester having an alkyl group having 1 to 4 carbon atoms is preferred, and methyl (meth)acrylate or ethyl (meth)acrylate is more preferred.
[0312] The (meth)acrylic resin may have a structural unit other than the structural unit derived from the (meth)acrylic compound. The polymerizable monomer that forms the above-mentioned structural unit is not particularly limited as long as it is a compound other than a (meth)acrylic compound that is copolymerizable with a (meth)acrylic compound, and examples thereof include styrene compounds that may have a substituent at the α-position or aromatic ring, such as styrene, vinyl toluene, and α-methylstyrene, vinyl alcohol esters such as acrylonitrile and vinyl-n-butyl ether, maleic acid monoesters such as maleic acid, maleic anhydride, monomethyl maleate, monoethyl maleate, and monoisopropyl maleate, fumaric acid, cinnamic acid, α-cyanocinnamic acid, itaconic acid, and crotonic acid. These polymerizable monomers may be used alone or in combination of two or more.
[0313] In order to improve the alkali developability, the (meth)acrylic resin preferably has a structural unit having an acid group. Examples of the acid group include a carboxy group, a sulfo group, a phosphoric acid group, and a phosphonic acid group. Among these, the (meth)acrylic resin more preferably has a structural unit having a carboxy group, and even more preferably has a structural unit derived from the above-mentioned (meth)acrylic acid.
[0314] The content of the structural unit having an acid group in the (meth)acrylic resin (preferably a structural unit derived from (meth)acrylic acid) is preferably 10% by mass or more based on the total mass of the (meth)acrylic resin in terms of excellent developability. The upper limit is not particularly limited, but is preferably 50% by mass or less, more preferably 40% by mass or less, in terms of excellent alkali resistance.
[0315] Moreover, the (meth)acrylic resin more preferably has a structural unit derived from the above-mentioned (meth)acrylic acid alkyl ester. The content of structural units derived from an alkyl (meth)acrylate in the (meth)acrylic resin is preferably 50% by mass to 90% by mass, more preferably 60% by mass to 90% by mass, and even more preferably 65% by mass to 90% by mass, based on all structural units of the (meth)acrylic resin.
[0316] As the (meth)acrylic resin, a resin having both a structural unit derived from (meth)acrylic acid and a structural unit derived from a (meth)acrylic acid alkyl ester is preferred, and a resin composed only of a structural unit derived from (meth)acrylic acid and a structural unit derived from a (meth)acrylic acid alkyl ester is more preferred. Furthermore, as the (meth)acrylic resin, an acrylic resin having a structural unit derived from methacrylic acid, a structural unit derived from methyl methacrylate, and a structural unit derived from ethyl acrylate is also preferred.
[0317] From the viewpoint of resolution, the (meth)acrylic resin preferably has at least one selected from the group consisting of structural units derived from methacrylic acid and structural units derived from an alkyl methacrylate ester, and preferably has both structural units derived from methacrylic acid and structural units derived from an alkyl methacrylate ester. From the viewpoint of resolution, the total content of the structural units derived from methacrylic acid and the structural units derived from methacrylic acid alkyl ester in the (meth)acrylic resin is preferably 40% by mass or more, more preferably 60% by mass or more, based on the total structural units of the (meth)acrylic resin. The upper limit is not particularly limited, and may be 100% by mass or less, and is preferably 80% by mass or less.
[0318] From the viewpoint of resolution, it is also preferable that the (meth)acrylic resin has at least one selected from the group consisting of structural units derived from methacrylic acid and structural units derived from an alkyl methacrylate ester, and at least one selected from the group consisting of structural units derived from acrylic acid and structural units derived from an alkyl acrylate ester. From the viewpoint of resolution, the total content of the structural units derived from methacrylic acid and the structural units derived from an alkyl methacrylate is preferably 60 / 40 to 80 / 20 in mass ratio to the total content of the structural units derived from acrylic acid and the structural units derived from an alkyl acrylate.
[0319] The (meth)acrylic resin preferably has an ester group at the end, in view of excellent developability of the photosensitive resin layer after transfer. The terminal portion of the (meth)acrylic resin is composed of a portion derived from the polymerization initiator used in the synthesis. The (meth)acrylic resin having an ester group at the terminal can be synthesized by using a polymerization initiator that generates a radical having an ester group.
[0320] Moreover, the alkali-soluble resin is preferably an alkali-soluble resin having an acid value of 60 mgKOH / g or more, for example, from the viewpoint of developability. Moreover, the alkali-soluble resin is more preferably a resin having a carboxy group with an acid value of 60 mgKOH / g or more (so-called carboxy group-containing resin), and even more preferably a (meth)acrylic resin having a carboxy group with an acid value of 60 mgKOH / g or more (so-called carboxy group-containing (meth)acrylic resin), from the viewpoint of, for example, being thermally crosslinked with the crosslinking component by heating and easily forming a strong film. When the alkali-soluble resin has a carboxy group, the three-dimensional crosslinking density can be increased by, for example, adding a thermally crosslinkable compound such as a blocked isocyanate compound to thermally crosslink the resin. In addition, when the carboxy group of the resin having a carboxy group is dehydrated and hydrophobized, the humidity and heat resistance can be improved.
[0321] The carboxyl group-containing (meth)acrylic resin having an acid value of 60 mgKOH / g or more is not particularly limited as long as it satisfies the above-mentioned acid value condition, and can be appropriately selected from known (meth)acrylic resins. For example, among the polymers described in paragraph 0025 of JP-A-2011-095716, carboxyl group-containing acrylic resins having an acid value of 60 mgKOH / g or more, and among the polymers described in paragraphs 0033 to 0052 of JP-A-2010-237589, carboxyl group-containing acrylic resins having an acid value of 60 mgKOH / g or more can be preferably used.
[0322] Another preferred embodiment of the alkali-soluble resin is a styrene-acrylic copolymer. In this specification, the styrene-acrylic copolymer refers to a resin having a structural unit derived from a styrene compound and a structural unit derived from a (meth)acrylic compound, and the total content of the structural unit derived from the styrene compound and the structural unit derived from the (meth)acrylic compound is preferably 30% by mass or more, more preferably 50% by mass or more, based on the total structural units of the copolymer. The content of the structural units derived from a styrene compound is preferably 1% by mass or more, more preferably 5% by mass or more, and even more preferably 5 to 80% by mass, based on all the structural units of the copolymer. The content of the structural units derived from the (meth)acrylic compound is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 20% by mass to 95% by mass, based on all structural units of the copolymer.
[0323] From the viewpoint of moisture permeability and strength of the resulting cured film, the alkali-soluble resin preferably has an aromatic ring structure, and more preferably has a constituent unit having an aromatic ring structure. Examples of monomers that form structural units having an aromatic ring structure include styrene compounds such as styrene, tert-butoxystyrene, methylstyrene, and α-methylstyrene, as well as benzyl (meth)acrylate. Of these, styrene compounds are preferred, and styrene is more preferred. From the viewpoint of moisture permeability and strength of the resulting cured film, the alkali-soluble resin more preferably has a constitutional unit represented by the following formula (S) (a constitutional unit derived from styrene).
[0324] [ka]
[0325] When the alkali-soluble resin has a structural unit having an aromatic ring structure, the content of the structural unit having an aromatic ring structure is, from the viewpoint of moisture permeability and strength of the obtained cured film, preferably from 5% by mass to 90% by mass, more preferably from 10% by mass to 70% by mass, and further preferably from 20% by mass to 60% by mass, based on the total structural units of the alkali-soluble resin. Furthermore, the content of the structural unit having an aromatic ring structure in the alkali-soluble resin is, from the viewpoint of moisture permeability and strength of the obtained cured film, preferably 5 mol % to 70 mol %, more preferably 10 mol % to 60 mol %, and even more preferably 20 mol % to 60 mol %, based on all the structural units of the alkali-soluble resin. Furthermore, the content of the structural unit represented by the above formula (S) in the alkali-soluble resin is, from the viewpoint of moisture permeability and strength of the obtained cured film, preferably 5 mol % to 70 mol %, more preferably 10 mol % to 60 mol %, even more preferably 20 mol % to 60 mol %, and particularly preferably 20 mol % to 50 mol %, based on all structural units of the alkali-soluble resin. In this specification, when the content of the "structural unit" is specified by a molar ratio, the "structural unit" is synonymous with the "monomer unit". In addition, in this specification, the "monomer unit" may be modified after polymerization by a polymer reaction or the like. The same applies hereinafter.
[0326] The alkali-soluble resin preferably has an aliphatic hydrocarbon ring structure from the viewpoint of suppression of development residue, strength of the obtained cured film, and adhesion of the obtained uncured film.That is, the alkali-soluble resin preferably has a structural unit having an aliphatic hydrocarbon ring structure.In particular, the alkali-soluble resin more preferably has a ring structure in which two or more aliphatic hydrocarbon rings are condensed.
[0327] Examples of the ring that constitutes the aliphatic hydrocarbon ring structure in the structural unit having an aliphatic hydrocarbon ring structure include a tricyclodecane ring, a cyclohexane ring, a cyclopentane ring, a norbornane ring, and an isoborone ring. Among these, from the viewpoints of suppression of development residues, strength of the resulting cured film, and adhesion of the resulting uncured film, a ring in which two or more aliphatic hydrocarbon rings are condensed is preferred, and a tetrahydrodicyclopentadiene ring (tricyclo[5.2.1.0 2,6 ]decane ring) is more preferred. Examples of monomers that form a structural unit having an aliphatic hydrocarbon ring structure include dicyclopentanyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate. Moreover, from the viewpoints of suppressing development residues, the strength of the resulting cured film, and the adhesion of the resulting uncured film, it is more preferable that the alkali-soluble resin has a constitutional unit represented by the following formula (Cy), and it is even more preferable that the alkali-soluble resin has a constitutional unit represented by the above formula (S) and a constitutional unit represented by the following formula (Cy).
[0328] [ka]
[0329] In the formula (Cy), RM represents a hydrogen atom or a methyl group, R Cy represents a monovalent group having an aliphatic hydrocarbon ring structure.
[0330] R in formula (Cy) M is preferably a methyl group. R in formula (Cy) Cy From the viewpoints of suppression of development residues, strength of the resulting cured film, and adhesion of the resulting uncured film, is preferably a monovalent group having an aliphatic hydrocarbon ring structure having 5 to 20 carbon atoms, more preferably a monovalent group having an aliphatic hydrocarbon ring structure having 6 to 16 carbon atoms, and even more preferably a monovalent group having an aliphatic hydrocarbon ring structure having 8 to 14 carbon atoms. R in formula (Cy) Cy The aliphatic hydrocarbon ring structure in may be a monocyclic structure or a polycyclic structure. In addition, R in formula (Cy) Cy From the viewpoints of suppression of development residues, strength of the resulting cured film, and adhesion of the resulting uncured film, the aliphatic hydrocarbon ring structure in is preferably a cyclopentane ring structure, a cyclohexane ring structure, a tetrahydrodicyclopentadiene ring structure, a norbornane ring structure, or an isoborone ring structure, more preferably a cyclohexane ring structure or a tetrahydrodicyclopentadiene ring structure, and even more preferably a tetrahydrodicyclopentadiene ring structure. Furthermore, R in formula (Cy) Cy From the viewpoints of suppression of development residues, strength of the resulting cured film, and adhesion of the resulting uncured film, the aliphatic hydrocarbon ring structure in is preferably a ring structure in which two or more aliphatic hydrocarbon rings are condensed, and more preferably a ring in which two to four aliphatic hydrocarbon rings are condensed. Furthermore, R in formula (Cy) CyFrom the viewpoints of suppression of development residues, strength of the resulting cured film, and adhesion of the resulting uncured film, is preferably a group in which the oxygen atom of -C(=O)O- in formula (Cy) is directly bonded to an aliphatic hydrocarbon ring structure, i.e., an aliphatic hydrocarbon ring group, more preferably a cyclohexyl group or a dicyclopentanyl group, and even more preferably a dicyclopentanyl group.
[0331] The alkali-soluble resin may have one type of structural unit having an aliphatic hydrocarbon ring structure, or may have two or more types of structural units having an aliphatic hydrocarbon ring structure. When the alkali-soluble resin has a structural unit having an aliphatic hydrocarbon ring structure, the content of the structural unit having an aliphatic hydrocarbon ring structure is, from the viewpoints of suppressing development residues, the strength of the resulting cured film, and the adhesion of the resulting uncured film, preferably from 5% by mass to 90% by mass, more preferably from 10% by mass to 80% by mass, and even more preferably from 20% by mass to 70% by mass, based on the total structural units of the alkali-soluble resin. Furthermore, the content of the structural unit having an aliphatic hydrocarbon ring structure in the alkali-soluble resin is, from the viewpoints of suppressing development residues, the strength of the resulting cured film, and the adhesion of the resulting uncured film, preferably 5 mol % to 70 mol %, more preferably 10 mol % to 60 mol %, and even more preferably 20 mol % to 50 mol %, based on the total structural units of the alkali-soluble resin. Furthermore, the content of the structural unit represented by the above formula (Cy) in the alkali-soluble resin is, from the viewpoints of suppressing development residues, the strength of the resulting cured film, and the adhesion of the resulting uncured film, preferably 5 mol % to 70 mol %, more preferably 10 mol % to 60 mol %, and even more preferably 20 mol % to 50 mol %, based on the total structural units of the alkali-soluble resin.
[0332] When the alkali-soluble resin has a structural unit having an aromatic ring structure and a structural unit having an aliphatic hydrocarbon ring structure, the total content of the structural units having an aromatic ring structure and the structural units having an aliphatic hydrocarbon ring structure is, from the viewpoints of suppressing development residues, the strength of the resulting cured film, and the adhesion of the resulting uncured film, preferably from 10% by mass to 90% by mass, more preferably from 20% by mass to 80% by mass, and even more preferably from 40% by mass to 75% by mass, based on the total structural units of the alkali-soluble resin. Furthermore, the total content of the structural units having an aromatic ring structure and the structural units having an aliphatic hydrocarbon ring structure in the alkali-soluble resin is, from the viewpoints of suppressing development residues, the strength of the resulting cured film, and the adhesion of the resulting uncured film, preferably from 10 mol % to 80 mol %, more preferably from 20 mol % to 70 mol %, and even more preferably from 40 mol % to 60 mol %, based on the total structural units of the alkali-soluble resin. Furthermore, the total content of the structural units represented by the above formula (S) and the structural units represented by the above formula (Cy) in the alkali-soluble resin is, from the viewpoints of suppressing development residues, the strength of the resulting cured film, and the adhesion of the resulting uncured film, preferably from 10 mol % to 80 mol %, more preferably from 20 mol % to 70 mol %, and even more preferably from 40 mol % to 60 mol %, relative to the total structural units of the alkali-soluble resin. Furthermore, in the alkali-soluble resin, the molar amount nS of the constitutional unit represented by the above formula (S) and the molar amount nCy of the constitutional unit represented by the above formula (Cy) preferably satisfy the relationship shown in the following formula (SCy), more preferably satisfy the following formula (SCy-1), and even more preferably satisfy the following formula (SCy-2), from the viewpoints of suppression of development residues, the strength of the obtained cured film, and the adhesion of the obtained uncured film. 0.2≦nS / (nS+nCy)≦0.8: Formula (SCy) 0.30≦nS / (nS+nCy)≦0.75: Formula (SCy-1) 0.40≦nS / (nS+nCy)≦0.70: Formula (SCy-2)
[0333] From the viewpoints of developability and adhesion to a substrate, the alkali-soluble resin preferably has a structural unit having an acid group. Examples of the acid group include a carboxy group, a sulfo group, a phosphonic acid group, and a phosphoric acid group, with the carboxy group being preferred. As the structural unit having an acid group, a structural unit derived from (meth)acrylic acid shown below is preferred, and a structural unit derived from methacrylic acid is more preferred.
[0334] [ka]
[0335] The alkali-soluble resin may have one type of structural unit having an acid group, or may have two or more types of structural units having an acid group. When the alkali-soluble resin has a structural unit having an acid group, the content of the structural unit having an acid group is, from the viewpoints of developability and adhesion to a substrate, preferably 5% by mass to 50% by mass, more preferably 5% by mass to 40% by mass, and even more preferably 10% by mass to 30% by mass, based on the total structural units of the alkali-soluble resin. Furthermore, the content of the structural units having an acid group in the alkali-soluble resin is preferably 5 mol % to 70 mol %, more preferably 10 mol % to 50 mol %, and even more preferably 20 mol % to 40 mol %, based on the total structural units of the alkali-soluble resin, from the viewpoints of developability and adhesion to a substrate. Furthermore, the content of the structural units derived from (meth)acrylic acid in the alkali-soluble resin is preferably 5 mol % to 70 mol %, more preferably 10 mol % to 50 mol %, and even more preferably 20 mol % to 40 mol %, based on the total structural units of the alkali-soluble resin, from the viewpoints of developability and adhesion to a substrate.
[0336] From the viewpoints of curability and strength of the resulting cured film, the alkali-soluble resin preferably has a reactive group, and more preferably has a structural unit having a reactive group. The reactive group is preferably a radical polymerizable group, more preferably an ethylenically unsaturated group. In addition, when the alkali-soluble resin has an ethylenically unsaturated group, the alkali-soluble resin preferably has a structural unit having an ethylenically unsaturated group in a side chain. In this specification, the term "main chain" refers to the relatively longest bond chain in the molecule of the polymer compound that constitutes the resin, and the term "side chain" refers to an atomic group branching off from the main chain. The ethylenically unsaturated group is more preferably an allyl group or a (meth)acryloxy group. Examples of structural units having a reactive group include, but are not limited to, those shown below.
[0337] [ka]
[0338] The alkali-soluble resin may have one type of structural unit having a reactive group, or may have two or more types of structural units having a reactive group. When the alkali-soluble resin has a structural unit having a reactive group, the content of the structural unit having a reactive group is, from the viewpoints of curability and strength of the obtained cured film, preferably 5% by mass to 70% by mass, more preferably 10% by mass to 50% by mass, and even more preferably 20% by mass to 40% by mass, based on the total structural units of the alkali-soluble resin. Furthermore, the content of the structural unit having a reactive group in the alkali-soluble resin is, from the viewpoints of curability and strength of the resulting cured film, preferably 5 mol % to 70 mol %, more preferably 10 mol % to 60 mol %, and even more preferably 20 mol % to 50 mol %, based on the total structural units of the alkali-soluble resin.
[0339] Examples of a method for introducing a reactive group into an alkali-soluble resin include a method in which a functional group such as a hydroxy group, a carboxy group, a primary amino group, a secondary amino group, an acetoacetyl group, or a sulfo group is reacted with a compound such as an epoxy compound, a blocked isocyanate compound, an isocyanate compound, a vinyl sulfone compound, an aldehyde compound, a methylol compound, or a carboxylic acid anhydride. A preferred example of a method for introducing a reactive group into an alkali-soluble resin is to synthesize a polymer having a carboxy group by polymerization, and then react a part of the carboxy group of the obtained resin with glycidyl (meth)acrylate by a polymer reaction to introduce a (meth)acryloxy group into the polymer. By this method, an alkali-soluble resin having a (meth)acryloxy group in the side chain can be obtained. The polymerization reaction is preferably carried out at a temperature of 70°C to 100°C, and more preferably at a temperature of 80°C to 90°C. The polymerization initiator used in the polymerization reaction is preferably an azo-based initiator, and more preferably V-601 (trade name) or V-65 (trade name) manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., for example. The polymer reaction is preferably carried out at a temperature of 80°C to 110°C. In the polymer reaction, a catalyst such as an ammonium salt is preferably used.
[0340] As the alkali-soluble resin, the resins shown below are preferred in terms of achieving better effects in the present disclosure. The content ratios (a to d) of each of the structural units shown below and the weight average molecular weight Mw can be appropriately changed depending on the purpose.
[0341] [ka]
[0342] In the above resin, it is preferable that a is 20% by mass to 60% by mass, b is 10% by mass to 50% by mass, c is 5.0% by mass to 25% by mass, and d is 10% by mass to 50% by mass.
[0343] [ka]
[0344] In the above resin, it is preferable that a is 20% by mass to 60% by mass, b is 10% by mass to 50% by mass, c is 5.0% by mass to 25% by mass, and d is 10% by mass to 50% by mass.
[0345] [ka]
[0346] In the above resin, it is preferable that a is 30% to 65% by mass, b is 1.0% to 20% by mass, c is 5.0% to 25% by mass, and d is 10% to 50% by mass.
[0347] [ka]
[0348] In the above resin, it is preferable that a is 1.0% by mass to 20% by mass, b is 20% by mass to 60% by mass, c is 5.0% by mass to 25% by mass, and d is 10% by mass to 50% by mass.
[0349] The alkali-soluble resin may also contain a polymer having a structural unit with a carboxylic acid anhydride structure (hereinafter, also referred to as "polymer X"). The carboxylic acid anhydride structure may be either a chain carboxylic acid anhydride structure or a cyclic carboxylic acid anhydride structure, but is preferably a cyclic carboxylic acid anhydride structure. The ring of the cyclic carboxylic acid anhydride structure is preferably a 5- to 7-membered ring, more preferably a 5- or 6-membered ring, and even more preferably a 5-membered ring.
[0350] The structural unit having a carboxylic acid anhydride structure is preferably a structural unit containing a divalent group obtained by removing two hydrogen atoms from a compound represented by the following formula P-1 in its main chain, or a structural unit in which a monovalent group obtained by removing one hydrogen atom from a compound represented by the following formula P-1 is bonded to the main chain directly or via a divalent linking group.
[0351] [ka]
[0352] In formula P-1, R A1a represents a substituent, n 1a RA1a may be the same or different, Z 1a represents a divalent group forming a ring containing -C(=O)-OC(=O)-, n 1a represents an integer greater than or equal to 0.
[0353] R A1a The substituent represented by the formula (I) is, for example, an alkyl group. Z 1a As the alkylene group, an alkylene group having 2 to 4 carbon atoms is preferable, an alkylene group having 2 or 3 carbon atoms is more preferable, and an alkylene group having 2 carbon atoms is even more preferable. n 1a represents an integer equal to or greater than 0. 1a When represents an alkylene group having 2 to 4 carbon atoms, n 1a is preferably an integer of 0 to 4, more preferably an integer of 0 to 2, and even more preferably 0. n 1a If represents an integer of 2 or more, there are multiple R A1a may be the same or different. In addition, if there are multiple R A1a may be bonded to each other to form a ring, but preferably do not bond to each other to form a ring.
[0354] As a structural unit having a carboxylic acid anhydride structure, a structural unit derived from an unsaturated carboxylic acid anhydride is preferable, a structural unit derived from an unsaturated cyclic carboxylic acid anhydride is more preferable, a structural unit derived from an unsaturated aliphatic cyclic carboxylic acid anhydride is even more preferable, a structural unit derived from maleic anhydride or itaconic anhydride is particularly preferable, and a structural unit derived from maleic anhydride is most preferable.
[0355] Specific examples of structural units having a carboxylic acid anhydride structure are given below, but the structural units having a carboxylic acid anhydride structure are not limited to these specific examples. In the following structural units, Rx represents a hydrogen atom, a methyl group, a CH2OH group, or a CF3 group, and Me represents a methyl group.
[0356] [ka]
[0357] [ka]
[0358] The structural unit having a carboxylic acid anhydride structure in the polymer X may be of one type alone, or of two or more types.
[0359] The total content of the structural units having a carboxylic acid anhydride structure relative to all the structural units of polymer X is preferably from 0 mol % to 60 mol %, more preferably from 5 mol % to 40 mol %, and even more preferably from 10 mol % to 35 mol %.
[0360] The photosensitive resin layer may contain only one type of polymer X, or may contain two or more types. When the photosensitive resin layer contains polymer X, from the viewpoints of resolution and developability, the content of polymer X is preferably 0.1% by mass to 30% by mass, more preferably 0.2% by mass to 20% by mass, even more preferably 0.5% by mass to 20% by mass, and still more preferably 1% by mass to 20% by mass, based on the total mass of the photosensitive resin layer.
[0361] The weight average molecular weight (Mw) of the alkali-soluble resin is preferably 5,000 or more, more preferably 10,000 or more, further preferably from 10,000 to 50,000, and particularly preferably from 20,000 to 30,000, from the viewpoint of improving resolution and developability.
[0362] The acid value of the alkali-soluble resin is preferably from 10 mgKOH / g to 200 mgKOH / g, more preferably from 60 mgKOH / g to 200 mgKOH / g, further preferably from 60 mgKOH / g to 150 mgKOH / g, and particularly preferably from 60 mgKOH / g to 110 mgKOH / g. The acid value of the alkali-soluble resin is a value measured according to the method described in JIS K0070:1992. The dispersity (weight average molecular weight / number average molecular weight) of the alkali-soluble resin is preferably from 1.0 to 6.0, more preferably from 1.0 to 5.0, further preferably from 1.0 to 4.0, and particularly preferably from 1.0 to 3.0, from the viewpoint of developability.
[0363] The photosensitive resin layer may contain only one type of alkali-soluble resin, or may contain two or more types of alkali-soluble resin. From the viewpoints of photosensitivity, resolution and developability, the content of the alkali-soluble resin is preferably 10% by mass to 90% by mass, more preferably 20% by mass to 80% by mass, and even more preferably 30% by mass to 70% by mass, relative to the total mass of the photosensitive resin layer.
[0364] -Polymerizable compound- The photosensitive resin layer may contain a polymerizable compound. The polymerizable compound is a compound having a polymerizable group. Examples of the polymerizable group include a radical polymerizable group and a cationic polymerizable group, and the radical polymerizable group is preferable.
[0365] The polymerizable compound preferably contains a polymerizable compound having an ethylenically unsaturated group (hereinafter, also simply referred to as an "ethylenically unsaturated compound"). The ethylenically unsaturated group is preferably a (meth)acryloxy group. The ethylenically unsaturated compound in this specification is a compound other than the above-mentioned binder polymer, and preferably has a molecular weight of less than 5,000. The preferred embodiments of the ethylenically unsaturated compound are the same as those described above in the section "Photosensitive resin layer."
[0366] One preferred embodiment of the ethylenically unsaturated compound is a compound represented by the following formula (M) (also simply referred to as "compound M"). Q 2 -R 1 -Q 1 :Formula(M) In formula (M), Q 1 and Q 2each independently represents a (meth)acryloyloxy group; R 1 represents a divalent linking group having a chain structure.
[0367] Q in formula (M) 1 and Q 2 From the viewpoint of ease of synthesis, Q 1 and Q 2 are preferably the same group. In addition, Q in formula (M) 1 and Q 2 is preferably an acryloyloxy group from the viewpoint of reactivity. R in formula (M) 1 From the viewpoints of suppression of development residues, rust prevention, and bending resistance of the resulting cured film, the alkylene group, alkyleneoxyalkylene group (-L 1 -OL 1 -), or a polyalkyleneoxyalkylene group (-(L 1 -O) p -L 1 -) is preferred, a hydrocarbon group having 2 to 20 carbon atoms or a polyalkyleneoxyalkylene group is more preferred, an alkylene group having 4 to 20 carbon atoms is further preferred, and a linear alkylene group having 6 to 18 carbon atoms is particularly preferred. The hydrocarbon group may have a chain structure at least in a portion thereof, and the portion other than the chain structure is not particularly limited and may be, for example, a branched, cyclic, or linear alkylene group having 1 to 5 carbon atoms, an arylene group, an ether bond, or a combination thereof. An alkylene group or a group combining two or more alkylene groups and one or more arylene groups is preferable, an alkylene group is more preferable, and a linear alkylene group is even more preferable. In addition, the above L 1 each independently represents an alkylene group, preferably an ethylene group, a propylene group, or a butylene group, more preferably an ethylene group or a 1,2-propylene group. p represents an integer of 2 or more, and is preferably an integer of 2 to 10.
[0368] In addition, Q in compound M 1 and Q2 The number of atoms in the shortest linking chain between and is preferably 3 to 50, more preferably 4 to 40, even more preferably 6 to 20, and particularly preferably 8 to 12, from the viewpoints of suppression of development residues, rust prevention, and bending resistance of the resulting cured film. As used herein, "Q 1 and Q 2 The number of atoms in the shortest chain connecting Q 1 R to be connected 1 Q from atoms in 2 R to be connected 1 is the shortest number of atoms that can connect to an atom in
[0369] Specific examples of compound M include 1,3-butanediol di(meth)acrylate, tetramethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,7-heptanediol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, hydrogenated bisphenol A di(meth)acrylate, hydrogenated bisphenol F di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, poly(ethylene glycol / propylene glycol) di(meth)acrylate, and polybutylene glycol di(meth)acrylate. The above ester monomers can also be used as a mixture. Among the above compounds, from the viewpoints of suppression of development residues, rust prevention, and bending resistance of the obtained cured film, at least one compound selected from the group consisting of 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, and neopentyl glycol di(meth)acrylate is preferred, at least one compound selected from the group consisting of 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and 1,10-decanediol di(meth)acrylate is more preferred, and at least one compound selected from the group consisting of 1,9-nonanediol di(meth)acrylate and 1,10-decanediol di(meth)acrylate is even more preferred.
[0370] One of the preferred embodiments of the ethylenically unsaturated compound is a di- or higher functional ethylenically unsaturated compound. In this specification, the term "di- or higher functional ethylenically unsaturated compound" means a compound having two or more ethylenically unsaturated groups in one molecule. As the ethylenically unsaturated group in the ethylenically unsaturated compound, a (meth)acryloyl group is preferred. As the ethylenically unsaturated compound, a (meth)acrylate compound is preferred.
[0371] The difunctional ethylenically unsaturated compound is not particularly limited and can be appropriately selected from known compounds. Examples of the difunctional ethylenically unsaturated compound other than the compound M include tricyclodecane dimethanol di(meth)acrylate and 1,4-cyclohexanediol di(meth)acrylate.
[0372] Commercially available bifunctional ethylenically unsaturated compounds include tricyclodecane dimethanol diacrylate (trade name: NK Ester A-DCP, manufactured by Shin-Nakamura Chemical Co., Ltd.), tricyclodecane dimenanol dimethacrylate (trade name: NK Ester DCP, manufactured by Shin-Nakamura Chemical Co., Ltd.), 1,9-nonanediol diacrylate (trade name: NK Ester A-NOD-N, manufactured by Shin-Nakamura Chemical Co., Ltd.), and 1,6-hexanediol diacrylate (trade name: NK Ester A-HD-N, manufactured by Shin-Nakamura Chemical Co., Ltd.).
[0373] The tri- or higher functional ethylenically unsaturated compound is not particularly limited and can be appropriately selected from known compounds. Examples of the tri- or higher functional ethylenically unsaturated compound include dipentaerythritol (tri / tetra / penta / hexa)(meth)acrylate, pentaerythritol (tri / tetra)(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, isocyanuric acid (meth)acrylate, and (meth)acrylate compounds having a glycerin tri(meth)acrylate skeleton.
[0374] Examples of the ethylenically unsaturated compound include caprolactone-modified (meth)acrylate compounds (KAYARAD (registered trademark) DPCA-20 manufactured by Nippon Kayaku Co., Ltd., A-9300-1CL manufactured by Shin-Nakamura Chemical Co., Ltd., etc.), alkylene oxide-modified (meth)acrylate compounds (KAYARAD (registered trademark) RP-1040 manufactured by Nippon Kayaku Co., Ltd., ATM-35E and A-9300 manufactured by Shin-Nakamura Chemical Co., Ltd., EBECRYL (registered trademark) 135 manufactured by Daicel-Allnex Corporation, etc.), and ethoxylated glycerin triacrylate (NK Ester A-GLY-9E manufactured by Shin-Nakamura Chemical Co., Ltd., etc.).
[0375] The ethylenically unsaturated compounds also include urethane (meth)acrylate compounds. Examples of the urethane (meth)acrylate include urethane di(meth)acrylate, such as propylene oxide modified urethane di(meth)acrylate, and ethylene oxide and propylene oxide modified urethane di(meth)acrylate. In addition, the urethane (meth)acrylate may be a trifunctional or higher urethane (meth)acrylate. The lower limit of the number of functional groups is more preferably 6 or more, and even more preferably 8 or more. The upper limit of the number of functional groups is preferably 20 or less. Examples of trifunctional or higher urethane (meth)acrylates include 8UX-015A (manufactured by Taisei Fine Chemical Co., Ltd.), UA-32P (manufactured by Shin-Nakamura Chemical Co., Ltd.), U-15HA (manufactured by Shin-Nakamura Chemical Co., Ltd.), UA-1100H (manufactured by Shin-Nakamura Chemical Co., Ltd.), AH-600 (product name) manufactured by Kyoeisha Chemical Co., Ltd., and UA-306H, UA-306T, UA-306I, UA-510H, and UX-5000 (all manufactured by Nippon Kayaku Co., Ltd.).
[0376] One of the preferred embodiments of the ethylenically unsaturated compound is an ethylenically unsaturated compound having an acid group. Acid groups include phosphate groups, sulfo groups, and carboxy groups. Among these, the acid group is preferably a carboxy group. Examples of the ethylenically unsaturated compound having an acid group include a trifunctional or tetrafunctional ethylenically unsaturated compound having an acid group [a carboxy group has been introduced into a pentaerythritol tri- or tetraacrylate (PETA) skeleton (acid value: 80 mg KOH / g to 120 mg KOH / g)], a pentafunctional or hexafunctional ethylenically unsaturated compound having an acid group (a carboxy group has been introduced into a dipentaerythritol penta- or hexaacrylate (DPHA) skeleton (acid value: 25 mg KOH / g to 70 mg KOH / g)], and the like. These trifunctional or higher ethylenically unsaturated compounds having an acid group may be used in combination with a difunctional ethylenically unsaturated compound having an acid group, if necessary.
[0377] The ethylenically unsaturated compound having an acid group is preferably at least one selected from the group consisting of di- or higher functional ethylenically unsaturated compounds having a carboxy group and carboxylic acid anhydrides thereof. When the ethylenically unsaturated compound having an acid group is at least one selected from the group consisting of di- or higher functional ethylenically unsaturated compounds having a carboxy group and carboxylic acid anhydrides thereof, the developability and film strength are further improved. The di- or higher functional ethylenically unsaturated compound having a carboxy group is not particularly limited and can be appropriately selected from known compounds. Examples of difunctional or higher ethylenically unsaturated compounds having a carboxy group include ARONIX (registered trademark) TO-2349 (manufactured by Toagosei Co., Ltd.), ARONIX (registered trademark) M-520 (manufactured by Toagosei Co., Ltd.), and ARONIX (registered trademark) M-510 (manufactured by Toagosei Co., Ltd.).
[0378] As the ethylenically unsaturated compound having an acid group, the polymerizable compounds having an acid group described in paragraphs 0025 to 0030 of JP-A No. 2004-239942 are preferred, and the contents of this publication are incorporated herein by reference.
[0379] Examples of the ethylenically unsaturated compound include compounds obtained by reacting a polyhydric alcohol with an α,β-unsaturated carboxylic acid, compounds obtained by reacting a glycidyl group-containing compound with an α,β-unsaturated carboxylic acid, urethane monomers such as (meth)acrylate compounds having a urethane bond, phthalic acid compounds such as γ-chloro-β-hydroxypropyl-β'-(meth)acryloyloxyethyl-o-phthalate, β-hydroxyethyl-β'-(meth)acryloyloxyethyl-o-phthalate, and β-hydroxypropyl-β'-(meth)acryloyloxyethyl-o-phthalate, and (meth)acrylic acid alkyl esters. These may be used alone or in combination of two or more.
[0380] Examples of compounds obtained by reacting a polyhydric alcohol with an α,β-unsaturated carboxylic acid include bisphenol A-based (meth)acrylate compounds such as 2,2-bis(4-((meth)acryloxypolyethoxy)phenyl)propane, 2,2-bis(4-((meth)acryloxypolypropoxy)phenyl)propane, and 2,2-bis(4-((meth)acryloxypolyethoxypolypropoxy)phenyl)propane; polyethylene glycol di(meth)acrylates having 2 to 14 ethylene oxide groups; polypropylene glycol di(meth)acrylates having 2 to 14 propylene oxide groups; polyethylene polypropylene glycol di(meth)acrylates having 2 to 14 ethylene oxide groups and 2 to 14 propylene oxide groups; trimethylolpropane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane ethoxy tri(meth)acrylate, trimethylolpropane diethoxy tri(meth)acrylate, trimethylolpropane triethoxy tri(meth)acrylate, trimethylolpropane tetraethoxy tri(meth)acrylate, trimethylolpropane pentaethoxy tri(meth)acrylate, di(trimethylolpropane) tetraacrylate, tetramethylolmethane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate. Among these, ethylenically unsaturated compounds having a tetramethylolmethane structure or a trimethylolpropane structure are preferred, and tetramethylolmethane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, trimethylolpropane tri(meth)acrylate, or di(trimethylolpropane)tetraacrylate are more preferred.
[0381] Examples of the ethylenically unsaturated compound include caprolactone-modified ethylenically unsaturated compounds (e.g., KAYARAD (registered trademark) DPCA-20 manufactured by Nippon Kayaku Co., Ltd., A-9300-1CL manufactured by Shin-Nakamura Chemical Co., Ltd., etc.), alkylene oxide-modified ethylenically unsaturated compounds (e.g., KAYARAD RP-1040 manufactured by Nippon Kayaku Co., Ltd., ATM-35E and A-9300 manufactured by Shin-Nakamura Chemical Co., Ltd., EBECRYL (registered trademark) 135 manufactured by Daicel-Allnex Corporation, etc.), and ethoxylated glycerin triacrylate (A-GLY-9E manufactured by Shin-Nakamura Chemical Co., Ltd., etc.).
[0382] As the ethylenically unsaturated compound, from the viewpoint of excellent developability, those containing an ester bond are also preferred. The ethylenically unsaturated compound containing an ester bond is not particularly limited as long as it contains an ester bond in the molecule, but from the viewpoint of excellent curability and developability, an ethylenically unsaturated compound having a tetramethylolmethane structure or a trimethylolpropane structure is preferred, and tetramethylolmethane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, trimethylolpropane tri(meth)acrylate, or di(trimethylolpropane)tetraacrylate is more preferred. From the viewpoint of providing reliability, the ethylenically unsaturated compound preferably contains an ethylenically unsaturated compound having an aliphatic group having 6 to 20 carbon atoms and the above-mentioned ethylenically unsaturated compound having a tetramethylolmethane structure or a trimethylolpropane structure. Examples of ethylenically unsaturated compounds having an aliphatic structure having 6 or more carbon atoms include 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, and tricyclodecane dimethanol di(meth)acrylate.
[0383] One of the preferred embodiments of the ethylenically unsaturated compound is an ethylenically unsaturated compound having an aliphatic hydrocarbon ring structure (preferably a difunctional ethylenically unsaturated compound). The above-mentioned ethylenically unsaturated compound is preferably an ethylenically unsaturated compound having a ring structure in which two or more aliphatic hydrocarbon rings are condensed (preferably a structure selected from the group consisting of a tricyclodecane structure and a tricyclodecene structure), more preferably a bifunctional ethylenically unsaturated compound having a ring structure in which two or more aliphatic hydrocarbon rings are condensed, and even more preferably tricyclodecane dimethanol di(meth)acrylate. As the aliphatic hydrocarbon ring structure, from the viewpoints of the moisture permeability and bending resistance of the obtained cured film, and the adhesion of the obtained uncured film, a cyclopentane structure, a cyclohexane structure, a tricyclodecane structure, a tricyclodecene structure, a norbornane structure, or an isoborone structure is preferred.
[0384] The molecular weight of the ethylenically unsaturated compound is preferably from 200 to 3,000, more preferably from 250 to 2,600, further preferably from 280 to 2,200, and particularly preferably from 300 to 2,200. Among the ethylenically unsaturated compounds contained in the photosensitive resin layer, the content ratio of ethylenically unsaturated compounds having a molecular weight of 300 or less is preferably 30 mass% or less, more preferably 25 mass% or less, and even more preferably 20 mass% or less, based on the content of all ethylenically unsaturated compounds contained in the photosensitive resin layer.
[0385] As one of the preferred embodiments of the photosensitive resin layer, the photosensitive resin layer preferably contains a difunctional or higher ethylenically unsaturated compound, more preferably contains a trifunctional or higher ethylenically unsaturated compound, and even more preferably contains a trifunctional or tetrafunctional ethylenically unsaturated compound.
[0386] In addition, as one of the preferred embodiments of the photosensitive resin layer, the photosensitive resin layer preferably contains a bifunctional ethylenically unsaturated compound having an aliphatic hydrocarbon ring structure and an alkali-soluble resin having a structural unit having an aliphatic hydrocarbon ring.
[0387] In addition, as one of the preferred embodiments of the photosensitive resin layer, the photosensitive resin layer preferably contains a compound represented by formula (M) and an ethylenically unsaturated compound having an acid group, more preferably contains 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, and a polyfunctional ethylenically unsaturated compound having a carboxylic acid group, and even more preferably contains 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, and a succinic acid modified product of dipentaerythritol pentaacrylate.
[0388] In addition, as one of the preferred embodiments of the photosensitive resin layer, the photosensitive resin layer preferably contains a compound represented by formula (M), an ethylenically unsaturated compound having an acid group, and a thermally crosslinkable compound described later, and more preferably contains a compound represented by formula (M), an ethylenically unsaturated compound having an acid group, and a blocked isocyanate compound described later.
[0389] In addition, as one of the preferred embodiments of the photosensitive resin layer, from the viewpoints of suppressing development residues and rust prevention, the photosensitive resin layer preferably contains a difunctional ethylenically unsaturated compound (preferably a difunctional (meth)acrylate compound) and a trifunctional or higher ethylenically unsaturated compound (preferably a trifunctional or higher (meth)acrylate compound). The mass ratio of the content of the difunctional ethylenically unsaturated compound to the content of the tri- or higher functional ethylenically unsaturated compound is preferably from 10:90 to 90:10, and more preferably from 30:70 to 70:30. The content of the difunctional ethylenically unsaturated compound relative to the total amount of all the ethylenically unsaturated compounds is preferably from 20% by mass to 80% by mass, and more preferably from 30% by mass to 70% by mass. The content of the bifunctional ethylenically unsaturated compound in the photosensitive resin layer is preferably from 10% by mass to 60% by mass, and more preferably from 15% by mass to 40% by mass, based on the total mass of the photosensitive resin layer.
[0390] In one preferred embodiment of the photosensitive resin layer, the photosensitive resin layer preferably contains a compound M and a bifunctional ethylenically unsaturated compound having an aliphatic hydrocarbon ring structure from the viewpoint of rust prevention. In addition, as one of the preferred embodiments of the photosensitive resin layer, from the viewpoints of substrate adhesion, suppression of development residue, and rust prevention, the photosensitive resin layer preferably contains a compound M and an ethylenically unsaturated compound having an acid group, more preferably contains a compound M, a bifunctional ethylenically unsaturated compound having an aliphatic hydrocarbon ring structure, and an ethylenically unsaturated compound having an acid group, still more preferably contains a compound M, a bifunctional ethylenically unsaturated compound having an aliphatic hydrocarbon ring structure, a tri- or higher functional ethylenically unsaturated compound, and an ethylenically unsaturated compound having an acid group, and particularly preferably contains a compound M, a bifunctional ethylenically unsaturated compound having an aliphatic hydrocarbon ring structure, a tri- or higher functional ethylenically unsaturated compound, an ethylenically unsaturated compound having an acid group, and a urethane (meth)acrylate compound. In addition, as one of the preferred embodiments of the photosensitive resin layer, from the viewpoints of substrate adhesion, development residue suppression, and rust prevention, the photosensitive resin layer preferably contains 1,9-nonanediol diacrylate and a polyfunctional ethylenically unsaturated compound having a carboxylic acid group, preferably contains 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, and a polyfunctional ethylenically unsaturated compound having a carboxylic acid group, more preferably contains 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, dipentaerythritol hexaacrylate, and an ethylenically unsaturated compound having a carboxylic acid group, and particularly preferably contains 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, an ethylenically unsaturated compound having a carboxylic acid group, and a urethane acrylate compound.
[0391] The photosensitive resin layer may contain a monofunctional ethylenically unsaturated compound as the ethylenically unsaturated compound. The content of the di- or higher functional ethylenically unsaturated compound in the above ethylenically unsaturated compound is preferably 60% by mass to 100% by mass, more preferably 80% by mass to 100% by mass, and even more preferably 90% by mass to 100% by mass, based on the total content of all ethylenically unsaturated compounds contained in the photosensitive resin layer.
[0392] The ethylenically unsaturated compounds may be used alone or in combination of two or more kinds. The content of the ethylenically unsaturated compound in the photosensitive resin layer is preferably 1% by mass to 70% by mass, more preferably 5% by mass to 70% by mass, even more preferably 5% by mass to 60% by mass, and particularly preferably 5% by mass to 50% by mass, relative to the total mass of the photosensitive resin layer.
[0393] -Polymerization initiator- The photosensitive resin layer may contain a polymerization initiator. The polymerization initiator is preferably a photopolymerization initiator. The preferred embodiment of the photopolymerization initiator is the same as the preferred embodiment of the photopolymerization initiator explained in the above section "Photosensitive resin layer." The polymerization initiator may be used alone or in combination of two or more kinds. The content of the polymerization initiator is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1.0% by mass or more, based on the total mass of the photosensitive resin layer, and the upper limit is preferably 10% by mass or less, more preferably 5% by mass or less, based on the total mass of the photosensitive resin layer.
[0394] -Heterocyclic compounds- The photosensitive resin layer may contain a heterocyclic compound. The heterocycle contained in the heterocyclic compound may be either a monocyclic or polycyclic heterocycle. Examples of the heteroatom contained in the heterocyclic compound include a nitrogen atom, an oxygen atom, and a sulfur atom. The heterocyclic compound preferably contains at least one atom selected from the group consisting of a nitrogen atom, an oxygen atom, and a sulfur atom, and more preferably contains a nitrogen atom.
[0395] Examples of heterocyclic compounds include triazole compounds, benzotriazole compounds, tetrazole compounds, thiadiazole compounds, triazine compounds, rhodanine compounds, thiazole compounds, benzothiazole compounds, benzimidazole compounds, benzoxazole compounds, and pyrimidine compounds. Among the above, the heterocyclic compound is preferably at least one compound selected from the group consisting of triazole compounds, benzotriazole compounds, tetrazole compounds, thiadiazole compounds, triazine compounds, rhodanine compounds, thiazole compounds, benzimidazole compounds, and benzoxazole compounds, and more preferably at least one compound selected from the group consisting of triazole compounds, benzotriazole compounds, tetrazole compounds, thiadiazole compounds, thiazole compounds, benzothiazole compounds, benzimidazole compounds, and benzoxazole compounds.
[0396] Preferable specific examples of the heterocyclic compound are shown below. As the triazole compound and the benzotriazole compound, the following compounds can be exemplified.
[0397] [ka]
[0398] [ka]
[0399] Examples of the tetrazole compound include the following compounds.
[0400] [ka]
[0401] [ka]
[0402] Examples of the thiadiazole compound include the following compounds.
[0403] [ka]
[0404] Examples of the triazine compound include the following compounds.
[0405] [ka]
[0406] Examples of rhodanine compounds include the following compounds.
[0407] [ka]
[0408] Examples of the thiazole compound include the following compounds.
[0409] [ka]
[0410] Examples of the benzothiazole compound include the following compounds.
[0411] [ka]
[0412] Examples of the benzimidazole compound include the following compounds.
[0413] [ka]
[0414] [ka]
[0415] Examples of the benzoxazole compound include the following compounds.
[0416] [ka]
[0417] The heterocyclic compounds may be used alone or in combination of two or more. When the photosensitive resin layer contains a heterocyclic compound, the content of the heterocyclic compound is preferably 0.01 mass% to 20.0 mass%, more preferably 0.10 mass% to 10.0 mass%, further preferably 0.30 mass% to 8.0 mass%, and particularly preferably 0.50 mass% to 5.0 mass%, relative to the total mass of the photosensitive resin layer.
[0418] -Aliphatic thiol compounds- The photosensitive resin layer may contain an aliphatic thiol compound. When the photosensitive resin layer contains an aliphatic thiol compound, the aliphatic thiol compound undergoes an ene-thiol reaction with the ethylenically unsaturated compound, thereby suppressing the cure shrinkage of the film formed and reducing stress.
[0419] The aliphatic thiol compound is preferably a monofunctional aliphatic thiol compound or a polyfunctional aliphatic thiol compound (that is, a di- or higher functional aliphatic thiol compound). Among the above, as the aliphatic thiol compound, polyfunctional aliphatic thiol compounds are more preferable from the viewpoint of adhesion of the pattern to be formed (particularly adhesion after exposure). In this specification, the term "polyfunctional aliphatic thiol compound" refers to an aliphatic compound having two or more thiol groups (also called "mercapto groups") in the molecule.
[0420] The polyfunctional aliphatic thiol compound is preferably a low molecular weight compound having a molecular weight of at least 100. Specifically, the molecular weight of the polyfunctional aliphatic thiol compound is more preferably 100 to 1,500, and further preferably 150 to 1,000.
[0421] The number of functional groups of the polyfunctional aliphatic thiol compound is preferably 2 to 10, more preferably 2 to 8, and even more preferably 2 to 6, from the viewpoint of adhesion of the formed pattern.
[0422] Examples of polyfunctional aliphatic thiol compounds include trimethylolpropane tris(3-mercaptobutyrate), 1,4-bis(3-mercaptobutyryloxy)butane, pentaerythritol tetrakis(3-mercaptobutyrate), 1,3,5-tris(3-mercaptobutyryloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, trimethylolethane tris(3-mercaptobutyrate), tris[(3-mercaptopropionyloxy)ethyl]isocyanurate, trimethylolpropane tris(3-mercaptopropionyloxy)ethyl]isocyanurate, ester), pentaerythritol tetrakis(3-mercaptopropionate), tetraethylene glycol bis(3-mercaptopropionate), dipentaerythritol hexakis(3-mercaptopropionate), ethylene glycol bisthiopropionate, 1,4-bis(3-mercaptobutyryloxy)butane, 1,2-ethanedithiol, 1,3-propanedithiol, 1,6-hexamethylenedithiol, 2,2'-(ethylenedithio)diethanethiol, meso-2,3-dimercaptosuccinic acid, and di(mercaptoethyl)ether.
[0423] Among the above, the polyfunctional aliphatic thiol compound is preferably at least one compound selected from the group consisting of trimethylolpropane tris(3-mercaptobutyrate), 1,4-bis(3-mercaptobutyryloxy)butane, and 1,3,5-tris(3-mercaptobutyryloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione.
[0424] Examples of monofunctional aliphatic thiol compounds include 1-octanethiol, 1-dodecanethiol, β-mercaptopropionic acid, methyl-3-mercaptopropionate, 2-ethylhexyl-3-mercaptopropionate, n-octyl-3-mercaptopropionate, methoxybutyl-3-mercaptopropionate, and stearyl-3-mercaptopropionate.
[0425] The photosensitive resin layer may contain one kind of aliphatic thiol compound alone, or may contain two or more kinds of aliphatic thiol compounds. When the photosensitive resin layer contains an aliphatic thiol compound, the content of the aliphatic thiol compound is preferably 5 mass% or more, more preferably 5 mass% to 50 mass%, even more preferably 5 mass% to 30 mass%, and particularly preferably 8 mass% to 20 mass%, relative to the total mass of the photosensitive resin layer.
[0426] -Thermal crosslinkable compound- The photosensitive resin layer preferably contains a thermally crosslinkable compound from the viewpoints of the strength of the resulting cured film and the adhesion of the resulting uncured film. Examples of the thermally crosslinkable compound include the thermally crosslinkable compounds described above in the section "Photosensitive resin layer." The thermally crosslinkable compound may be used alone or in combination of two or more kinds. When the photosensitive resin layer contains a thermally crosslinkable compound, the content of the thermally crosslinkable compound is preferably 1 mass % to 50 mass %, and more preferably 5 mass % to 30 mass %, based on the total mass of the photosensitive resin layer.
[0427] -Surfactants- The photosensitive resin layer may contain a surfactant. Examples of the surfactant include the surfactants described above in the section "Photosensitive resin layer." The surfactant may be used alone or in combination of two or more kinds. When the photosensitive resin layer contains a surfactant, the content of the surfactant is preferably 0.01% by mass to 3.0% by mass, more preferably 0.01% by mass to 1.0% by mass, and further preferably 0.05% by mass to 0.80% by mass, relative to the total mass of the photosensitive resin layer.
[0428] - Radical polymerization inhibitor - The photosensitive resin layer may contain a radical polymerization inhibitor. Examples of the radical polymerization inhibitor include the radical polymerization inhibitors described above in the section "Photosensitive resin layer." The radical polymerization inhibitor may be used alone or in combination of two or more kinds. When the photosensitive resin layer contains a radical polymerization inhibitor, the content of the radical polymerization inhibitor is preferably 0.01% by mass to 3% by mass, more preferably 0.05% by mass to 1% by mass, based on the total mass of the photosensitive resin layer. When the content is 0.01% by mass or more, the storage stability of the photosensitive resin layer is more excellent. On the other hand, when the content is 3% by mass or less, the maintenance of sensitivity and the suppression of decolorization of the dye are more excellent.
[0429] -Hydrogen donor compounds- The photosensitive resin layer may contain a hydrogen donor compound. The hydrogen donor compound has the effect of further improving the sensitivity of the photopolymerization initiator to actinic rays and suppressing the polymerization inhibition of the polymerizable compound caused by oxygen. Examples of hydrogen donor compounds include amines and amino acid compounds.
[0430] Examples of amines include compounds described in MR Sander et al., Journal of Polymer Society, Vol. 10, p. 3173 (1972), JP-B-020189 / 1969, JP-A-51-082102, JP-A-52-134692, JP-A-59-138205, JP-A-60-084305, JP-A-62-018537, JP-A-64-033104, and Research Disclosure No. 33825. More specifically, 4,4'-bis(diethylamino)benzophenone, tris(4-dimethylaminophenyl)methane (also known as leuco crystal violet), triethanolamine, p-dimethylaminobenzoic acid ethyl ester, p-formyldimethylaniline, and p-methylthiodimethylaniline. Among these, from the viewpoints of sensitivity, curing speed, and curability, the amine is preferably at least one selected from the group consisting of 4,4'-bis(diethylamino)benzophenone and tris(4-dimethylaminophenyl)methane.
[0431] Examples of the amino acid compound include N-phenylglycine, N-methyl-N-phenylglycine, and N-ethyl-N-phenylglycine. Among these, from the viewpoints of sensitivity, curing speed, and curability, N-phenylglycine is preferred as the amino acid compound.
[0432] Further, examples of hydrogen donor compounds include organometallic compounds (such as tributyltin acetate) described in JP-B-48-042965, hydrogen donors described in JP-B-55-034414, and sulfur compounds (such as trithiane) described in JP-A-6-308727.
[0433] The hydrogen donor compounds may be used alone or in combination of two or more kinds. When the photosensitive resin layer contains a hydrogen donor compound, the content of the hydrogen donor compound is preferably 0.01 mass % to 10.0 mass %, more preferably 0.01 mass % to 8.0 mass %, and even more preferably 0.03 mass % to 5.0 mass %, relative to the total mass of the photosensitive resin layer, from the viewpoint of improving the curing rate through a balance between the polymerization growth rate and chain transfer.
[0434] -impurities- The photosensitive resin layer may contain a predetermined amount of impurities. Examples of the impurities include the impurities described above in the section "Photosensitive resin layer."
[0435] -Residual monomer- The photosensitive resin layer may contain residual monomers corresponding to the respective structural units of the polymer A described above. Examples of the residual monomers corresponding to each structural unit of polymer A in the photosensitive resin layer include the residual monomers corresponding to each structural unit of polymer A described above in the section "Photosensitive resin layer."
[0436] -Other Ingredients- The photosensitive resin layer may contain components other than those described above (hereinafter, also referred to as "other components"). Examples of the other components include colorants, antioxidants, and particles (e.g., metal oxide particles). Examples of the other components include other additives described in paragraphs 0058 to 0071 of JP-A-2000-310706.
[0437] The particles are preferably metal oxide particles. The metals in the metal oxide particles include metalloids such as B, Si, Ge, As, Sb, and Te. The average primary particle size of the particles is, for example, preferably from 1 nm to 200 nm, and more preferably from 3 nm to 80 nm, from the viewpoint of the transparency of the cured film. The average primary particle size of particles is calculated by measuring the particle sizes of 200 random particles using an electron microscope and taking the arithmetic mean of the measurement results. If the particle shape is not spherical, the longest side is used as the particle size.
[0438] When the photosensitive resin layer contains particles, it may contain only one type of particles having different metal species, sizes, etc., or may contain two or more types of particles. The photosensitive resin layer does not contain particles, or if the photosensitive resin layer contains particles, the particle content is preferably more than 0 mass% and 35 mass% or less, relative to the total mass of the photosensitive resin layer; more preferably, the photosensitive resin layer does not contain particles or the particle content is more than 0 mass% and 10 mass% or less, relative to the total mass of the photosensitive resin layer; even more preferably, the photosensitive resin layer does not contain particles or the particle content is more than 0 mass% and 5 mass% or less, relative to the total mass of the photosensitive resin layer; even more preferably, the photosensitive resin layer does not contain particles or the particle content is more than 0 mass% and 1 mass% or less, relative to the total mass of the photosensitive resin layer; and it is particularly preferable that the photosensitive resin layer does not contain particles.
[0439] The photosensitive resin layer may contain a colorant (pigment, dye, etc.), but preferably does not substantially contain a colorant, for example, from the viewpoint of transparency. When the photosensitive resin layer contains a colorant, the content of the colorant is preferably less than 1% by mass, and more preferably less than 0.1% by mass, based on the total mass of the photosensitive resin layer.
[0440] Examples of antioxidants include 3-pyrazolidones such as 1-phenyl-3-pyrazolidone (also known as phenidone), 1-phenyl-4,4-dimethyl-3-pyrazolidone, and 1-phenyl-4-methyl-4-hydroxymethyl-3-pyrazolidone; polyhydroxybenzenes such as hydroquinone, catechol, pyrogallol, methylhydroquinone, and chlorohydroquinone; paramethylaminophenol, paraaminophenol, parahydroxyphenylglycine, and paraphenylenediamine. Among these, from the viewpoints of storage stability and curing property, 3-pyrazolidones are preferred as the antioxidant, and 1-phenyl-3-pyrazolidone is more preferred.
[0441] When the photosensitive resin layer contains an antioxidant, the content of the antioxidant is preferably 0.001% by mass or more, more preferably 0.005% by mass or more, and even more preferably 0.01% by mass or more, based on the total mass of the photosensitive resin layer. There is no particular upper limit, but the content is preferably 1% by mass or less.
[0442] -Thickness of photosensitive resin layer- The thickness (layer thickness) of the photosensitive resin layer is not particularly limited, but from the viewpoint of developability and resolution, it is preferably 30 μm or less, more preferably 20 μm or less, even more preferably 15 μm or less, particularly preferably 10 μm or less, and most preferably 5.0 μm or less. As the lower limit, it is preferably 0.60 μm or more, and more preferably 1.5 μm or more, in terms of excellent strength of the film obtained by curing the photosensitive resin layer.
[0443] -Refractive index of photosensitive resin layer- The refractive index of the photosensitive resin layer is preferably from 1.47 to 1.56, and more preferably from 1.49 to 1.54.
[0444] -Color of photosensitive resin layer- The photosensitive resin layer is preferably achromatic. Specifically, the total reflection (incident angle 8°, light source: D-65 (2° field of view)) is CIE1976(L * ,a * ,b * ) color space, L * The value is preferably 10 to 90, and a * The value is preferably -1.0 to 1.0, and b * The value is preferably between -1.0 and 1.0.
[0445] The pattern obtained by curing the photosensitive resin layer (cured film of the photosensitive resin layer) is preferably achromatic. Specifically, total reflection (incident angle 8°, light source: D-65 (2° field of view)) is * ,a * ,b * ) color space, the L * The value is preferably 10 to 90, and the pattern a *The value is preferably -1.0 to 1.0, and the b * The value is preferably between -1.0 and 1.0.
[0446] -Moisture permeability of photosensitive resin layer- The moisture permeability of the pattern (cured film of the photosensitive resin layer) obtained by curing the photosensitive resin layer at a layer thickness of 40 μm is set to 500 g / (m 2 24hr) or less, and 300g / (m 2 24hr) or less, and 100g / (m 2 It is more preferable that the time is 24 hours or less. The moisture permeability was measured by exposing the photosensitive resin layer to i-rays at a dose of 300 mJ / cm 2 After exposure to light at 40° C., the photosensitive resin layer is post-baked at 145° C. for 30 minutes to harden the photosensitive resin layer, and the hardness is measured on the hardened film.
[0447] (Refractive index adjustment layer) The photosensitive transfer material preferably has a refractive index adjusting layer. The refractive index adjusting layer may be a known refractive index adjusting layer. Examples of materials contained in the refractive index adjusting layer include an alkali-soluble resin, an ethylenically unsaturated compound, a metal salt, and particles. The method for controlling the refractive index of the refractive index adjusting layer is not particularly limited, and examples thereof include a method of using a resin having a predetermined refractive index alone, a method of using a resin and particles, and a method of using a complex of a metal salt and a resin.
[0448] Examples of the alkali-soluble resin and the ethylenically unsaturated compound include the alkali-soluble resin and the ethylenically unsaturated compound described above in the section "Photosensitive resin layer."
[0449] Examples of the particles include metal oxide particles and metal particles. The type of metal oxide particles is not particularly limited, and known metal oxide particles can be used. The metal in the metal oxide particles includes semimetals such as B, Si, Ge, As, Sb, and Te.
[0450] The average primary particle size of the particles is, for example, preferably from 1 nm to 200 nm, and more preferably from 3 nm to 80 nm, from the viewpoint of the transparency of the cured film. The average primary particle size of particles is calculated by measuring the particle sizes of 200 random particles using an electron microscope and taking the arithmetic mean of the measurement results. If the particle shape is not spherical, the longest side is used as the particle size.
[0451] Specifically, the metal oxide particles are preferably at least one selected from the group consisting of zirconium oxide particles (ZrO2 particles), Nb2O5 particles, titanium oxide particles (TiO2 particles), silicon dioxide particles (SiO2 particles), and composite particles thereof. Among these, the metal oxide particles are more preferably at least one type selected from the group consisting of zirconium oxide particles and titanium oxide particles, for example, from the viewpoint of ease of adjusting the refractive index.
[0452] Commercially available metal oxide particles include calcined zirconium oxide particles (manufactured by CIK Nanotech Co., Ltd., product name: ZRPGM15WT%-F04), calcined zirconium oxide particles (manufactured by CIK Nanotech Co., Ltd., product name: ZRPGM15WT%-F74), calcined zirconium oxide particles (manufactured by CIK Nanotech Co., Ltd., product name: ZRPGM15WT%-F75), calcined zirconium oxide particles (manufactured by CIK Nanotech Co., Ltd., product name: ZRPGM15WT%-F76), zirconium oxide particles (Nanouse OZ-S30M, manufactured by Nissan Chemical Industries, Ltd.), and zirconium oxide particles (Nanouse OZ-S30K, manufactured by Nissan Chemical Industries, Ltd.).
[0453] The particles may be used alone or in combination of two or more kinds. The content of the particles in the refractive index adjusting layer is preferably 1% by mass to 95% by mass, more preferably 20% by mass to 90% by mass, and further preferably 40% by mass to 85% by mass, based on the total mass of the refractive index adjusting layer. When titanium oxide is used as the metal oxide particles, the content of the titanium oxide particles is preferably 1 mass % to 95 mass %, more preferably 20 mass % to 90 mass %, and even more preferably 40 mass % to 85 mass %, relative to the total mass of the refractive index adjusting layer.
[0454] The refractive index of the refractive index adjusting layer is preferably higher than the refractive index of the photosensitive resin layer. The refractive index of the refractive index-adjusting layer is preferably 1.50 or more, more preferably 1.55 or more, even more preferably 1.60 or more, and particularly preferably 1.65 or more. The upper limit of the refractive index of the refractive index-adjusting layer is preferably 2.10 or less, more preferably 1.85 or less, and particularly preferably 1.78 or less.
[0455] The thickness of the refractive index adjusting layer is preferably from 50 nm to 500 nm, more preferably from 55 nm to 110 nm, and further preferably from 60 nm to 100 nm.
[0456] The refractive index adjustment layer is formed, for example, by using a refractive index adjustment layer. The composition for forming the refractive index adjustment layer preferably contains various components and a solvent that form the above-mentioned refractive index adjustment layer. In addition, in the composition for forming the refractive index adjustment layer, the preferred range of the content of each component relative to the total solid content of the composition is the same as the preferred range of the content of each component relative to the total mass of the above-mentioned refractive index adjustment layer. The solvent is not particularly limited as long as it is capable of dissolving or dispersing the components contained in the refractive index adjusting layer, and at least one selected from the group consisting of water and water-miscible organic solvents is preferred, and water or a mixed solvent of water and a water-miscible organic solvent is more preferred. Examples of the water-miscible organic solvent include alcohols having 1 to 3 carbon atoms, acetone, ethylene glycol, and glycerin, with alcohols having 1 to 3 carbon atoms being preferred, and methanol or ethanol being more preferred. The solvent may be used alone or in combination of two or more. The content of the solvent is preferably 50 parts by mass to 2,500 parts by mass, more preferably 50 parts by mass to 1,900 parts by mass, and even more preferably 100 parts by mass to 900 parts by mass, relative to 100 parts by mass of the total solid content of the composition.
[0457] The method for forming the refractive index adjusting layer is not particularly limited as long as it is a method capable of forming a layer containing the above components, and examples thereof include known coating methods (slit coating, spin coating, curtain coating, inkjet coating, etc.).
[0458] (Relationship between temporary support, photosensitive resin layer and protective film) In the photosensitive transfer material preferably used as the photosensitive transfer material for the wiring protective film, it is preferable that the above-mentioned relationship among the temporary support, the photosensitive resin layer, and the protective film is satisfied.
[0459] <Method of manufacturing resin pattern> The method for producing a resin pattern according to an embodiment of the present disclosure is a method for producing a resin pattern using a photosensitive transfer material according to the present disclosure. According to an embodiment of the present disclosure, a method for producing a resin pattern in which the occurrence of pinholes is suppressed is provided. The method for producing a resin pattern according to an embodiment of the present disclosure preferably includes a step of preparing a substrate (hereinafter, sometimes referred to as a "preparation step"); a step of contacting a photosensitive transfer material with the substrate and arranging a photosensitive resin layer and a temporary support on the substrate in this order (hereinafter, sometimes referred to as a "lamination step"); a step of exposing the photosensitive resin layer to a pattern (hereinafter, sometimes referred to as an "exposure step"); and a step of developing the exposed photosensitive resin layer to form a resin pattern (hereinafter, sometimes referred to as a "development step").
[0460] <<Preparation process>> In the preparation step, a substrate is prepared. The type of substrate is not limited. The substrate is preferably a substrate including a conductive layer. Furthermore, the substrate is preferably a substrate including a base material and a conductive layer on the base material, and more preferably a substrate including a base material and a conductive layer in contact with the base material. The conductive layer may be disposed on one side of the base material. The conductive layer may be disposed on both sides of the base material. The substrate may include a layer other than the conductive layer.
[0461] Examples of the substrate include glass, silicon, and resin films. The substrate is preferably transparent. In the present disclosure, "transparent" means that the transmittance at wavelengths of 400 nm to 700 nm is 80% or more. The refractive index of the substrate is preferably 1.50 to 1.52.
[0462] An example of the transparent glass is tempered glass, such as Gorilla Glass from Corning Inc. As the transparent glass, materials used in JP-A-2010-86684, JP-A-2010-152809, and JP-A-2010-257492 may be used.
[0463] The resin film is preferably a resin film having small optical distortion or high transparency. Examples of such resin films include polyethylene terephthalate (PET), polyethylene naphthalate, polycarbonate, triacetyl cellulose, and cycloolefin polymer.
[0464] In the method for producing a resin pattern utilizing a roll-to-roll system, the substrate is preferably a resin film.
[0465] The conductive layer may be, for example, a conductive layer used for general circuit wiring or touch panel wiring. The conductive layer is preferably an electrode pattern corresponding to a sensor of a visual recognition unit used in a capacitive touch panel or wiring of a peripheral extraction unit.
[0466] From the viewpoints of electrical conductivity and fine line formability, the conductive layer is preferably at least one selected from the group consisting of a metal layer, a conductive metal oxide layer, a graphene layer, a carbon nanotube layer, and a conductive polymer layer, more preferably a metal layer, and particularly preferably a copper layer or a silver layer.
[0467] Components of the conductive layer include, for example, metals and conductive metal oxides. Examples of metals include Al, Zn, Cu, Fe, Ni, Cr, Mo, Ag, and Au. Examples of conductive metal oxides include ITO (indium tin oxide), IZO (indium zinc oxide), and SiO2. In the present disclosure, "conductive" refers to a material having a volume resistivity of 1×10 6 The volume resistivity of conductive metal oxides is less than 1×10 4 It is preferably less than Ωcm.
[0468] When a resin pattern is produced using a substrate including a plurality of conductive layers, at least one of the plurality of conductive layers preferably includes a conductive metal oxide.
[0469] The substrate may include one or more conductive layers. When the substrate includes two or more conductive layers, the substrate preferably includes two or more conductive layers formed of different materials.
[0470] Preferred embodiments of the conductive layer are described, for example, in paragraph 0141 of WO 2018 / 155193, the contents of which are incorporated herein by reference.
[0471] The substrate including the conductive layer is preferably a substrate having at least one of a transparent electrode and a lead wiring. The substrate as described above can be suitably used as a substrate for a touch panel. The transparent electrode can suitably function as an electrode for a touch panel. The transparent electrode is preferably composed of a metal oxide film such as ITO (indium tin oxide) and IZO (indium zinc oxide), and a metal mesh and a metal nanowire. Examples of the metal wire include a thin wire of silver or copper. Among them, a silver conductive material such as a silver mesh or a silver nanowire is preferred.
[0472] The material of the wiring is preferably a metal. Examples of the metal that is the material of the wiring include gold, silver, copper, molybdenum, aluminum, titanium, chromium, zinc, and manganese, and alloys of two or more of these metal elements. The material of the wiring is preferably copper, molybdenum, aluminum, or titanium, and particularly preferably copper.
[0473] <<Bonding process>> In the lamination step, the photosensitive transfer material is brought into contact with the substrate, and the photosensitive resin layer and the temporary support are disposed in this order on the substrate.
[0474] The photosensitive transfer material is as described above in the section "Photosensitive Transfer Material." A preferred embodiment of the photosensitive transfer material used in the lamination step is the same as the preferred embodiment of the photosensitive transfer material described above in the section "Photosensitive Transfer Material."
[0475] In the lamination process, the photosensitive resin layer and the temporary support disposed on the substrate are the photosensitive resin layer and the temporary support contained in the photosensitive transfer material, respectively. That is, the layer structure of the laminate obtained by the lamination process changes depending on the layer structure of the photosensitive transfer material. For example, in the lamination process, when a photosensitive transfer material containing a temporary support, a thermoplastic resin layer, an intermediate layer, and a photosensitive resin layer in this order is contacted with the substrate, the photosensitive resin layer, the intermediate layer, the thermoplastic resin layer, and the temporary support are disposed on the substrate in this order. When the photosensitive transfer material contains a protective film, the protective film is removed from the photosensitive transfer material, and then the photosensitive transfer material is contacted with the substrate.
[0476] In the lamination step, it is preferable to bring the photosensitive transfer material into contact with the substrate and pressurize the photosensitive transfer material onto the substrate. For example, it is preferable to bring the photosensitive transfer material into contact with the substrate and apply pressure and heat to the substrate and the photosensitive transfer material using a means such as a roll, thereby pressing the photosensitive transfer material onto the substrate.
[0477] In the method of contacting the photosensitive transfer material with the substrate (including the method of pressing the photosensitive transfer material with the substrate), for example, a known transfer method or a known lamination method is used. In the method of contacting the photosensitive transfer material with the substrate, for example, a laminator, a vacuum laminator, or an auto-cut laminator that can further increase productivity is used.
[0478] <<Exposure process>> In the exposure step, the photosensitive resin layer is exposed to a pattern. The arrangement and dimensions of the pattern in the pattern exposure are not limited. At least a part of the pattern (preferably a part corresponding to the electrode pattern or the lead wiring of the touch panel) preferably includes a thin line having a width of 20 μm or less, and more preferably includes a thin line having a width of 10 μm or less.
[0479] Examples of the light source in the exposure step include light sources that irradiate light with a wavelength capable of exposing the photosensitive resin layer (e.g., 365 nm or 405 nm). Examples of the light source include ultra-high pressure mercury lamps, high pressure mercury lamps, metal halide lamps, and LEDs (Light Emitting Diodes).
[0480] The exposure dose was 5 mJ / cm 2 ~300mJ / cm 2 and preferably 10 mJ / cm 2 ~200mJ / cm 2 It is more preferable that:
[0481] In the exposure step, the photosensitive resin layer may be pattern-exposed after the temporary support is peeled off.In the exposure step, the photosensitive resin layer may be pattern-exposed through the temporary support, and then the temporary support may be peeled off.
[0482] In the exposure method using a photomask, when the temporary support is peeled off before the pattern exposure, the photosensitive resin layer may be exposed by contacting the photomask with the photosensitive resin layer, or the photosensitive resin layer may be exposed by bringing the photomask close to the photosensitive resin layer without contacting the photosensitive resin layer. In the exposure method using a photomask, when the photosensitive resin layer is exposed through a temporary support, the photosensitive resin layer may be exposed by contacting the photomask with the temporary support, or the photosensitive resin layer may be exposed by bringing the photomask close to the temporary support without contacting the photomask with the temporary support. In order to prevent contamination of the photomask due to contact between the photosensitive resin layer and the photomask, and to avoid the influence of foreign matter attached to the photomask on the exposure, it is preferable to expose the photosensitive resin layer through the temporary support.
[0483] The exposure method is not limited. Examples of the exposure method include contact exposure method and non-contact exposure method. Examples of the contact exposure method include a method of pattern-exposing the photosensitive resin layer using a photomask. Examples of the non-contact exposure method include a proximity exposure method, a lens-based or mirror-based projection exposure method, and a direct exposure method using an exposure laser. In the lens-based or mirror-based projection exposure method, an exposure machine having an appropriate lens numerical aperture (NA) may be used depending on the required resolution and focal depth. In the direct exposure method, drawing may be performed directly on the photosensitive layer, or reduced projection exposure may be performed on the photosensitive layer through a lens. Exposure may be performed under atmospheric conditions, reduced pressure, or vacuum. Exposure may be performed by interposing a liquid such as water between the light source and the photosensitive resin layer.
[0484] <<Developing process>> In the development step, the exposed photosensitive resin layer is developed to form a resin pattern. When the photosensitive resin layer is a negative photosensitive resin layer, the non-exposed portion of the photosensitive resin layer is removed, and the exposed portion of the photosensitive resin layer forms a resin pattern. When the photosensitive resin layer is a positive photosensitive resin layer, the exposed portion of the photosensitive resin layer is removed, and the non-exposed portion of the photosensitive resin layer forms a resin pattern. In addition, the thermoplastic resin layer and the intermediate layer arranged on the substrate in the lamination step are removed together with the photosensitive resin layer to be removed. The thermoplastic resin layer and the intermediate layer may be removed by dissolving or dispersing in a developer.
[0485] The development is carried out, for example, using a developer. The developer is not limited as long as it is a developer that removes the target photosensitive resin layer. A known developer is used as the developer. For example, the developer described in JP-A-5-72724 can be mentioned. The developer is preferably an alkaline aqueous solution type developer containing a compound having a pKa of 7 to 13 at a concentration of 0.05 mol / L to 5 mol / L. The developer may contain a water-soluble organic solvent and / or a surfactant. The developer is also preferably the developer described in paragraph 0194 of WO 2015 / 093271.
[0486] The temperature of the developer is not limited, but is preferably 20°C to 40°C.
[0487] The developing method is not limited. The developing method may be, for example, paddle development, shower development, shower and spin development, or dip development. Shower development is a method in which a developing solution is sprayed onto the exposed photosensitive resin layer by showering, thereby removing the target photosensitive resin layer.
[0488] After the development step, it is preferable to remove development residues by spraying a cleaning agent by showering and scrubbing with a brush.
[0489] The line width of the resin pattern obtained through the above-mentioned steps is preferably 20 μm or less, more preferably 10 μm or less, and particularly preferably 8 μm or less. There is no lower limit for the line width of the resin pattern. The line width of the resin pattern may be, for example, 1 μm or more. The line width of the resin pattern is measured by the following method. The resin pattern is observed using a scanning electron microscope (SEM) and the line widths of 30 points in the resin pattern are measured. The arithmetic average of the measured values is adopted as the line width of the resin pattern.
[0490] The resin pattern obtained through the above steps may be used as a permanent film or a protective film for etching.
[0491] <<Roll-to-roll method>> The method for producing a resin pattern is preferably carried out by a roll-to-roll method. The roll-to-roll method refers to a method in which a substrate capable of being wound up and unwound is used, and includes a step of unwinding a substrate or a laminate including a substrate (sometimes referred to as an "unwinding step") before any step included in the method for producing a resin pattern, and a step of winding a substrate or a laminate including a substrate (sometimes referred to as a "winding step" below) after any step, and at least any step (preferably all steps) is carried out while transporting the substrate or the laminate including a substrate. As the unwinding method in the unwinding step and the winding method in the winding step, for example, a known method applied to the roll-to-roll method is used.
[0492] <Method of manufacturing conductive patterns> A method for producing a conductive pattern according to an embodiment of the present disclosure is a method for producing a conductive pattern using a photosensitive transfer material according to the present disclosure. According to an embodiment of the present disclosure, a method for producing a conductive pattern in which the occurrence of pinholes is suppressed is provided. The method for producing a conductive pattern according to an embodiment of the present disclosure preferably includes a step of preparing a substrate including a conductive layer (hereinafter, sometimes referred to as a "preparation step"); a step of contacting a photosensitive transfer material with the substrate and arranging a photosensitive resin layer and a temporary support on the substrate in this order (hereinafter, sometimes referred to as a "lamination step"); a step of exposing the photosensitive resin layer to a pattern (hereinafter, sometimes referred to as an "exposure step"); a step of developing the exposed photosensitive resin layer to form a resin pattern (hereinafter, sometimes referred to as a "development step"); and a step of etching the conductive layer not covered by the resin pattern to form a conductive pattern (hereinafter, sometimes referred to as an "etching step").
[0493] <<Preparation process>> In the preparation step, a substrate including a conductive layer is prepared. The substrate including a conductive layer is as described above in the section "Method for producing a resin pattern". A preferred embodiment of the substrate including a conductive layer is the same as the preferred embodiment of the substrate including a conductive layer described above in the section "Method for producing a resin pattern". <<Bonding process>> In the lamination step, the photosensitive transfer material is brought into contact with the substrate, and the photosensitive resin layer and the temporary support are placed on the substrate in this order. The lamination step is as described above in the section "Method for producing a resin pattern." The preferred embodiment of the lamination step is the same as the preferred embodiment of the lamination step described above in the section "Method for producing a resin pattern."
[0494] <<Exposure process>> In the exposure step, the photosensitive resin layer is exposed to a pattern. The exposure step is as described above in the section "Method for producing a resin pattern." The preferred embodiment of the exposure step is the same as the preferred embodiment of the exposure step described above in the section "Method for producing a resin pattern."
[0495] <<Developing process>> In the development step, the exposed photosensitive resin layer is developed to form a resin pattern. The development step is as described above in the section "Method for producing a resin pattern." The preferred embodiment of the development step is the same as the preferred embodiment of the development step described above in the section "Method for producing a resin pattern."
[0496] <<Etching process>> In the etching process, the conductive layer not covered by the resin pattern is etched to form the conductive pattern. In the etching process, the resin pattern functions as a protective film for the conductive layer. In the etching process, the conductive layer not covered by the resin pattern is removed by etching, and the conductive layer covered by the resin pattern forms the conductive pattern.
[0497] As the etching method, for example, a known method is used. As the etching method, for example, the method described in paragraphs 0209 to 0210 of JP2017-120435A, the method described in paragraphs 0048 to 0054 of JP2010-152155A, a wet etching method in which the substrate is immersed in an etching solution, and a dry etching method (for example, plasma etching) can be mentioned.
[0498] The etching solution used in the wet etching method may be an acidic or alkaline etching solution that is appropriately selected according to the target of etching. Examples of the acidic etching solution include an aqueous solution containing at least one acidic component selected from the group consisting of hydrochloric acid, sulfuric acid, nitric acid, acetic acid, hydrofluoric acid, oxalic acid, and phosphoric acid. Examples of the acidic etching solution include an aqueous solution containing the above-mentioned acidic component and at least one salt selected from the group consisting of ferric chloride, ammonium fluoride, and potassium permanganate. The acidic component may be a combination of multiple acidic components. Examples of the alkaline etching solution include an aqueous solution containing at least one alkaline component selected from the group consisting of sodium hydroxide, potassium hydroxide, ammonia, organic amines, and salts of organic amines (e.g., tetramethylammonium hydroxide). Examples of the alkaline etching solution include an aqueous solution containing the above-mentioned alkaline component and a salt (e.g., potassium permanganate). The alkaline component may be a combination of multiple alkaline components.
[0499] <<Removal process>> The method for producing a conductive pattern according to an embodiment of the present disclosure preferably includes, after the etching step, a step of removing the remaining resin pattern.
[0500] As a method for removing the resin pattern, for example, a method for removing the resin pattern using a chemical treatment can be mentioned. A method for removing the resin pattern using a removal liquid is preferable. As a method for removing the resin pattern using a removal liquid, for example, a method for immersing a substrate including a resin pattern in a stirring removal liquid having a liquid temperature of 30°C to 80°C (preferably 50 to 80°C) for 1 minute to 30 minutes can be mentioned.
[0501] The removal liquid may, for example, include a removal liquid containing an inorganic or organic alkaline component and at least one selected from the group consisting of water, dimethyl sulfoxide, and N-methylpyrrolidone. The inorganic alkaline component may, for example, be sodium hydroxide or potassium hydroxide. The organic alkaline component may, for example, be a primary amine compound, a secondary amine compound, a tertiary amine compound, or a quaternary ammonium salt compound.
[0502] The remaining resin pattern may be removed using known methods such as spray, shower and puddle methods.
[0503] <<Other processes>> The method for producing a conductive pattern according to an embodiment of the present disclosure may further include other steps in addition to the steps described above. Examples of the other steps include the steps shown below. Furthermore, the exposure step, development step, and other steps applicable to the method for producing a conductive pattern according to an embodiment of the present disclosure are described in paragraphs 0035 to 0051 of JP 2006-23696 A. The contents of the above publications are incorporated herein by reference.
[0504] (Step of reducing visible light reflectance) The method for manufacturing a conductive pattern according to an embodiment of the present disclosure may include a step of performing a process for reducing the visible light reflectance of a part or all of the multiple conductive layers of the substrate. Examples of the process for reducing the visible light reflectance include an oxidation process. For example, when the conductive layer contains copper, the visible light reflectance of the conductive layer can be reduced by oxidizing the copper to form copper oxide and blackening the conductive layer. The process for reducing the visible light reflectance is described in paragraphs 0017 to 0025 of JP 2014-150118 A and paragraphs 0041, 0042, 0048, and 0058 of JP 2013-206315 A. The contents of these publications are incorporated herein by reference.
[0505] (Step of forming an insulating film and step of forming a new conductive layer on the surface of the insulating film) The method for producing a conductive pattern according to an embodiment of the present disclosure preferably includes a step of forming an insulating film on the surface of the conductive pattern, and a step of forming a new conductive layer on the surface of the insulating film. The above steps allow the formation of a second electrode pattern insulated from the first electrode pattern. Examples of a method for forming an insulating film include a method for forming a known permanent film. A photosensitive material having insulating properties may be used to form an insulating film of a desired pattern by photolithography. Examples of a method for forming a new conductive layer on the surface of an insulating film include a method for forming a new conductive layer of a desired pattern by photolithography using a photosensitive material having electrical conductivity.
[0506] In the method for producing a conductive pattern according to an embodiment of the present disclosure, it is also preferable to use a substrate having a plurality of conductive layers on both sides of the substrate, and to form a circuit on the conductive layers formed on both sides of the substrate sequentially or simultaneously. According to the above-mentioned method, a first conductive pattern can be formed on one surface of the substrate, and a second conductive pattern can be formed on the other surface of the substrate. The above-mentioned conductive pattern is used, for example, as a circuit wiring for a touch panel. The above-mentioned conductive pattern is preferably formed by a roll-to-roll method.
[0507] <<Roll-to-roll method>> The method for producing a conductive pattern according to an embodiment of the present disclosure is preferably performed by a roll-to-roll method, as described above in the section "Method for producing a resin pattern."
[0508] <<Circuit wiring applications>> The conductive pattern obtained by the method for producing a conductive pattern according to an embodiment of the present disclosure is applied to various devices. An example of a device including a conductive pattern is an input device, preferably a touch panel, more preferably a capacitive touch panel. The input device can be applied to a display device such as an organic electroluminescence display device or a liquid crystal display device. In addition, the conductive pattern obtained by the method for producing a conductive pattern according to an embodiment of the present disclosure is preferably applied to a touch sensor.
[0509] <Touch sensor> The touch sensor according to an embodiment of the present disclosure includes a conductive pattern obtained by the method for producing a conductive pattern according to an embodiment of the present disclosure. The components of the touch sensor according to an embodiment of the present disclosure are not limited except that the components include a conductive pattern obtained by the method for producing a conductive pattern according to an embodiment of the present disclosure. The conductive pattern is used, for example, as a transparent electrode or frame wiring of the touch sensor. The shape and dimensions of the conductive pattern are determined, for example, according to the target touch sensor. Examples of the photomask pattern used in the production of the conductive pattern include pattern A and pattern B described in JP 2019-204070 A. As components other than the conductive pattern, for example, components included in a known touch sensor are used. The touch sensor is described, for example, in JP 6486341 A and JP 2016-155978 A. These publications are incorporated herein by reference. The known method for producing a touch sensor may be referred to in order to form components of the touch sensor other than the conductive pattern.
[0510] The touch sensor is applied to, for example, various input devices, such as a touch panel.
[0511] Examples of detection methods for touch panels include resistive film type, capacitive type, ultrasonic type, electromagnetic induction type, and optical type. Among these, the capacitive type is preferred.
[0512] Examples of touch panel types include in-cell types (e.g., the configurations shown in Figures 5, 6, 7, and 8 of JP-T-2012-517051), on-cell types (e.g., the configuration shown in Figure 19 of JP-A-2013-168125 and the configurations shown in Figures 1 and 5 of JP-A-2012-89102), OGS (One Glass Solution) types, TOL (Touch-on-Lens) types (e.g., the configuration shown in Figure 2 of JP-A-2013-54727), various out-cell types (e.g., GG, G1 / G2, GFF, GF2, GF1, and G1F), and other configurations (e.g., the configuration shown in Figure 6 of JP-A-2013-164871). EXAMPLES
[0513] The present disclosure will be described in detail below based on examples. However, the present disclosure is not limited to the following examples. The contents of the following examples (e.g., materials, amounts used, ratios, processing contents and processing procedures) may be changed as appropriate within the scope of the purpose of the present disclosure.
[0514] <Preparation of particle-containing layer forming composition 1> The mixture obtained by mixing the components shown below was filtered using a 6 μm filter (F20, Mahle Filter Systems, Inc.) and then subjected to membrane degassing using a 2x6 Radial Flow Superphobic (Polypore, Inc.) By the above procedure, a particle-containing layer forming composition 1 was obtained.
[0515] Acrylic polymer (AS-563A, Daicel Miraize Co., Ltd., solid content: 27.5% by mass): 167 parts by mass Nonionic surfactant (Naroacty CL95, Sanyo Chemical Industries, Ltd., solid content: 100% by mass): 0.7 parts by mass Anionic surfactant (Rapisol A-90, NOF Corporation, water-diluted solution with a solids concentration of 1% by mass): 114.4 parts by mass Carnauba wax dispersion (Cellosol 524, Chukyo Yushi Co., Ltd., solid content: 30% by mass): 7 parts by mass Carbodiimide compound (Carbodilite V-02-L2, Nisshinbo Chemical Inc., diluted with water to a solids concentration of 10% by mass): 20.9 parts by mass Matting agent (Snowtex XL, Nissan Chemical Co., Ltd., solid content: 40% by weight, average particle size: 50 nm): 2.8 parts by weight ·Water: 690.2 parts by mass
[0516] <Production of temporary support 1> A temporary support 1 was produced by the following method.
[0517] (Extrusion molding) Pellets of polyethylene terephthalate (PET) produced using the citric acid chelate organic titanium complex described in Japanese Patent No. 5575671 as a polymerization catalyst were dried to reduce the moisture content of the pellets to 50 ppm or less. The dried pellets were placed in a hopper of a single-screw kneading extruder having a diameter of 30 mm and melted at 280°C. The melt was passed through a filter (hole size: 2 μm) and then extruded from a die onto a cooling roll at 25°C to obtain an unstretched film. In the above method, the melt was brought into close contact with the cooling roll using an electrostatic application method.
[0518] (Stretching and Coating) The solidified unstretched film was subjected to sequential biaxial stretching by the following method to form a particle-containing layer with a thickness of 40 nm on a polyethylene terephthalate film with a thickness of 16 μm.
[0519] (a) Longitudinal stretching The unstretched film was passed between two pairs of nip rolls with different peripheral speeds and stretched in the machine direction (transport direction). The conditions for machine stretching are as follows: Preheat temperature: 75℃ ·Stretching temperature: 90℃ ·Stretching ratio: 3.4 times ·Stretching speed: 1,300% / sec
[0520] (b) Coating Composition 1 for forming a particle-containing layer was applied to one surface of the longitudinally stretched film using a bar coater so that the thickness of the film after formation would be 40 nm.
[0521] (c) Lateral stretching The film coated with the particle-containing layer forming composition 1 was stretched laterally using a tenter under the following conditions. Preheat temperature: 110℃ ·Stretching temperature: 120℃ ·Stretching ratio: 4.2x ·Stretching speed: 50% / sec
[0522] (Heat Fixation and Heat Relaxation) The biaxially stretched film having been stretched longitudinally and transversely was heat-set under the following conditions. ·Heat fixing temperature: 227℃ ·Heat setting time: 6 seconds
[0523] After heat setting, the tenter width was reduced and the biaxially stretched film was heat relaxed under the following conditions. ·Thermal relaxation temperature: 190℃ ·Thermal relaxation rate: 4%
[0524] (winding) After heat fixing and heat relaxation, both ends of the film were trimmed, and the ends of the film were extrusion processed (knurled) at a width of 10 mm, and then the film was wound up with a tension of 40 kg / m. The width of the film was 1.5 m, and the wound length of the film was 6,300 m. The obtained film roll was used as temporary support 1.
[0525] The temporary support 1 includes a polyethylene terephthalate film (base material) and a particle-containing layer in this order. The haze of the temporary support 1 was 0.2%. The haze was measured as total light haze using a haze meter (Nippon Denshoku Industries Co., Ltd., NDH2000). The thermal shrinkage rate by heating at 150°C for 30 minutes was 1.0% on the MD (machine direction) side and 0.2% on the TD (transverse direction) side. The thickness of the particle-containing layer measured from a cross-sectional TEM photograph was 40 nm. The average particle diameter of the particles contained in the particle-containing layer measured by the above-mentioned method using a HT-7700 transmission electron microscope (TEM) manufactured by Hitachi High-Technologies Corporation was 50 nm.
[0526] <Production of temporary support 2> A temporary support 2 was obtained in the same manner as the temporary support 1, except that in the extrusion molding, the melt was passed through the filter twice.
[0527] <Production of temporary support 3> A temporary support 3 was obtained in the same manner as the temporary support 1, except that in the extrusion molding, the pore size of the filter of the filter was changed to 3 μm.
[0528] <Production of temporary support 4> A temporary support 4 was obtained in the same manner as the temporary support 3, except that in the extrusion molding, the melt was passed through the filter twice.
[0529] <Production of temporary support 5> A temporary support 5 was obtained in the same manner as the temporary support 3, except that in the extrusion molding, the melt was passed through the filter three times.
[0530] <Production of temporary support 6> A temporary support 6 was obtained in the same manner as the temporary support 4, except that in the extrusion molding, the discharge amount was adjusted so that the thickness of the temporary support would be 10 μm.
[0531] <Manufacture of temporary support 7> A temporary support 7 was obtained in the same manner as the temporary support 1, except that in the extrusion molding, the pore size of the filter of the filter was changed to 5 μm.
[0532] <Number of particles> Ten random areas on the surface of the temporary support (size of each area: 10 mm × 10 mm, total area: 1000 mm) 2 ) was visually observed using an optical microscope. The number of particles with a diameter of 3 μm or more contained in each area was counted. Based on the total number of particles counted in the 10 areas, the number of particles per cm2 of the measurement area was calculated. 2 Number of particles per cm 2 The measurement results are shown below. In Table 1, the column "3μm~" indicates the number of particles with diameters of 3μm or more and less than 4.5μm (particles / cm 2 ) in the "4.5μm~" column, and the number of particles with a diameter of 4.5μm or more but less than 6μm (pieces / cm 2 ) in the "6μm~" column, and the number of particles with a diameter of 6μm or more but less than 7.5μm (pieces / cm 2 ) in the "9μm~" column, and the number of particles with a diameter of 9μm or more but less than 10.5μm (pieces / cm 2 ) and in the "10.5μm~" column, the number of particles with a diameter of 10.5μm or more (pieces / cm 2 ) are shown, respectively.
[0533] [Table 1]
[0534] <Preparation of Photosensitive Resin Layer Forming Compositions 1 to 4> Compositions 1 to 4 for forming photosensitive resin layers were prepared by mixing methyl ethyl ketone (400 parts by mass), propylene glycol monomethyl ether (40 parts by mass), propylene glycol monomethyl ether acetate (200 parts by mass), methyl alcohol (20 parts by mass) and the following components.
[0535] [Table 2]
[0536] <Preparation of Thermoplastic Resin Layer-Forming Composition 1> Methyl ethyl ketone (500 parts by mass), propylene glycol monomethyl ether (20 parts by mass), propylene glycol monomethyl ether acetate (200 parts by mass) and the following components were mixed to prepare a thermoplastic resin layer forming composition 1.
[0537] [Table 3]
[0538] The meanings of the abbreviations in the above table are as follows: A-2: Benzyl methacrylate / methacrylic acid / acrylic acid copolymer (75% by mass / 10% by mass / 15% by mass, weight average molecular weight: 30,000, Tg: 75°C, acid value: 186 mgKOH / g) B-1: Compound with the structure shown below (a dye that changes color when exposed to acid)
[0539] [ka]
[0540] C-1: Compound with the structure shown below (photoacid generator, compound described in paragraph 0227 of JP2013-47765A, synthesized according to the method described in paragraph 0227)
[0541] [ka]
[0542] D-3: NK Ester A-DCP (tricyclodecane dimethanol diacrylate, Shin-Nakamura Chemical Co., Ltd.) D-4: 8UX-015A (multifunctional urethane acrylate compound, Taisei Fine Chemical Co., Ltd.) D-5: ARONIX TO-2349 (polyfunctional acrylate compound with carboxyl groups, Toagosei Co., Ltd.) E-1: Megafac F-552 (fluorosurfactant, DIC Corporation) F-1: Phenothiazine (FUJIFILM Wako Pure Chemical Corporation) F-2: CBT-1 (Carboxybenzotriazole, Johoku Chemical Industry Co., Ltd.)
[0543] <Preparation of Water-Soluble Resin Layer-Forming Composition 1> The following components were mixed to prepare a water-soluble resin layer forming composition 1. Ion-exchanged water: 38.12 parts by weight Methanol (Mitsubishi Gas Chemical Co., Ltd.): 57.17 parts by mass Kuraray Poval 4-88LA (Polyvinyl alcohol, Kuraray Co., Ltd.): 3.22 parts by weight Polyvinylpyrrolidone K-30 (Nippon Shokubai Co., Ltd.): 1.49 parts by weight Megafac F-444 (fluorosurfactant, DIC Corporation): 0.0035 parts
[0544] <Example 1> The thermoplastic resin layer forming composition 1 was applied to the surface of the temporary support base material (polyethylene terephthalate film) opposite to the surface on which the particle-containing layer was to be formed, using a slit nozzle. The applied thermoplastic resin layer forming composition 1 was dried at 100° C. for 120 seconds to form a thermoplastic resin layer having a thickness of 2.0 μm.
[0545] On the thermoplastic resin layer, the composition 1 for forming a water-soluble resin layer was applied using a slit nozzle. The applied composition 1 for forming a water-soluble resin layer was dried at 120° C. for 120 seconds to form a water-soluble resin layer having a thickness of 1.0 μm. The water-soluble resin layer was an intermediate layer.
[0546] Photosensitive resin layer forming composition 2 was applied onto the water-soluble resin layer using a slit nozzle. The applied photosensitive resin layer forming composition 2 was dried at 100° C. for 120 seconds to form a photosensitive resin layer having a thickness of 4.0 μm.
[0547] The photosensitive transfer material obtained by the above procedure includes a temporary support, a thermoplastic resin layer, a water-soluble resin layer, and a photosensitive resin layer in this order. The layer configurations of the thermoplastic resin layer, the water-soluble resin layer, and the photosensitive resin layer are shown in Tables 4 and 5.
[0548] <Examples 2 to 10 and Comparative Example 1> Photosensitive transfer materials were obtained in the same manner as in Example 1, except that the type of temporary support and the layer structure were appropriately changed according to the descriptions in Tables 4 and 5.
[0549] <Resolution> (1) A copper layer having a thickness of 200 nm was formed by sputtering on a polyethylene terephthalate (PET) film having a thickness of 100 μm, to prepare a PET substrate with a copper layer. A photosensitive transfer material and a PET substrate with a copper layer were bonded together by a roll-to-roll method using a vacuum laminator (MCK Corporation, roll temperature: 100° C., linear pressure: 1.0 MPa, linear speed: 0.5 m / min). The obtained laminate contained at least a PET film, a copper layer, a photosensitive resin layer, and a temporary support, in this order. (2) The obtained laminate was pressurized and degassed for 30 minutes using an autoclave under conditions of 0.6 MPa and 60° C. (3) Using an ultra-high pressure mercury lamp, the photosensitive resin layer was exposed through a line and space pattern mask (the duty ratio was 1:1, and the line width changed stepwise from 1 μm to 20 μm at 1 μm intervals) without peeling off the temporary support. (4) The temporary support was peeled off, and then development was performed. Development was performed by shower development for 30 seconds using a 1.0% by mass aqueous solution of sodium carbonate at 25°C. A resin pattern was formed by developing the photosensitive resin layer. The exposure dose (unit: mJ / cm2) was increased until a resin pattern having a minimum line width corresponding to the mask pattern (hereinafter referred to as the "reference pattern" in this paragraph) was obtained. 2The above-mentioned series of steps (1) to (4) were carried out while adjusting each time. The minimum line width of the reference pattern was adopted as the limit resolution (X) of the photosensitive resin layer. The evaluation results are shown in Table 5.
[0550] <Pinholes in wiring patterns> A wiring pattern (i.e., a resin pattern) was formed by the same method as described in the "Resolution" section above (i.e., a method of exposing a photosensitive resin layer to a standard exposure dose to form a resin pattern), except for using a wiring formation mask (duty ratio 1:1, line width varying in 1 μm increments from 1 μm to 20 μm, length of the wiring pattern 50 mm, number of wirings 10). The wiring pattern was visually observed using an optical microscope, and pinholes in the wiring pattern were evaluated according to the following criteria based on the maximum size and number of pinholes. The evaluation results are shown in Table 5. A: No pinholes were found, or pinholes smaller than 1 / 4 of the wiring width were found. B: A pinhole larger than 1 / 4 and smaller than 1 / 2 the wiring width was confirmed. C: A pinhole larger than 1 / 2 and smaller than 3 / 4 of the wiring width was confirmed. D: A pinhole larger than 3 / 4 of the wiring width was confirmed.
[0551] [Table 4]
[0552] [Table 5]
[0553] Table 5 shows that, compared to Comparative Example 1, the occurrence of pinholes in the wiring patterns in Examples 1 to 10 was suppressed.
[0554] <Examples 11 to 21> (Preparation of Polyester A Pellets) Esterification reaction was carried out with 86.5 parts by mass of terephthalic acid and 37.1 parts by mass of ethylene glycol at 255° C. while distilling off water. After completion of the esterification reaction, 0.02 parts by mass of trimethyl phosphate, 0.06 parts by mass of magnesium acetate, 0.01 parts by mass of lithium acetate, and 0.0085 parts by mass of antimony trioxide were added, and the mixture was subsequently heated to 290° C. under reduced pressure to carry out a polycondensation reaction, thereby obtaining polyester A pellets (referred to as polyester A in Table 6) having an intrinsic viscosity of 0.63 dl / g.
[0555] (Preparation of polyester C pellets) Using terephthalic acid as the dicarboxylic acid component and CHDM (cyclohexanedimethanol) as the diol component, a polycondensation reaction was carried out in the presence of 200 ppm of butyltin tris(2-ethylhexanoate) to obtain polyester C pellets having an alicyclic structure (referred to as polyester C in Table 6).
[0556] (Preparation of polyester E-pellets) In producing polyester A pellets in the same manner as described above, after the esterification reaction was completed, spherical silica having a volume average particle diameter of 0.2 μm, a volume shape factor f=0.51, a volume average particle diameter of 0.06 μm, a volume shape factor f=0.51, and a Mohs hardness of 7 was added, and then a polycondensation reaction was carried out to obtain silica-containing polyester E pellets (referred to as polyester E in Table 6) containing 1% by mass each of the two types of spherical silica relative to the mass of polyester A. The spherical silica is monodispersed silica particles obtained by adding a mixed solution of ethanol, pure water, and aqueous ammonia to a mixed solution of ethanol and ethyl silicate while stirring the mixed solution, stirring the resulting reaction solution to carry out a hydrolysis reaction of ethyl silicate and a polycondensation reaction of the hydrolysis product, and then stirring the mixture after the reaction.
[0557] (Preparation of Polyester G Pellets) To 100 parts by mass of dimethyl terephthalate and 64 parts by mass of ethylene glycol, 0.04 parts by mass of manganese acetate and 0.03 parts by mass of antimony trioxide were added as a catalyst to carry out an ester exchange reaction, and then a slurry containing agglomerated alumina was added to the reaction product, and then antimony trioxide was added to carry out a polycondensation reaction, thereby obtaining Polyester G pellets (referred to as Polyester G in Table 6) containing 2% by mass of agglomerated alumina and having an intrinsic viscosity of 0.62 dl / g. The above-mentioned slurry containing agglomerated alumina was obtained by using δ-type alumina as the agglomerated alumina, preparing a 10 mass% ethylene glycol slurry, pulverizing and dispersing the slurry using a sand grinder, and filtering the slurry using a 3 μm filter with a collection efficiency of 95%.
[0558] (Preparation of Polyester Z Pellets) In producing polyester A pellets in the same manner as above, after the esterification reaction was completed, spherical silica (SO-C1 manufactured by Admatec Co., Ltd., particle size: 0.2 μm to 0.4 μm) was added, and then a polycondensation reaction was carried out to obtain silica-containing polyester Z pellets (referred to as polyester Z in Table 6) containing 1% by mass of spherical silica relative to the mass of polyester A.
[0559] (Preparation of temporary support 8) A temporary support 8 (a single-layer polyethylene terephthalate film having a thickness of 16 μm) was prepared in the same manner as in the preparation of the temporary support 1, except that the particle-containing layer was not formed. The arithmetic mean roughness Ra of the first surface of the temporary support 8 was 0.2 nm.
[0560] (Preparation of temporary support 9) A surface irregularity was formed on the first surface of the temporary support 8 by thermal nanoimprinting (heating temperature: 130° C., pressure: 0.1 MPa) to prepare a temporary support 9 (a single-layer polyethylene terephthalate film having a thickness of 16 μm). The arithmetic mean roughness Ra of the first surface of the temporary support 9 was 35 nm.
[0561] (Preparation of temporary supports 10 to 15) The mixture of raw materials prepared for each layer according to the composition shown in Table 6 was stirred in a blender and then fed into a vented twin screw extruder for layers A and B. The mixture was melt extruded at 275°C, filtered twice through a filter with a pore size of 3 μm, and then joined and laminated in a rectangular 3-layer joining block to form a 3-layer laminate consisting of layers A, B, and A. The mixture was then passed through a slit die maintained at 285°C onto a cooling roll, and wound around a casting drum with a surface temperature of 25°C using an electrostatic casting method, followed by cooling and solidification to obtain an unstretched laminate film. The unstretched laminated film was successively stretched (longitudinal direction, width direction). First, longitudinal stretching was performed, and then width direction stretching was performed. The longitudinal stretching was performed by conveying the film with a Teflon (registered trademark) roll at 105 ° C., and then stretching 4.0 times at 120 ° C. with the difference in peripheral speed of the roll to obtain a uniaxially stretched film. Next, this uniaxially stretched film was stretched 4.0 times in the transverse direction at 115 ° C. in a stenter, and then heat-set at 230 ° C., relaxed 5% in the width direction, and cooled in the conveying process. After that, the edges were cut and then wound up to obtain an intermediate product of a biaxially stretched film having the thickness of each layer listed in Table 6. This intermediate product was slit with a slitter to obtain a roll of polyester film consisting of three layers. The obtained polyester films each having a three-layer laminate consisting of A layer / B layer / A layer were used as temporary supports 10-15.
[0562] (Preparation of temporary supports 16 and 18) A mixture of raw materials prepared according to the composition shown in Table 6 for each layer was stirred in a blender and then fed to vented twin-screw extruders for layers A, B, and C. The mixture was melt extruded at 275°C, filtered through a high-precision filter that captures 95% or more of foreign matter of 5 μm or more, and then joined and laminated in a rectangular 3-layer junction block to form a 3-layer laminate consisting of layers A, B, and C. A roll of a 3-layer polyester film was obtained in the same manner as in the preparation of temporary support 12, except that the mixture was melt extruded at 275°C, filtered through a high-precision filter that captures 95% or more of foreign matter of 5 μm or more, and then joined and laminated in a rectangular 3-layer junction block to form a 3-layer laminate consisting of layer...
Claims
1. A temporary support and a photosensitive resin layer are included in this order, The temporary support is a biaxially oriented polyester film consisting of two or more layers, a surface layer of the temporary support on the photosensitive resin layer side and a surface layer of the temporary support on the opposite side to the photosensitive resin layer side do not contain a filler, At least a surface layer on the side opposite to the photosensitive resin layer side of the temporary support contains a first polyester resin and a second polyester resin having an alicyclic structure and different in compatibility from the first polyester resin, and has a phase-separated structure; The photosensitive transfer material has an arithmetic mean roughness Ra of 1 nm to 50 nm on the surface of the temporary support opposite to the photosensitive resin layer side.
2. The photosensitive transfer material according to claim 1 , wherein the alicyclic structure is a cyclohexane ring.
3. 3. The photosensitive transfer material according to claim 1, wherein a surface layer of the temporary support opposite to the photosensitive resin layer contains copolymerized polyethylene terephthalate having isophthalic acid as a copolymerization component.
4. A method for producing a resin pattern using the photosensitive transfer material according to any one of claims 1 to 3, comprising the steps of: providing a substrate; a step of contacting the photosensitive transfer material with the substrate and disposing a photosensitive resin layer and a temporary support in this order on the substrate; A step of pattern-exposing the photosensitive resin layer; developing the exposed photosensitive resin layer to form a resin pattern; A method for producing a resin pattern comprising the steps of:
5. The method for producing a resin pattern according to claim 4 , wherein the line width of the resin pattern is 10 μm or less.
6. A method for producing a conductive pattern using the photosensitive transfer material according to any one of claims 1 to 3, comprising the steps of: Providing a substrate including a conductive layer; a step of contacting the photosensitive transfer material with the substrate and disposing a photosensitive resin layer and a temporary support in this order on the substrate; A step of pattern-exposing the photosensitive resin layer; developing the exposed photosensitive resin layer to form a resin pattern; a step of etching the conductive layer not covered by the resin pattern to form a conductive pattern; A method for producing a conductive pattern comprising the steps of:
Citation Information
Patent Citations
Laminated polyester film for dry-film photoresist
JP2004106322A
Pattern forming material and pattern forming method
JP2006154622A
Polyester film
JP2020084187A
Polyester film for dry film resist
WO2019203175A1